Laminate, hard coating film, and coating material composition

JP2025003505AActive Publication Date: 2025-01-09ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024182061
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-03-04
Filing Date
2024-10-17
Publication Date
2025-01-09
Estimated Expiration
2041-03-04

AI Technical Summary

Benefits of technology

【0012】 (第1の効果) 本発明によれば、高い耐摩耗性、密着性及び光学特性を有する積層体を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025003505000001
    Figure 2025003505000001
  • Figure 2025003505000002
    Figure 2025003505000002
  • Figure 2025003505000003
    Figure 2025003505000003
Patent Text Reader

Abstract

To provide, as a first object, a laminate which has high abrasion resistance, adhesiveness and optical properties, and to provide, as a second object, a hard coating film, a hard coating film-applied substrate, a coating material composition, and a window material, each of which has high abrasion resistance, durability and weather resistance.SOLUTION: A laminate containing: an adhesion layer-applied substrate containing a substrate and an adhesion layer disposed on the substrate, the adhesion layer containing adhesive emulsion particles (F), an inorganic oxide (G) and a light-shielding agent (S1); and a hard coating layer (C) disposed on the adhesion layer-applied substrate and containing a matrix component (B) containing an inorganic oxide (D), wherein a haze value H1 of the adhesion layer-applied substrate is larger than a haze value H2 of the laminate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate, a hard coat film, and a coating composition. [Background technology]

[0002] (First Background Art) The aqueous dispersion obtained by polymerization is used as a water-based paint because the coating film formed by drying at room temperature or under heating tends to exhibit barrier properties, contamination resistance, chemical resistance, flame retardancy, heat resistance, weather resistance, abrasion resistance, and abrasion resistance. When such an aqueous paint is used for an application requiring transparency, optical properties such as transparency and cloudiness, discoloration, whitening, and craze generation may become problems due to long-term exposure outdoors or to ultraviolet rays. Furthermore, when the paint is used as a top coat, the top coat is required to have abrasion resistance. From the viewpoint of abrasion resistance, a solvent-based paint may be used. It is relatively easy to incorporate an organic light-shielding agent into such a solvent-based paint while maintaining the properties of the paint and the resulting coating film. However, the use of water-based paint is desired from the viewpoint of the sanitary conditions at the work site and the burden on the global environment.

[0003] As a technique for improving the optical properties of water-based paints, Patent Document 1 describes a method of incorporating an ultraviolet absorber during polymerization for the purpose of imparting weather resistance. Patent Document 2 describes a method of dissolving an ultraviolet absorber in a film-forming auxiliary component and incorporating it. In addition, a method of adding an inorganic oxide to a resin material is described as a technique for imparting hard coat properties to a resin material (see, for example, Patent Documents 3 and 4).

[0004] (Second Background Art) Resin materials are excellent in moldability and light weight, but are often inferior to inorganic materials such as metals and glass in hardness, barrier properties, contamination resistance, chemical resistance, flame retardancy, heat resistance, weather resistance, etc. In particular, resin materials have significantly lower hardness than inorganic glass and are easily scratched on the surface, so they are often used with a hard coat applied, but it is difficult to provide the hard coat coating with resistance to contamination by soot and dust, to maintain performance under high temperature and humidity conditions, and to maintain the appearance when exposed to ultraviolet rays for a long period of time, and therefore hard-coated resin materials are not used in applications requiring high abrasion resistance, durability, and weather resistance.

[0005] For the purpose of imparting abrasion resistance to a resin material, a method using an active energy ray-curable resin composition (see, for example, Patent Document 5), a method of adding an inorganic oxide to a resin material (see, for example, Patent Document 3 and Patent Document 6), and a method of adding polymer particles to a resin material (see, for example, Patent Document 7) have been proposed. In addition, for the purpose of imparting weather resistance to a resin material, the combined use of an acrylic polymer and cerium oxide has been proposed (see, for example, Patent Document 8). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-12505 [Patent Document 2] Japanese Patent Application Publication No. 7-173404 [Patent Document 3] JP 2006-63244 A [Patent Document 4] Japanese Patent Application Publication No. 8-238683 [Patent Document 5] JP 2014-109712 A [Patent Document 6] Japanese Patent Application Publication No. 8-238683 [Patent Document 7] JP 2017-114949 A [Patent Document 8] Japanese Patent Application Publication No. 5-339400 Summary of the Invention [Problem to be solved by the invention]

[0007] (First issue) The methods described in Patent Documents 1 and 2 are general methods for imparting weather resistance to water-based paints, but the amount of UV absorber that can be contained in the coating film is small, making it difficult to impart high weather resistance. In addition, the coating film disposed on a substrate lacks adhesion. The methods of Patent Documents 3 and 4 are general methods for imparting abrasion resistance to resin materials, but they use solvent-based paints and are not easily applicable to water-based paints. As described above, there is still room for improvement in the coating film-coated substrates obtained from water-based paints in the prior art from the viewpoints of high abrasion resistance and optical properties.

[0008] The present invention has been made in view of the above problems, and a first object of the present invention is to provide a laminate having high abrasion resistance, adhesion and optical properties.

[0009] (Second issue) The methods of Patent Document 5 and Patent Document 3 are general methods for imparting abrasion resistance to a resin material, but it is difficult to impart high abrasion resistance. The method of Patent Document 6 is a general method that uses a flexible silicone polymer and hard inorganic oxide microparticles as a hard coat coating, but the silicone polymer, which corresponds to the matrix component, does not have sufficient hardness and therefore does not have sufficient abrasion resistance. The method of Patent Document 7 uses polymer particles, silicone polymer, and inorganic oxide fine particles as a hard coat coating film, and although the physical properties of the coating film are described, there is no description of the physical properties of each component, and the abrasion resistance is insufficient and there is no description of contamination resistance. According to Patent Document 8, although some improvement is observed in weather resistance, the level is not sufficient from the viewpoint of the balance of physical properties including abrasion resistance and durability. As described above, there is still room for improvement in the hard coat coatings of the conventional techniques from the viewpoints of high abrasion resistance, durability, and weather resistance.

[0010] The present invention has been made in consideration of the above problems, and a second object of the present invention is to provide a hard coat film, a substrate with a hard coat film, a coating composition, and a window material that have high abrasion resistance, durability, and weather resistance. [Means for solving the problem]

[0011] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by forming a laminate comprising a substrate with a predetermined adhesive layer and a hard coat layer, and have thus completed the present invention. That is, the present invention includes the following aspects. [1] A substrate having an adhesive layer, the adhesive layer being disposed on the substrate and containing adhesive emulsion particles (F), an inorganic oxide (G) and a light-shielding agent (S1); a hard coat layer (C) disposed on the substrate with the adhesive layer and including a matrix component (B) containing an inorganic oxide (D); A laminate comprising: A laminate, wherein a haze value H1 of the substrate with an adhesive layer is greater than a haze value H2 of the laminate. [2] The laminate according to [1], wherein H2 is 5% or less. [3] A substrate having an adhesive layer, the adhesive layer being disposed on the substrate and containing adhesive emulsion particles (F), an inorganic oxide (G) and a light-shielding agent (S1); a hard coat layer (C) disposed on the substrate with the adhesive layer and including a matrix component (B) containing an inorganic oxide (D); A laminate comprising: A laminate, wherein the surface roughness Ra1 of the substrate with an adhesive layer is greater than the surface roughness Ra2 of the laminate. [4] The laminate according to [3], wherein the Ra1 is 10 to 500 nm. [5] The laminate according to [3] or [4], wherein the Ra2 is less than 100 nm. [6] The laminate according to any one of [1] to [5], wherein the light-shielding agent (S1) contains an ultraviolet absorbing agent. [7] The laminate according to any one of [1] to [6], wherein the adhesive layer further contains a hindered amine-based light stabilizer. [8] the hard coat layer (C) further comprises polymer nanoparticles (A) dispersed in the matrix component (B); The Martens hardness HM of the polymer nanoparticles (A) A and the Martens hardness HM of the matrix component (B). B But, HM B / HM A > 1, The Martens hardness HM of the hard coat layer is 100 N / mm 2 The laminate according to any one of [1] to [7] above. [9] The laminate according to [8], wherein the average particle size of the polymer nanoparticles (A) is 10 nm or more and 400 nm or less.

[10] The laminate according to [8] or [9], wherein a volume fraction of the polymer nanoparticles (A) in the hard coat layer (C) is 2% or more and 80% or less.

[11] The polymer nanoparticles (A) contain a hydrolyzable silicon compound (a), The laminate according to any one of [8] to

[10] , wherein the content of the hydrolyzable silicon compound (a) in the polymer nanoparticles (A) is 50 mass % or more.

[12] The laminate according to

[11] , wherein the hydrolyzable silicon compound (a) comprises at least one selected from a compound containing an atomic group represented by the following formula (a-1), its hydrolysis product and condensation product, and a compound represented by the following formula (a-2), its hydrolysis product and condensation product: -R 1 n1 Six1 3-n1 (a-1) (In formula (a-1), R 1 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group, an alkynyl group, or an aryl group; R 1 may have a substituent containing a halogen, a hydroxy group, a mercapto group, an amino group, a (meth)acryloyl group, or an epoxy group, and X 1 represents a hydrolyzable group, and n1 represents an integer of 0 to 2. Six 2 4(a-2) (In formula (a-2), X 2 represents a hydrolyzable group.

[13] The laminate according to any one of [1] to

[12] , wherein the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Al, Zn, Ti, Zr, Sb, Mg, Sn, Bi, Co and Cu.

[14] The laminate according to any one of [1] to

[13] , wherein the hard coat layer (C) further contains a light-shielding agent (S2).

[15] The laminate according to any one of [1] to

[14] , wherein the inorganic oxide (G) is silica having a spherical and / or connected structure.

[16] The laminate according to any one of [1] to

[15] , wherein the adhesive layer contains a complex of the inorganic oxide (G) and the adhesive emulsion particles (F).

[17] The laminate according to any one of [1] to

[16] , wherein at least one selected from the group consisting of the inorganic oxide (G), the adhesive emulsion particles (F), and a complex of the inorganic oxide (G) and the adhesive emulsion particles (F) has an average particle size of 2 nm or more and 400 nm or less.

[18] The laminate according to any one of [1] to

[17] , wherein a mass ratio of the inorganic oxide (G) to the adhesive emulsion particles (F) is 1:0.1 to 1:10.

[19] The laminate according to any one of [1] to

[18] , wherein the adhesive layer further contains an isocyanate compound and / or a urethane compound.

[20] The laminate according to any one of [1] to

[19] , wherein when the hard coat layer is subjected to a Taber abrasion test in accordance with ASTM D1044 under conditions of an abrasion wheel CS-10F and a load of 500 g, the difference between the haze at 500 revolutions and the haze before the Taber abrasion test is 10 or less. [twenty one] The laminate according to any one of [1] to

[20] , wherein when the hard coat layer is subjected to a Taber abrasion test in accordance with ASTM D1044 under conditions of an abrasion wheel CS-10F and a load of 500 g, the difference between the haze at 1000 revolutions and the haze before the Taber abrasion test is 10 or less. [twenty two] The elastic recovery rate η of the hard coat layer measured by an indentation test conforming to ISO14577-1 IT The laminate according to any one of [1] to

[21] , wherein is 0.50 or more. [twenty three] The laminate according to any one of [1] to

[22] , wherein the hard coat layer has a thickness of 1 μm or more and 100 μm or less. [twenty four] The laminate according to any one of [1] to

[23] , wherein the matrix component (B) contains a hydrolyzable silicon compound (b). [twenty five] The laminate according to

[24] , wherein the hydrolyzable silicon compound (b) comprises one or more selected from a compound containing an atomic group represented by the following formula (b-1), its hydrolysis product and condensation product, and a compound represented by the following formula (b-2), its hydrolysis product and condensation product: -R 2 n2 Six 3 3-n2 (b-1) (In formula (b-1), R 2 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group, an alkynyl group, or an aryl group; R 2may have a substituent containing a halogen, a hydroxy group, a mercapto group, an amino group, a (meth)acryloyl group, or an epoxy group, and X 3 represents a hydrolyzable group, and n2 represents an integer of 0 to 2. Six 4 4(b-2) (In formula (b-2), X 4 represents a hydrolyzable group.

[26] The laminate according to any one of [1] to

[25] , wherein the inorganic oxide (D) has an average particle size of 2 nm or more and 150 nm or less.

[27] The laminate according to any one of [1] to

[26] , wherein the inorganic oxide (D) is silica particles.

[28] The laminate according to any one of [1] to

[27] , which is for use as an automobile member.

[29] a mixture of adhesive emulsion particles (F) and an inorganic oxide (G) and / or a complex of the inorganic oxide (G) and the adhesive emulsion particles (F); A light blocking agent (S1); A coating composition comprising: The average particle size of the mixture and / or complex is 2 nm or more and 2000 nm or less, A coating composition, wherein the mass ratio of the inorganic oxide (G) to the adhesive emulsion particles (F) is 1:0.1 to 1:10.

[30] The coating composition according to

[29] , wherein the light-shielding agent (S1) contains an ultraviolet absorber.

[31] The coating composition according to either

[29] or

[30] , further comprising a hindered amine light stabilizer.

[32] The coating composition according to any one of

[29] to

[31] , wherein the inorganic oxide (G) is silica having a spherical and / or connected structure.

[33] The coating composition according to any one of

[29] to

[32] , wherein the inorganic oxide (G) has an aspect ratio (major axis / minor axis) of 3 to 25.

[34] The coating composition according to any one of

[29] to

[33] , further comprising an isocyanate compound and / or a urethane compound.

[35] The coating composition according to

[34] , wherein the isocyanate compound is a water-dispersible isocyanate compound.

[36] The coating composition according to

[35] , wherein the water-dispersible isocyanate compound is a blocked isocyanate.

[37] A coating composition comprising polymer nanoparticles (A) and a matrix raw material component (B'), The elastic recovery rate η of the polymer nanoparticles (A) measured by an indentation test in accordance with ISO14577-1. ITA is between 0.30 and 0.90, The Martens hardness HM of the polymer nanoparticles (A) A and the Martens hardness HM of the matrix raw material component (B'). B' But, HM B' / HM A > 1, The matrix raw material component (B') contains an inorganic oxide (D), A coating composition, wherein the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Al, Zn, Ti, Zr, Sb, Mg, Sn, Bi, Co and Cu.

[38] The coating composition according to

[37] , further comprising a light-blocking agent (S2).

[39] The coating composition according to any one of

[29] to

[38] , wherein the polymer nanoparticles (A) and / or the adhesive emulsion particles (F) have a functional group (e) having a secondary amide group and / or a tertiary amide group.

[40] The coating composition according to any one of

[29] to

[39] , wherein the polymer nanoparticles (A) and / or the adhesive emulsion particles (F) have a functional group having a hydroxyl group.

[41] A hard coat coating film comprising polymer nanoparticles (A) and a matrix component (B), The Martens hardness HM of the polymer nanoparticles (A) A and the Martens hardness HM of the matrix component (B). B But, HM B / HM A > 1, The Martens hardness HM of the hard coat film is 100 N / mm 2 That's all. The matrix component (B) contains an inorganic oxide (D), The hard coat film, wherein the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Al, Zn, Ti, Zr, Sb, Mg, Sn, Bi, Co and Cu. Effect of the Invention

[0012] (First effect) According to the present invention, it is possible to provide a laminate having high abrasion resistance, adhesion and optical properties.

[0013] (Second effect) According to the present invention, it is possible to provide a hard coat film, a substrate with a hard coat film, a coating composition, and a window material, all of which have high abrasion resistance, durability, and weather resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as the present embodiment) will be described in detail. Note that the present invention is not limited to the following embodiment, and can be modified in various ways within the scope of the gist of the present invention.

[0015] <<First embodiment>> Here, a first aspect according to this embodiment (also referred to as "first embodiment" in this specification) will be described in detail.

[0016] <Laminate> The laminate of this embodiment (hereinafter, unless otherwise specified, "this embodiment" in the section <<First embodiment>> means the first embodiment) is a laminate comprising a substrate, a substrate with an adhesive layer disposed on the substrate and having an adhesive layer containing adhesive emulsion particles (F), an inorganic oxide (G) and a light-shielding agent, and a hard coat layer disposed on the substrate with an adhesive layer and containing a matrix component (B) containing an inorganic oxide (D), wherein the haze value H1 of the substrate with an adhesive layer is greater than the haze value H2 of the laminate. The laminate of this embodiment is configured as described above, and therefore has high abrasion resistance, adhesion and optical properties. In this embodiment, from the viewpoint of adhesion, the ratio of H1 to H2 (H1 / H2) is preferably 2 or more, more preferably 5 or more, further preferably 10 or more, and particularly preferably 20 or more. In addition, in this embodiment, even if it is difficult to confirm the magnitude relationship between H1 and H2, the magnitude relationship can be estimated by evaluating the surface roughness. That is, the laminate of this embodiment is a laminate including a substrate, a substrate with an adhesive layer disposed on the substrate and having an adhesive layer containing adhesive emulsion particles (F), an inorganic oxide (G) and a light-shielding agent (S1), and a hard coat layer (C) disposed on the substrate with an adhesive layer and containing a matrix component (B) containing an inorganic oxide (D), and the surface roughness Ra1 of the substrate with an adhesive layer can be specified as being larger than the surface roughness Ra2 of the laminate. In this embodiment, from the viewpoint of adhesion, the ratio of Ra1 to Ra2 (Ra1 / Ra2) is preferably 1.5 or more, more preferably 2 or more, even more preferably 3 or more, and particularly preferably 5 or more. The laminate of the present embodiment is configured as described above, and therefore has high abrasion resistance, adhesion and optical properties. The laminate of the present embodiment exhibits high levels of abrasion resistance, adhesion and optical properties, and is therefore useful, but not limited to, as a hard coat for building materials, automobile parts, electronic devices, electrical products, etc., and is particularly preferably used for automobile parts.

[0017] [Substrate with adhesive layer] The substrate with an adhesive layer in this embodiment has a substrate and an adhesive layer disposed on the substrate, the adhesive layer containing adhesive emulsion particles (F), an inorganic oxide (G) and a light-shielding agent. In this embodiment, the adhesive layer is disposed on at least one surface and / or both surfaces of the substrate.

[0018] [Base material] The substrate in this embodiment is not particularly limited, but includes resin, metal, glass, etc. The shape of the substrate is not limited to the following, but includes, for example, a plate-like shape, a shape including unevenness, a shape including a curved surface, a hollow shape, a porous shape, and a combination thereof. The substrate may be of any type, and may include, for example, a sheet, a film, a fiber, etc. Among them, resin is preferable from the viewpoint of hard coat property and moldability. The resin used as the substrate may be, but is not limited to the following, for example, a thermoplastic resin or a thermosetting resin. The thermoplastic resin used as the substrate may be, but is not limited to the following, for example, polyethylene, polypropylene, polystyrene, ABS resin, vinyl chloride resin, methyl methacrylate resin, nylon, fluororesin, polycarbonate, polyester resin, etc. The thermosetting resin used as the substrate may be, but is not limited to the following, for example, a phenol resin, a urea resin, a melamine resin, an unsaturated polyester resin, an epoxy resin, a silicon resin, a silicone rubber, a SB rubber, a natural rubber, a thermosetting elastomer, etc.

[0019] [Adhesive layer] The adhesive layer in this embodiment contains adhesive emulsion particles (F), an inorganic oxide (G), and a light-shielding agent.

[0020] [Adhesive emulsion particles (F)] The adhesive emulsion particles (F) in this embodiment play a role of imparting flexibility and improving adhesion to the substrate. The adhesive emulsion particles (F) are not particularly limited, but are particles composed of one or more of polyurethane, polyester, poly(meth)acrylate, polyvinyl acetate, polybutadiene, polyvinyl chloride, chlorinated polypropylene, polyethylene, polystyrene, polystyrene-(meth)acrylate copolymer, rosin derivative, alcohol adduct of styrene-maleic anhydride copolymer, polycarbonyl compound such as cellulose resin, silicone compound, etc. In this embodiment, the adhesive emulsion particles (F) are preferably poly(meth)acrylate.

[0021] The adhesive emulsion particle (F) in this embodiment is prepared by any method, but preferably has a structure obtained by polymerizing a vinyl monomer in the presence of water and an emulsifier. When the adhesive emulsion particle (F) thus obtained is included in the adhesive layer, it tends to maintain better adhesion to the substrate.

[0022] The vinyl monomer is not particularly limited, but examples thereof include (meth)acrylic acid esters, aromatic vinyl compounds, and vinyl cyanide compounds, as well as monomers containing functional groups such as carboxyl group-containing vinyl monomers, hydroxyl group-containing vinyl monomers, epoxy group-containing vinyl monomers, carbonyl group-containing vinyl monomers, and vinyl monomers having secondary and / or tertiary amide groups.

[0023] The (meth)acrylic acid ester is not particularly limited, but examples thereof include (meth)acrylic acid alkyl esters having an alkyl moiety with 1 to 50 carbon atoms, and (poly)oxyethylene di(meth)acrylates having 1 to 100 ethylene oxide groups.

[0024] The (meth)acrylic acid alkyl ester is not particularly limited, but examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, cyclohexyl (meth)acrylate, lauryl (meth)acrylate, and dodecyl (meth)acrylate.

[0025] The (poly)oxyethylene di(meth)acrylate is not particularly limited, but examples thereof include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, diethylene glycol methoxy(meth)acrylate, and tetraethylene glycol di(meth)acrylate.

[0026] The aromatic vinyl compound is not particularly limited, but examples thereof include styrene and 4-vinyltoluene.

[0027] The vinyl cyanide compound is not particularly limited, but examples thereof include acrylonitrile and methacrylonitrile.

[0028] The carboxyl group-containing vinyl monomer is not particularly limited, and examples thereof include (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, maleic anhydride, and half esters of dibasic acids such as itaconic acid, maleic acid, and fumaric acid. When a carboxyl group-containing vinyl monomer is used, a carboxyl group can be introduced into the adhesive emulsion particles (F) in this embodiment, and the electrostatic repulsion between the particles improves the stability of the emulsion, and resistance to external dispersion destruction such as aggregation during stirring tends to improve. In this case, from the viewpoint of further improving the electrostatic repulsion, the introduced carboxyl group can be partially or completely neutralized with ammonia, amines such as triethylamine and dimethylethanolamine, or bases such as NaOH and KOH.

[0029] The hydroxyl group-containing vinyl monomer is not particularly limited, but examples thereof include hydroxyalkyl esters of (meth)acrylic acid such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; hydroxyalkyl esters of fumaric acid such as di-2-hydroxyethyl fumarate and mono-2-hydroxyethyl monobutyl fumarate; allyl alcohol and (poly)oxyethylene mono(meth)acrylate having 1 to 100 ethylene oxide groups; (poly)oxypropylene mono(meth)acrylate having 1 to 100 propylene oxide groups; and further, "Placcel FM, FA Monomer" (trade name of caprolactone addition monomer manufactured by Daicel Chemical Industries, Ltd.) and other hydroxyalkyl esters of α,β-ethylenically unsaturated carboxylic acids.

[0030] The (poly)oxyethylene (meth)acrylate is not particularly limited, but examples thereof include ethylene glycol (meth)acrylate, ethylene glycol methoxy(meth)acrylate, diethylene glycol (meth)acrylate, diethylene glycol methoxy(meth)acrylate, tetraethylene glycol (meth)acrylate, and tetraethylene glycol methoxy(meth)acrylate.

[0031] The (poly)oxypropylene (meth)acrylate is not particularly limited, but examples thereof include propylene glycol (meth)acrylate, propylene glycol methoxy(meth)acrylate, dipropylene glycol (meth)acrylate, dipropylene glycol methoxy(meth)acrylate, tetrapropylene glycol (meth)acrylate, and tetrapropylene glycol methoxy(meth)acrylate.

[0032] The epoxy group-containing vinyl monomer is not particularly limited, but examples thereof include glycidyl group-containing vinyl monomers, etc. The glycidyl group-containing vinyl monomer is not particularly limited, but examples thereof include glycidyl (meth)acrylate, allyl glycidyl ether, allyl dimethyl glycidyl ether, etc.

[0033] The carbonyl-containing vinyl monomer is not particularly limited, but examples thereof include diacetone acrylamide.

[0034] Specific examples of vinyl monomers other than those mentioned above include, but are not limited to, olefins such as ethylene, propylene, and isobutylene; dienes such as butadiene; haloolefins such as vinyl chloride, vinylidene chloride fluoride, tetrafluoroethylene, and chlorotrifluoroethylene; vinyl carboxylate esters such as vinyl acetate, vinyl propionate, vinyl n-butyrate, vinyl benzoate, vinyl pt-butylbenzoate, vinyl pivalate, vinyl 2-ethylhexanoate, vinyl versatate, and vinyl laurate; isopropenyl carboxylate esters such as isopropenyl acetate and isopropenyl propionate; ethyl vinyl ether; Examples of the acrylates include vinyl ethers such as allyl vinyl ether and cyclohexyl vinyl ether, allyl esters such as allyl acetate and allyl benzoate, allyl ethers such as allyl ethyl ether and allyl phenyl ether, as well as 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-(meth)acryloyloxy-1,2,2,6,6-pentamethylpiperidine, perfluoromethyl(meth)acrylate, perfluoropropyl(meth)acrylate, perfluoropropylmethyl(meth)acrylate, vinylpyrrolidone, trimethylolpropane tri(meth)acrylate, allyl(meth)acrylate, and the like, and combinations thereof.

[0035] The vinyl monomer having the secondary and / or tertiary amide group is not particularly limited, and examples thereof include N-alkyl or N-alkylene substituted (meth)acrylamides, etc. Specific examples thereof include N-methylacrylamide, N-methylmethacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N-ethylmethacrylamide, N-methyl-N-ethylacrylamide, N-methyl-N-ethylmethacrylamide, N-isopropylacrylamide, Nn-propylacrylamide, N-isopropylmethacrylamide, Nn-propylmethacrylamide, N-methyl-Nn-propylacrylamide, N-methyl-N-iso ... Examples of the monomer units include N-vinyl amide, N-acryloylpyrrolidine, N-methacryloylpyrrolidine, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylhexahydroazepine, N-acryloylmorpholine, N-methacryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, N,N'-methylenebisacrylamide, N,N'-methylenebismethacrylamide, N-vinylacetamide, diacetone acrylamide, diacetone methacrylamide, N-methylolacrylamide, and N-methylol methacrylamide. The silicone compound is not particularly limited, but examples thereof include trimethoxysilane, triethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethoxysilane, diethoxysilane, methyldimethoxysilane, methyldiethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethoxydiphenylsilane, diethoxydiphenylsilane, 3 Examples of hydrolysis and condensation products include 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, tetramethoxysilane, and tetraethoxysilane.

[0036] The adhesive emulsion particles (F) may contain an emulsifier. The emulsifier is not particularly limited, and examples thereof include acidic emulsifiers such as alkylbenzenesulfonic acid, alkylsulfonic acid, alkylsulfosuccinic acid, polyoxyethylene alkylsulfuric acid, polyoxyethylene alkylarylsulfuric acid, and polyoxyethylene distyrylphenyl ether sulfonic acid; anionic surfactants such as alkali metal (Li, Na, K, etc.) salts of acidic emulsifiers, ammonium salts of acidic emulsifiers, and fatty acid soaps; cationic surfactants of quaternary ammonium salts, pyridinium salts, and imidazolinium salts, such as alkyltrimethylammonium bromides, alkylpyridinium bromides, and imidazolinium laurates; nonionic surfactants such as polyoxyethylene alkylaryl ethers, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene oxypropylene block copolymers, and polyoxyethylene distyrylphenyl ethers, and reactive emulsifiers having radical polymerizable double bonds.

[0037] Examples of the reactive emulsifier having a radically polymerizable double bond include, but are not limited to, Eleminol JS-2 (trade name, manufactured by Sanyo Chemical Industries, Ltd.), Latemul S-120, S-180A or S-180 (trade name, manufactured by Kao Corporation), Aqualon HS-10, KH-1025, RN-10, RN-20, RN30, RN50 (trade name, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), Adeka Reasoap SE1025, SR-1025, NE-20, NE-30, NE-40 (trade name, manufactured by Asahi Denka Kogyo Co., Ltd.), ammonium salt of p-styrenesulfonic acid, sodium salt of p-styrenesulfonic acid, potassium salt of p-styrenesulfonic acid, alkylsulfonic acid (meth)acrylate such as 2-sulfoethyl acrylate, methylpropanesulfonic acid (meth)acrylamide, ammonium salt of allylsulfonic acid, sodium salt of allylsulfonic acid, potassium salt of allylsulfonic acid, and the like.

[0038] [Average particle size of adhesive emulsion particles (F)] The average particle size of the adhesive emulsion particles (F) in this embodiment is determined from the size of the particles observed by cross-sectional SEM or dynamic light scattering. The average particle size of the adhesive emulsion particles (F) is not particularly limited, but is preferably 300 nm or less. By adjusting the average particle size of the adhesive emulsion particles (F) to the above range, there is a tendency that an adhesive layer with even better adhesion can be formed by improving the contact area with the substrate. In addition, from the viewpoint of improving the transparency of the obtained adhesive layer, the average particle size is more preferably 200 nm or less, and from the viewpoint of improving the storage stability of the raw material composition of the adhesive layer, it is preferably 10 nm or more, and more preferably 50 nm or more. The average particle size of the adhesive emulsion particles (F) can be measured by the method described in the examples below.

[0039] [Inorganic oxide (G)] The adhesive layer in this embodiment contains an inorganic oxide (G) from the viewpoint of improving adhesion through interaction with the hard coat layer. The adhesive layer in this embodiment contains adhesive emulsion particles (F) and inorganic oxide (G), which increases the surface roughness of the adhesive layer, and is considered to improve adhesion. The surface roughness of the adhesive layer can be evaluated, for example, by comparing the minimum film-forming temperatures measured in accordance with JIS K6828-2 using a thermal gradient tester between the adhesive emulsion particles (F) and the inorganic oxide (G). That is, it can be indirectly confirmed that the adhesive layer has sufficient surface roughness by the minimum film-forming temperature T1 of the adhesive emulsion particles (F) being lower than the minimum film-forming temperature T2 of the inorganic oxide (G). The specific method for measuring the minimum film-forming temperatures T1 and T2 is based on the method described in the examples below.

[0040] Specific examples of the inorganic oxide (G) in this embodiment include, but are not limited to, oxides of silicon, aluminum, titanium, zirconium, zinc, cerium, tin, indium, gallium, germanium, antimony, molybdenum, niobium, magnesium, bismuth, cobalt, copper, etc. These may be used alone or in mixture. Among the above, the inorganic oxide (G) is preferably silica particles. On the other hand, from the viewpoint of improving optical properties, the inorganic oxide (G) preferably contains at least one selected from the group consisting of cerium oxide, zinc oxide, aluminum oxide, zirconium oxide, niobium oxide, bismuth oxide, cobalt oxide, copper oxide, tin oxide, and titanium oxide.

[0041] In the present embodiment, the primary average particle diameter of the inorganic oxide (G) is preferably 2 nm or more from the viewpoint of improving the storage stability of the raw material composition of the adhesive layer. From the viewpoint of improving the transparency of the laminate as a whole, it is preferably 150 nm or less, more preferably 100 nm or less, and even more preferably 50 nm or less. Therefore, the primary average particle diameter is preferably 2 nm or more and 100 nm or less, more preferably 2 nm or more and 50 nm or less, and even more preferably 4 nm or more and 50 nm or less. The primary average particle diameter can be measured by the method described in the examples below.

[0042] The inorganic oxide (G) is not particularly limited, but from the viewpoint of interaction with the hydrolyzable silicon compound (b) described later and from the viewpoint of adhesion with the hard coat layer, silica particles, such as dry silica and colloidal silica, are preferred. Colloidal silica is preferred because it can be used in the form of an aqueous dispersion.

[0043] [Colloidal silica preferably used as inorganic oxide (G)] The acidic colloidal silica with water as a dispersion medium that is preferably used in this embodiment is not particularly limited, but can be prepared by the sol-gel method or a commercially available product. When preparing by the sol-gel method, reference can be made to Werner Stober et al.; J. Colloid and Interface Sci., 26, 62-69 (1968), Rickey D. Badley et al.; Lang muir 6, 792-801 (1990), Journal of the Color Materials Association, 61 [9] 488-493 (1988), etc. When using commercially available products, examples include Snowtex-O, Snowtex-OS, Snowtex-OXS, Snowtex-O-40, Snowtex-OL, Snowtex-OYL, Snowtex-OUP, Snowtex-PS-SO, Snowtex-PS-MO, Snowtex-AK-XS, Snowtex-AK, Snowtex-AK-L, Snowtex-AK-YL, Snowtex-AK-PS-S (product names, manufactured by Nissan Chemical Industries, Ltd.), Adelite AT-20Q (product name, manufactured by Asahi Denka Kogyo Co., Ltd.), Crebosol 20H12, Crebosol 30CAL25 (product names, manufactured by Clariant Japan Co., Ltd.), and the like.

[0044] In addition, examples of basic colloidal silica include silica stabilized by the addition of alkali metal ions, ammonium ions, and amines, and are not particularly limited. Examples of such basic colloidal silica include, but are not limited to, Snowtex-20, Snowtex-30, Snowtex-XS, Snowtex-50, Snowtex-30L, Snowtex-XL, Snowtex-YL, Snowtex-ZL, Snowtex-UP, Snowtex-ST-PS-S, Snowtex-ST-PS-M, Snowtex-C, Snowtex-CXS, Snowtex-CM, Snowtex-N, Snowtex-NXS, Snowtex-NS, Snowtex-N-4, 0 (trade name, manufactured by Nissan Chemical Industries, Ltd.), Adelite AT-20, Adelite AT-30, Adelite AT-20N, Adelite AT-30N, Adelite AT-20A, Adelite AT-30A, Adelite AT-40, Adelite AT-50 (trade name, manufactured by Asahi Denka Kogyo Co., Ltd.), Crebosol 30R9, Crebosol 30R50, Crebosol 50R50 (trade name, manufactured by Clariant Japan Co., Ltd.), Ludox HS-40, Ludox HS-30, Ludox LS, Ludox AS-30, Ludox SM-AS, Ludox AM, Ludox HSA and Ludox SM (trade name, manufactured by DuPont) are examples of such.

[0045] Furthermore, the colloidal silica having a water-soluble solvent as a dispersion medium is not particularly limited, but examples thereof include MA-ST-M (methanol dispersion type having a particle size of 20 to 25 nm), IPA-ST (isopropyl alcohol dispersion type having a particle size of 10 to 15 nm), EG-ST (ethylene glycol dispersion type having a particle size of 10 to 15 nm), EGST-ZL (ethylene glycol dispersion type having a particle size of 70 to 100 nm), NPC-ST (ethylene glycol monopropyl ether dispersion type having a particle size of 10 to 15 nm), and TOL-ST (toluene dispersion type having a particle size of 10 to 15 nm), all manufactured by Nissan Chemical Industries, Ltd.

[0046] The dry silica particles are not particularly limited, but examples thereof include AEROSIL manufactured by Nippon Aerosil Co., Ltd. and Reolosil manufactured by Tokuyama Corporation.

[0047] The silica particles may contain an inorganic base (eg, sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia, etc.) or an organic base (eg, tetramethylammonium, triethylamine, etc.) as a stabilizer.

[0048] [Shape of inorganic oxide (G)] Furthermore, the shape of the inorganic oxide (G) in this embodiment is not limited to the following, and may be, for example, one or a mixture of two or more of spherical, angular, polyhedral, elliptical, flat, linear, beaded, and chain-like. In this embodiment, from the viewpoint of hardness and transparency of the laminate, it is preferable that the inorganic oxide (G) has a spherical and / or beaded or chain-like connection structure. Furthermore, from the viewpoint of adhesion of the laminate, it is more preferable that the inorganic oxide (G) has a beaded or chain-like connection structure. Here, the beaded structure means a structure in which spherical primary particles are connected in a beaded shape, and the chain-like structure means a structure in which spherical primary particles are connected in a chain-like shape. In this embodiment, it is particularly preferable that the inorganic oxide (G) is silica having a spherical and / or connected structure. The aspect ratio (major axis / minor axis) of the beaded or chain-like inorganic oxide (G) is preferably 3 to 25. From the viewpoint of adhesion, the aspect ratio (major axis / minor axis) is preferably 3 or more. From the viewpoint of transparency, the aspect ratio (major axis / minor axis) is preferably 25 or less. The aspect ratio can be measured by the method described in the examples below.

[0049] [Complex of adhesive emulsion particles (F) and inorganic oxide (G)] The inorganic oxide (G) may be previously composited with the adhesive emulsion particle (F). The composite of the adhesive emulsion particle (F) and the inorganic oxide (G) can be obtained, for example, by polymerizing the vinyl monomer constituting the adhesive emulsion particle (F) in the presence of the inorganic oxide (G). From the viewpoint of the interaction with the inorganic oxide (G), the vinyl monomer preferably contains the vinyl monomer having the secondary and / or tertiary amide group described above. A composite can be preferably formed by hydrogen bonding between the hydroxyl group of the inorganic oxide (G) and the secondary and / or tertiary amide group.

[0050] In this embodiment, the average particle diameter of at least one selected from the group consisting of the inorganic oxide (G), the adhesive emulsion particles (F), and the complex of the inorganic oxide (G) and the adhesive emulsion particles (F) is preferably 2 nm or more and 400 nm or less from the viewpoint of transparency and adhesion. The average particle diameter can be measured by the method described in the Examples described later. Here, the adhesive layer in this embodiment can be obtained by applying the coating composition (J) described later to a substrate and forming a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, etc., and therefore, if the average particle diameters of the inorganic oxide (G), the adhesive emulsion particles (F), and the complex of the inorganic oxide (G) and the adhesive emulsion particles (F) in the coating composition (J) are known, they can be determined as being closely consistent with the average particle diameters of the inorganic oxide (G), the adhesive emulsion particles (F), and the complex of the inorganic oxide (G) and the adhesive emulsion particles (F) in the corresponding adhesive layer, and each average particle diameter in the adhesive layer can be determined.

[0051] From the viewpoint of adhesion, the mass ratio of the adhesive emulsion particles (F) to the inorganic oxide (G) is preferably 1:0.1 to 1:10, more preferably 1:0.3 to 1:5, and even more preferably 1:0.5 to 1:2. Here, the adhesive layer in this embodiment can be obtained by applying the coating composition (J) described later to a substrate and forming a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, etc. Therefore, if the mass ratio of the adhesive emulsion particles (F) to the inorganic oxide (G) in the coating composition (J) is known, the mass ratio in the adhesive layer can be determined as being in good agreement with the mass ratio of the adhesive emulsion particles (F) to the inorganic oxide (G) in the corresponding adhesive layer.

[0052] The thickness of the adhesive layer is preferably 0.1 μm or more, more preferably 0.3 μm or more, from the viewpoint of adhesion, and is preferably 100.0 μm or less, more preferably 50.0 μm or less, from the viewpoint of transparency.

[0053] [Light blocking agent] The adhesive layer of this embodiment further contains a light-shielding agent in addition to the adhesive emulsion particles (F) and the inorganic oxide (G) from the viewpoint of ensuring optical properties. The light-shielding agent is not particularly limited, but it is preferable to contain an ultraviolet absorbing agent from the viewpoint of improving optical properties. Specific examples of the ultraviolet absorbing agent include, but are not limited to, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2,2'-dihydroxy-4-methoxybenzophenone ... benzophenone-based ultraviolet absorbers such as hydroxy-4,4'-dimethoxybenzophenone (BASF's trade name "UVINUL3049"), 2,2',4,4'-tetrahydroxybenzophenone (BASF's trade name "UVINUL3050"), 4-dodecyloxy-2-hydroxybenzophenone, 5-benzoyl-2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-hydroxy-4-stearyloxybenzophenone, and 4,6-dibenzoylresortinol;2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-octylphenyl)benzotriazole, 2-[2'-hydroxy-3',5'-bis(α,α'-dimethylbenzyl)phenyl] Benzotriazole), methyl-3-[3-tert-butyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]propionate and polyethylene glycol (molecular weight 300) condensation product (BASF product name "TINUVIN 1130"), isooctyl-3-[3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionate (BASF product name "TINUVIN 384"), 2-(3-dodecyl-5-methyl-2-hydroxyphenyl)propionate (BASF product name "TINUVIN 384"), nyl)benzotriazole (trade name "TINUVIN571" manufactured by BASF), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-4'-octoxyphenyl)benzotriazole, 2-[2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole, benzotriazole-based ultraviolet absorbers such as 2,2-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (trade name "TINUVIN 900" manufactured by BASF), TINUVIN 384-2, TINUVIN 326, TINUVIN 327, TINUVIN 109, TINUVIN 970, TINUVIN 328, TINUVIN 171, TINUVIN 970, TINUVIN PS, TINUVIN P, TINUVIN 99-2, and TINVIN 928 (trade names, manufactured by BASF);2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bisbutyloxyphenyl) -1,3,5-triazine (trade name "TINUVIN 460" manufactured by BASF), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (trade name "TINUVIN 479" manufactured by BASF), TINUVIN 400, TINUVIN 405, TINUVIN 477, TINUVIN 1600 (trade names, manufactured by BASF), and other triazine-based ultraviolet absorbers; HOSTAVIN PR25, HOSTAVIN B-CAP, HOSTAVIN VSU (trade names, manufactured by Clariant), and other malonic acid ester-based ultraviolet absorbers; HOSTAVIN 3206 LIQ, HOSTAVIN VSU P, HOSTAVIN 3212 LIQ (trade name, manufactured by Clariant) and other anilide-based ultraviolet absorbers; amyl salicylate, menthyl salicylate, homomenthyl salicylate, octyl salicylate, phenyl salicylate, benzyl salicylate, p-isopropanol phenyl salicylate and other salicylate-based ultraviolet absorbers; ethyl-2-cyano-3,3-diphenylacrylate (trade name "UVINUL3035" manufactured by BASF) cyanoacrylate-based ultraviolet absorbers such as (2-ethylhexyl)-2-cyano-3,3-diphenylacrylate (BASF's trade name "UVINUL3039") and 1,3-bis((2'-cyano-3',3'-diphenylacryloyl)oxy)-2,2-bis-(((2'-cyano-3',3'-diphenylacryloyl)oxy)methyl)propane (BASF's trade name "UVINUL3030");2-hydroxy-4-acryloxybenzophenone, 2-hydroxy-4-methacryloxybenzophenone, 2-hydroxy-5-acryloxybenzophenone, 2-hydroxy-5-methacryloxybenzophenone, 2-hydroxy-4-(acryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-diethoxy)benzophenone, 2-hydroxy-4-(acryloxy-triethoxy)benzophenone, 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole (trade name "RUVA-93" manufactured by Otsuka Chemical Co., Ltd.), 2-(2'-hydroxy-5'-methacryloxyethyl-3-tert-butylphenyl)-2H-benzotriazole, 2- Examples of such ultraviolet absorbents include radically polymerizable ultraviolet absorbents having a radically polymerizable double bond in the molecule, such as (2'-hydroxy-5'-methacryloxypropyl-3-tert-butylphenyl)-5-chloro-2H-benzotriazole and 3-methacryloyl-2-hydroxypropyl-3-[3'-(2''-benzotriazolyl)-4-hydroxy-5-tert-butyl]phenylpropionate (trade name "CGL-104" manufactured by Ciba-Geigy Japan Ltd.); ultraviolet absorbing polymers such as UV-G101, UV-G301, UV-G137, UV-G12, and UV-G13 (trade names manufactured by Nippon Shokubai Co., Ltd.); and ultraviolet absorbents reactive with silanol groups, isocyanate groups, epoxy groups, semicarbazide groups, and hydrazide groups, and these may be used alone or in combination of two or more kinds. Among these, from the viewpoint of ultraviolet absorbing ability, the ultraviolet absorber preferably includes at least one selected from the group consisting of benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, triazine-based ultraviolet absorbers, malonic acid ester-based ultraviolet absorbers, anilide-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, and cyanoacrylate-based ultraviolet absorbers, and more preferably includes at least one selected from the group consisting of benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, triazine-based ultraviolet absorbers, and cyanoacrylate-based ultraviolet absorbers;

[0054] [Components that may be included in the adhesive layer] The adhesive layer in this embodiment is not particularly limited as long as it contains adhesive emulsion particles (F), inorganic oxide (G) and a light-shielding agent, and may contain other components. The other components are not particularly limited, but include, for example, thermoplastic resins, thermosetting resins, rubber elastomers, etc., among which acrylic resins, acrylic urethane resins, urethane resins, silicone resins, etc. are preferred. The adhesive layer may also contain any appropriate additives as necessary. The additives include, but are not limited to, crosslinking agents, tackifiers, plasticizers, pigments, dyes, fillers, antioxidants, conductive materials, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, catalysts, etc., and from the viewpoint of optical properties, it is preferable to include a light stabilizer and / or an antioxidant. From the same viewpoint, the light stabilizer is not particularly limited, but includes, for example, hindered amine compounds, benzotriazole compounds, triazine compounds, benzophenone compounds, benzoate compounds, etc. The antioxidant is not particularly limited, but examples thereof include phenol-based compounds, amine-based compounds, phosphorus-based compounds, and sulfur-based compounds. Examples of the crosslinking agent include, but are not limited to, isocyanate-based crosslinking agents, epoxy-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, amine-based crosslinking agents, peroxide-based crosslinking agents, melamine-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, and metal salt-based crosslinking agents. Examples of light stabilizers include, but are not limited to, bis(2,2,6,6-tetramethyl-4-piperidyl)succinate, bis(2,2,6,6-tetramethylpiperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2-butylmalonate, 1-[2-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propynyloxy]ethyl]-4-[3-(3,5-di-tert-butyl -4-hydroxyphenyl)propynyloxy]-2,2,6,6-tetramethylpiperidine, mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl-1,2,2,6,6-pentamethyl-4-piperidyl-sebacate (BASF's trade name "TINUVIN 292"), bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, TINUVIN 123, TINUVIN 144, TINUVIN 152, TINUVIN 249, TIN hindered amine light stabilizers such as UVIN292 and TINUVIN5100 (trade names, manufactured by BASF); 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, 1,2,2,6,6-pentamethyl-4-piperidyl acrylate, 2,2,6,6-tetramethyl-4-piperidyl methacrylate, 2,2,6,6-tetramethyl-4-piperidyl acrylate, 1,2,2,6,6-pentamethyl-4-iminopiperidyl methacrylate, 2,2,6,6-tetramethyl-4-iminopiperidyl acrylate, Radical polymerizable hindered amine light stabilizers such as 4-cyano-2,2,6,6-tetramethyl-4-piperidyl methacrylate, 4-cyano-1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, etc.; light-stable polymers such as U-DOUBLE E-133, U-DOUBLE E-135, U-DOUBLE S-2000, U-DOUBLE S-2834, U-DOUBLE S-2840, U-DOUBLE S-2818, and U-DOUBLE S-2860 (product names, manufactured by Nippon Shokubai Co., Ltd.), etc. The above-mentioned components may be used alone or in combination of two or more.

[0055] The content of the ultraviolet absorber is preferably 1 part by mass or more, more preferably 5 parts by mass or more, even more preferably 12 parts by mass or more, and even more preferably 20 parts by mass or more, based on 100 parts by mass of the solid content of the adhesive emulsion particle (F) from the viewpoint of optical properties. Also, from the viewpoint of solubility, the content is preferably 300 parts by mass or less, more preferably 150 parts by mass or less, and even more preferably 50 parts by mass or less, based on 100 parts by mass of the solid content of the adhesive emulsion particle (F). The content of the light stabilizer is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.1 parts by mass or more, and even more preferably 0.5 parts by mass or more, based on 100 parts by mass of the solid content of the adhesive emulsion particle (F) from the viewpoint of optical properties. Also, from the viewpoint of coating stability, the content is preferably 100 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 10 parts by mass or less, based on 100 parts by mass of the solid content of the adhesive emulsion particle (F). The content of the antioxidant is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.1 parts by mass or more, and even more preferably 0.5 parts by mass or more, based on 100 parts by mass of the solid content of the adhesive emulsion particle (F) from the viewpoint of optical properties. Also, from the viewpoint of coating stability, the content is preferably 100 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 10 parts by mass or less, based on 100 parts by mass of the solid content of the adhesive emulsion particle (F).

[0056] [Isocyanate compounds] In the present embodiment, the adhesive layer preferably further contains an isocyanate compound and / or a urethane compound as an isocyanate-based crosslinking agent from the viewpoint of improving the adhesion between the adhesive layer and the substrate. When the adhesive layer further contains an isocyanate compound and / or a urethane compound, it is preferable to use adhesive emulsion particles (F) polymerized from a monomer containing the above-mentioned hydroxyl group-containing vinyl monomer. In this case, the hydroxyl group of the adhesive emulsion particles (F) and the isocyanate compound form a urethane bond during coating film formation, which tends to improve coating film adhesion and coating film strength.

[0057] The isocyanate compound refers to a compound having at least one isocyanate group in one molecule. The isocyanate compound may be a compound having two or more isocyanate groups in one molecule. Examples of the isocyanate compound include, but are not limited to, aliphatic diisocyanates such as 1,4-tetramethylene diisocyanate, ethyl (2,6-diisocyanato) hexanoate, 1,6-hexamethylene diisocyanate, 1,12-dodecamethylene diisocyanate, and 2,2,4- or 2,4,4-trimethylhexamethylene diisocyanate; 1,3,6-hexamethylene triisocyanate, 1,8-diisocyanato-4-isocyanatomethyloctane, and 2-isocyanatoethyl (2,6-diisocyanato) hexanoate; Aliphatic triisocyanates such as 1,3- or 1,4-bis(isocyanatomethylcyclohexane), 1,3- or 1,4-diisocyanatocyclohexane, 3,5,5-trimethyl(3-isocyanatomethyl)cyclohexylisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 2,5- or 2,6-diisocyanatomethylnorbornane; alicyclic triisocyanates such as 2,5- or 2,6-diisocyanatomethyl-2-isocyanatopropylnorbornane cyanates; aralkylene diisocyanates such as m-xylylene diisocyanate, α,α,α'α'-tetramethyl-m-xylylene diisocyanate; m- or p-phenylene diisocyanate, tolylene-2,4- or 2,6-diisocyanate, diphenylmethane-4,4'-diisocyanate, naphthalene-1,5-diisocyanate, diphenyl-4,4'-diisocyanate, 4,4'-diisocyanato-3,3'-dimethyldiphenyl, 3-methyl-diphenylmethane-4,4'-diisocyanate, diphenyl ether aromatic diisocyanates such as phenyl-4,4'-diisocyanate; aromatic triisocyanates such as triphenylmethane triisocyanate and tris(isocyanatophenyl)thiophosphate, and further diisocyanates or polyisocyanates having a uretdione structure obtained by cyclizing and dimerizing the isocyanate groups of the above diisocyanates or triisocyanates; polyisocyanates having an isocyanurate structure obtained by cyclizing and trimerizing the isocyanate groups of the above diisocyanates or triisocyanates;Examples of the polyisocyanate include a polyisocyanate having a biuret structure obtained by reacting the diisocyanate or triisocyanate with water; a polyisocyanate having an oxadiazinetrione structure obtained by reacting the diisocyanate or triisocyanate with carbon dioxide; a polyisocyanate having an allophanate structure obtained by reacting the diisocyanate or triisocyanate with various alcohols; and a polyisocyanate obtained by reacting the diisocyanate or triisocyanate with a compound containing active hydrogen such as a polyhydroxy compound, a polycarboxy compound, or a polyamine compound. Furthermore, examples of isocyanate compounds having an alkoxysilane moiety and / or a siloxane moiety in the molecule include 3-isocyanatepropyltriethoxysilane and / or hydrolysis condensates such as 3-isocyanatepropyltriethoxysilane. These compounds can be used alone or in combination of two or more. The isocyanate compound may be a blocked polyisocyanate in which an isocyanate group is reacted with a blocking agent. The blocking agent is not particularly limited, but examples thereof include oxime compounds, alcohol compounds, acid amide compounds, acid imide compounds, phenol compounds, amine compounds, active methylene compounds, imidazole compounds, and pyrazole compounds. The oxime compounds are not particularly limited, but examples thereof include formaldoxime, acetaldoxime, acetoxime, methyl ethyl ketoxime, and cyclohexanone oxime. The alcohol compounds are not particularly limited, but examples thereof include methanol, ethanol, 2-propanol, n-butanol, sec-butanol, 2-ethyl-1-hexanol, 2-methoxyethanol, 2-ethoxyethanol, and 2-butoxyethanol. The acid amide compounds are not particularly limited, but examples thereof include acetanilide, acetic acid amide, ε-caprolactam, δ-valerolactam, and γ-butyrolactam. The acid imide compounds are not particularly limited, but examples thereof include succinimide and maleimide. Examples of phenolic compounds include, but are not limited to, phenol, cresol, ethylphenol, butylphenol, nonylphenol, dinonylphenol, styrenated phenol, and hydroxybenzoic acid esters. Examples of amine compounds include, but are not limited to, diphenylamine, aniline, carbazole, di-n-propylamine, diisopropylamine, and isopropylethylamine. Examples of active methylene compounds include, but are not limited to, dimethyl malonate, diethyl malonate, methyl acetoacetate, ethyl acetoacetate, and acetylacetone. Examples of imidazole compounds include, but are not limited to, imidazole, and 2-methylimidazole. Examples of pyrazole compounds include, but are not limited to, pyrazole, 3-methylpyrazole, and 3,5-dimethylpyrazole.

[0058] Among the above polyisocyanate compounds, aliphatic or alicyclic diisocyanates or triisocyanates, aralkylene diisocyanates, or polyisocyanates derived therefrom are particularly preferred in terms of weather resistance and pot life. Furthermore, the polyisocyanates are preferably those having a biuret, isocyanurate, urethane, uretdione, allophanate, or other structure in the molecule. Those having a biuret structure are often excellent in adhesiveness. Those having an isocyanurate structure are often excellent in weather resistance. Those having a urethane structure using an alcohol compound with a long side chain are often excellent in elasticity and extensibility. Those having a uretdione structure or allophanate structure are often low in viscosity.

[0059] From the viewpoint of water dispersibility, the isocyanate compound is preferably a water-dispersible isocyanate compound obtained by reacting the polyisocyanate compound having two or more isocyanate groups in one molecule with a hydroxyl-containing hydrophilic compound having a nonionic and / or ionic hydrophilic group at an equivalent ratio of isocyanate group / hydroxyl group in the range of 1.05 to 1000. More preferably, the equivalent ratio is in the range of 2 to 200, and even more preferably 4 to 100. When the equivalent ratio is 1.05 or more, the isocyanate group content in the hydrophilic polyisocyanate becomes a predetermined level or higher, so that the crosslinking points in the crosslinkable water-based coating composition increase, leading to an increase in the curing speed or an improvement in the strength of the coating such as a coating film, which is preferable. When the equivalent ratio is 1000 or less, hydrophilicity is expressed, which is preferable. Such a water-dispersible isocyanate compound is not particularly limited, and a commercially available product can be used. For example, WT30-100 manufactured by Asahi Kasei Corporation and WM44-L70G manufactured by Asahi Kasei Corporation are preferably used as they have the above-mentioned characteristics.

[0060] The water-dispersible isocyanate compound is not particularly limited as long as it is a compound having a hydrophilic group introduced therein by a conventionally known method. For example, a compound represented by the general formula R 1 O(R 2 O) n -H (where R 1represents an alkyl group having 1 to 30 carbon atoms or a group containing two or more aromatic rings, R 2 represents an alkylene group having 1 to 5 carbon atoms. n is an integer of 2 to 250) and a polyisocyanate compound, a reaction product between a vinyl polymer having a hydrophilic group and a hydroxyl group and a polyisocyanate compound, and a reaction product between an emulsifier obtained by reacting an alkoxypolyalkylene glycol and a dialkanolamine and a polyisocyanate compound. Among these, the reaction product between the compound (m) and a polyisocyanate compound and the reaction product between a vinyl polymer having a hydrophilic group and a hydroxyl group and a polyisocyanate compound are particularly preferred because they have excellent water dispersibility.

[0061] Examples of the compound (m) include alkoxy polyalkylene glycols such as polymethylene glycol monomethyl ether, polyethylene glycol monomethyl ether, polyethylene glycol monoethyl ether, polyethylene glycol monopropyl ether, polyethylene glycol monolauryl ether, polyoxyethylene-oxypropylene (random and / or block) glycol monomethyl ether, polyoxyethylene-oxytetramethylene (random and / or block) glycol polybutylene glycol monomethyl ether, and nonionic surfactants having a group containing two or more aromatic rings such as (mono- to penta)styrenated phenyl group, mono (or di, tri)styryl-methyl-phenyl group, tribenzylphenyl group, and β-naphthyl group. Among them, polyethylene glycol monomethyl ether and nonionic surfactants having (mono- to penta)styrenated phenyl group are preferred in terms of self-emulsifying ability and pot life. As these compounds (m), those having a molecular weight preferably in the range of 100 to 10,000, more preferably 300 to 5,000, can be suitably used.

[0062] Examples of the hydrophilic group of the vinyl polymer having a hydrophilic group and a hydroxyl group include various known anionic groups, cationic groups, and nonionic groups, and the nonionic group is preferable. The nonionic group significantly extends the pot life of the coating composition, and the particle size of the polyisocyanate oil droplets becomes small, so that the water resistance of the coating film formed tends to be further improved. Specific examples of vinyl polymers having a hydrophilic group and a hydroxyl group include acrylic polymers, fluoroolefin polymers, vinyl ester polymers, aromatic vinyl polymers, polyolefin polymers, etc. Among these, acrylic polymers are preferred from the viewpoint of the weather resistance of the coating film formed. The polymerization method for obtaining an acrylic polymer suitable as a vinyl polymer having a hydrophilic group and a hydroxyl group is not particularly limited, and examples thereof include suspension polymerization, emulsion polymerization, and solution polymerization.Preferably, the acrylic polymer is obtained by solution polymerization of an ethylenically unsaturated monomer (i) having a hydrophilic group and an ethylenically unsaturated monomer (ii) having a hydroxyl group, and other ethylenically unsaturated monomers (iii) copolymerizable with these may also be used as necessary.

[0063] Examples of the ethylenically unsaturated monomer (i) having a hydrophilic group include alkoxy polyalkylene glycol (meth)acrylates such as methoxy polyethylene glycol (meth)acrylate, ethoxy polyethylene glycol (meth)acrylate, butoxy polyethylene glycol (meth)acrylate, polyalkylene glycol di(meth)acrylate, (meth)acrylamide monomers, anionic vinyl monomers, etc. Also, ethylenically unsaturated monomers having both a hydrophilic group and a hydroxyl group in the molecule, such as polyalkylene glycol (meth)acrylates, can be used. These may be used alone or in combination of two or more. Examples of other ethylenically unsaturated monomers (iii) copolymerizable therewith include (meth)acrylic acid esters, aromatic vinyl compounds, vinyl cyanides, carbonyl group-containing vinyl monomers, olefins, dienes, haloolefins, vinyl ethers, allyl esters, etc. These may be used alone or in combination of two or more. The vinyl polymer containing a hydrophilic group and a hydroxyl group preferably has a weight average molecular weight (polystyrene equivalent GPC method) in the range of 2,000 to 100,000, more preferably 3,000 to 50,000.

[0064] The content of the isocyanate compound (M) in the coating composition (J) relative to the adhesive emulsion particles (F) polymerized from a monomer containing a hydroxyl group-containing vinyl monomer is preferably such that the ratio of the number of moles of hydroxyl groups contained in the adhesive emulsion particles (F) to the number of moles of isocyanate groups contained in the isocyanate compound (C) (X=number of moles of isocyanate groups / number of moles of hydroxyl groups) is 0.02 or more. From the viewpoint of adhesion between the coating film formed and the substrate, X is more preferably 0.1 or more, and from the viewpoint of the abrasion resistance of the coating film, X is even more preferably 0.15 or more. From the viewpoint of the stability of the coating composition (resistance to gelation and high viscosity), X is preferably 10 or less, and from the viewpoint of the low water contact angle and high transparency (low haze) of the coating film formed, X is more preferably 5 or less. The ratio (X) may be 0.02 or more and 10 or less, 0.02 or more and 5 or less, 0.1 or more and 10 or less, 0.1 or more and 5 or less, 0.15 or more and 10 or less, or 0.15 or more and 5 or less.

[0065] In one embodiment, the mass ratio of the isocyanate compound to the adhesive emulsion particles (F) and the inorganic oxide (G) (mass of the isocyanate compound / total mass of the adhesive emulsion particles (F) and the inorganic oxide (G)) is preferably 0.001 or more, more preferably 0.01 or more, and even more preferably 0.05 or more, from the viewpoint of adhesion. Moreover, from the viewpoint of transparency, this mass ratio is preferably 1.0 or less, more preferably 0.7 or less, and even more preferably 0.5 or less.

[0066] The viscosity of the isocyanate compound (M) is preferably 1 to 50,000 mPa·s (20°C), more preferably 1 to 20,000 mPa·s (20°C), and even more preferably 10 to 10,000 mPa·s (20°C). The viscosity of the isocyanate compound (C) may be 10 to 50,000 mPa·s (20°C), 10 to 20,000 mPa·s (20°C), or 10 to 10,000 mPa·s (20°C). The viscosity of the polyisocyanate compound (M) is preferably 50,000 mPa·s or less, since it is easy to disperse in water. The viscosity here can be measured with a general E-type viscometer. In one embodiment, the viscosity is measured using an E-type viscometer (RE-80U manufactured by Toki Sangyo Co., Ltd.) at a rotation speed of 2.5 rpm and 25°C. Such an isocyanate compound is not particularly limited, and a commercially available product can also be used. For example, WT30-100 manufactured by Asahi Kasei Corporation and WM44-L70G manufactured by Asahi Kasei Corporation are preferably used as they have the above-mentioned characteristics.

[0067] The various isocyanate compounds described above may be in the form of a urethane compound by reacting a part or the whole of the compound with a polyol.

[0068] <Adhesive layer manufacturing method> The method for producing the adhesive layer in this embodiment is not particularly limited, but for example, the adhesive layer can be obtained by applying a coating composition (J) obtained by dispersing and dissolving the adhesive emulsion particles (F), the inorganic oxide (G), the light-shielding agent, and other appropriate components in a solvent to the substrate, and forming a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, or the like. The adhesive emulsion particles (F) and the inorganic oxide (G) may be used in advance as a composite. Furthermore, the coating method includes, but is not limited to, spraying, flow coating, brush coating, dip coating, spin coating, screen printing, casting, gravure printing, and flexographic printing. The applied coating composition (J) can be formed into a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, or the like, preferably at room temperature to 250°C, more preferably at 40°C to 150°C. Furthermore, this coating can be applied not only to already molded substrates, but also to flat plates before molding, such as pre-coated metals including rust-resistant steel plates.

[0069] [Paint composition (J)] The coating composition (J) in this embodiment is a coating composition comprising a mixture of adhesive emulsion particles (F) and inorganic oxide (G) and / or a complex of the inorganic oxide (G) and the adhesive emulsion particles (F), and a light-shielding agent (S1), and it is preferable that the average particle diameter of the mixture and / or complex is 2 nm or more and 2000 nm or less, and the mass ratio of the inorganic oxide (G) to the adhesive emulsion particles (F) is 1:0.1 to 1:10. The average particle size can be measured by the method described in the Examples below. In addition, when the coating composition (J) contains a mixture of adhesive emulsion particles (F) and inorganic oxide (G), when both the average particle size of the adhesive emulsion particles (F) and the average primary particle size of the inorganic oxide (G) are 2 nm or more and 2000 nm or less, the average particle size of the mixture is deemed to be 2 nm or more and 2000 nm or less.

[0070] Coating composition (J) may contain a solvent, and as the solvent, any solvent that can be used for coating composition (I) described below may be appropriately used.

[0071] Details of each component contained in the coating composition (J) that are not mentioned below are the same as those described above for each component contained in the adhesive layer.

[0072] [Complex of adhesive emulsion particles (F) and inorganic oxide (G)] The adhesive emulsion particles (F) and the inorganic oxide (G) contained in the coating composition (J) may be mixed with each other, or may be a composite of the adhesive emulsion particles (F) and the inorganic oxide (G) formed in advance. The composite of the adhesive emulsion particles (F) and the inorganic oxide (G) can be obtained, for example, by polymerizing the vinyl monomer of the adhesive emulsion particles (F) in the presence of the inorganic oxide (G). From the viewpoint of interaction with the inorganic oxide (G), the vinyl monomer preferably contains the vinyl monomer having the above-mentioned secondary and / or tertiary amide group. A complex is preferably formed by hydrogen bonding between the hydroxyl group of the inorganic oxide (G) and the secondary and / or tertiary amide group.

[0073] In this embodiment, the average particle size of the mixture of adhesive emulsion particles (F) and inorganic oxide (G) and / or the composite of adhesive emulsion particles (F) and inorganic oxide (G) is preferably 20 nm or more from the viewpoint of improving the storage stability of the raw material composition of the adhesive layer, and is preferably 2000 nm or less from the viewpoint of transparency, more preferably 1000 nm or less, and even more preferably 500 nm or less. The average particle size can be measured by the method described in the Examples below, and can be adjusted to the above-mentioned range, for example, by the mass ratio or solids concentration of the adhesive emulsion particles (F) and the inorganic oxide (G).

[0074] The mass ratio of the adhesive emulsion particles (F) to the inorganic oxide (G) in the coating composition (J) is preferably 1:0.1 to 1:10, more preferably 1:0.3 to 1:5, and even more preferably 1:0.5 to 1:2.

[0075] The inorganic oxide (G) in the coating composition (J) is preferably silica having a spherical and / or connected structure, and the above-mentioned silica having a spherical and / or connected structure contained in the adhesive layer can be appropriately used. The spherical silica is not particularly limited, and a commercially available product can be used, for example, Snowtex C or Snowtex OS manufactured by Nissan Chemical Industries, Ltd. is preferably used. The silica having a connected structure is also not particularly limited, and a commercially available product can be used, for example, Snowtex PSSO manufactured by Nissan Chemical Industries, Ltd. is preferably used.

[0076] The aspect ratio (major axis / minor axis) of the inorganic oxide (G) in the coating composition (J) is preferably 3 to 25. The aspect ratio can be measured based on the method described in the Examples below. The inorganic oxide (G) having the aspect ratio as described above is not particularly limited, and a commercially available product can be used. For example, Snowtex PSSO manufactured by Nissan Chemical Industries, Ltd. is preferably used.

[0077] The coating composition (J) contains a light-shielding agent (S1), and the above-mentioned light-shielding agent (S1) contained in the adhesive layer can be appropriately adopted. In this embodiment, the light-shielding agent (S1) preferably contains an ultraviolet absorbing agent, and the above-mentioned light-shielding agent (S1) contained in the adhesive layer can be appropriately adopted.

[0078] The coating composition (J) preferably further contains a hindered amine light stabilizer, and the above-mentioned materials can be appropriately used as the hindered amine light stabilizer contained in the adhesive layer.

[0079] In the coating composition (J), the adhesive emulsion particle (F) preferably has a functional group (e) having a secondary amide group and / or a tertiary amide group. The functional group (e) having a secondary amide group and / or a tertiary amide group is not particularly limited, but for example, the functional group (e) having a secondary amide group and / or a tertiary amide group in the coating composition (I) described later can be appropriately used.

[0080] In the coating composition (J), the adhesive emulsion particles (F) preferably have a functional group having a hydroxyl group. The functional group having a hydroxyl group is not particularly limited, but for example, the functional group having a hydroxyl group exemplified in the coating composition (I) described later can be appropriately adopted.

[0081] [Isocyanate compounds] From the viewpoint of improving the adhesion between the adhesive layer and the substrate, the coating composition (J) preferably contains an isocyanate compound and / or a urethane compound, more preferably the isocyanate compound is a water-dispersible isocyanate compound, and even more preferably the water-dispersible isocyanate compound is a blocked isocyanate. The isocyanate compound and / or urethane compound are not particularly limited, but for example, the isocyanate compound and / or urethane compound described above in the adhesive layer can be appropriately adopted. In addition, the water-dispersible isocyanate compound or blocked isocyanate can be appropriately adopted as the water-dispersible isocyanate compound and blocked isocyanate described above in the adhesive layer.

[0082] [Properties of coating composition (J)] From the viewpoint of coatability, the solid content of the coating composition (J) is preferably 0.01 to 60 mass%, more preferably 1 to 40 mass%, and from the viewpoint of coatability, the viscosity of the coating composition (J) at 20°C is preferably 0.1 to 100,000 mPa s, more preferably 1 to 10,000 mPa s.

[0083] [Hard coat layer] The hard coat layer in this embodiment (hereinafter also referred to as "layer (C)") is disposed on the substrate with the adhesive layer and contains a matrix component (B) containing an inorganic oxide (D), and contributes to the durability of the laminate. In this specification, the hard coat layer is defined as a layer having a Martens hardness HM of 100 N / mm 2 The layer described above is particularly referred to as a "hard coat layer."

[0084] In the present embodiment, from the viewpoint of abrasion resistance, the hard coat layer further contains polymer nanoparticles (A) dispersed in the matrix component (B), and the Martens hardness HM of the polymer nanoparticles (A) is A and the Martens hardness HM of the matrix component (B). B But, HM B / HM A >1, and the Martens hardness HM of the hard coat layer is 100 N / mm 2 More preferably, it is equal to or greater than this. The above Martens hardness HM A and Martens hardness HM B Even when it is difficult to confirm the magnitude relationship between the Martens hardnesses, the magnitude relationship between the Martens hardnesses can be estimated by comparing the adhesive forces of the polymer nanoparticles (A) and the matrix component (B) described below. Since the lower the adhesive force, the higher the elasticity, the lower the adhesive force, the less the coating film is likely to deform, and the higher the hardness. Specifically, the above-mentioned preferred layer (C) can also be specified as follows. That is, the above-mentioned preferred layer (C) contains polymer nanoparticles (A) and a matrix component (B), and has an adhesive force F of the polymer nanoparticles (A) measured in the adhesion force mode of a scanning probe microscope (SPM), A and the adhesive force F of the matrix component (B). B But, F A / F B >1, and the Martens hardness HM of the hard coat layer is 100 N / mm 2 That's all.

[0085] In the layer (C) of this embodiment, the polymer nanoparticles (A) are preferably dispersed in the matrix component (B). In this embodiment, "dispersion" means that the polymer nanoparticles (A) are dispersed in the matrix component (B) as a dispersed phase, and the matrix component (B) is continuous, and the polymer nanoparticles (A) are distributed in the matrix component (B) uniformly or while forming a structure. The dispersion can be confirmed by cross-sectional SEM observation of the hard coat layer. In the hard coat layer of this embodiment, the polymer nanoparticles (A) are dispersed in the matrix component (B), so that the layer tends to have high abrasion resistance.

[0086] [Martens hardness] The Martens hardness in this embodiment is a hardness in accordance with ISO14577-1, and is a value calculated from the indentation depth at 2mN under the measurement conditions (Vickers square pyramid diamond indenter, load increase condition 2mN / 20sec, load decrease condition 2mN / 20sec). The Martens hardness in this embodiment can be measured using, for example, a microhardness tester Fischerscope (HM2000S manufactured by Fisher Instruments), a super-microindentation hardness tester (ENT-NEXUS manufactured by Elionix Co., Ltd.), a nanoindenter (iNano, G200 manufactured by Toyo Corporation), and a nanoindentation system (TI980 manufactured by Bruker). The shallower the indentation depth, the higher the Martens hardness, and the deeper the indentation depth, the lower the Martens hardness.

[0087] [Adhesion force] The adhesive force in this embodiment can be measured by a scanning probe microscope (SPM), and since the lower the adhesive force, the higher the elasticity, the lower the adhesive force, the less likely the coating film is to deform and the higher the hardness. The method for measuring the adhesive force is not limited to the following, but for example, the measurement can be performed using SPM-970 and SPM-9700HT manufactured by Shimadzu Corporation, Dimension ICON manufactured by Bruker AXS, AFM5000II manufactured by Hitachi High-Tech Science Corporation, etc.

[0088] [Other hardness] The magnitude relationship of the Martens hardness and adhesive force in the above-mentioned embodiment can also be estimated by checking the magnitude relationship of the measured values ​​using other hardness as an index. The other hardness is not particularly limited as long as it is an index indicating the difficulty of deformation of the material when force is applied to the material, and can include Vickers hardness and indentation hardness measured by an indentation hardness tester represented by a microhardness tester or a nanoindentation measuring instrument, and an index expressed by a logarithmic decrement measured by a pendulum-type viscoelasticity represented by a rigid pendulum-type physical property tester. In addition, it can also include indexes expressed by phase, friction force, viscoelasticity, adsorption force, hardness and elastic modulus measured by a scanning probe microscope (SPM). If it is confirmed that the hardness of the matrix component (B) is higher than the hardness of the polymer nanoparticles (A) in these indices, it is estimated that the matrix component (B) is harder than the polymer nanoparticles (A) in terms of Martens hardness and adhesive force.

[0089] [Martens hardness HM of polymer nanoparticles (A) A and the Martens hardness HM of the matrix component (B) B ] Martens hardness HM of the polymer nanoparticles (A) in this embodiment A and the Martens hardness HM of the matrix component (B) B It is preferable that the relationship of the following formula (1) is satisfied. HM B / HM A >1 formula (1) Formula (1) expresses the presence of soft polymer nanoparticles (A) in a hard matrix component (B), and by having a three-dimensional gradient in hardness in this way, layer (C) tends to be able to impart abrasion resistance that was not possible with conventional coating films. The reasons for this, although not intended to be limited to the following, are presumed to be that the soft nanoparticles absorb impact and the hard matrix component suppresses deformation. HM A From the viewpoint of shock absorption, the range is 50N / mm 2 More than 100N / mm is preferable. 2 More preferably, from the viewpoint of film forming property, 2000N / mm 2Less than 800N / mm is preferable. 2 Less than 350N / mm is more preferable. 2 More preferred are: HM B From the viewpoint of shock absorption, the range is 100N / mm 2 More than 150N / mm is preferable. 2 More preferably, from the viewpoint of film forming property, 4000N / mm 2 Less than 2000N / mm is preferable. 2 The following is more preferred: The layer (C) can be obtained as a cured product obtained by curing the coating composition (I) described later by hydrolysis and condensation or the like. The composition of the polymer nanoparticles (A) usually does not change during the curing process. Therefore, the Martens hardness HM of the polymer nanoparticles (A) in the coating composition (I) measured by the method described in the examples described later can be calculated by the following formula: A The value of is the Martens hardness HM of the polymer nanoparticles (A) in the layer (C). A The Martens hardness HM in layer (C) is in good agreement with A The value of can be determined. The matrix component (B) corresponds to a cured product obtained by curing the matrix raw material component (B') described later by hydrolysis and condensation or the like. Therefore, the Martens hardness HM of the matrix raw material component (B') measured by the method described in the examples described later B' The value of is the Martens hardness HM of the corresponding matrix component (B). B The Martens hardness HM B The value of can be determined. The above HM A and H.M. B The values ​​of can be adjusted to satisfy the above-mentioned magnitude relationship depending on the structures and composition ratios of the constituent components of the polymer nanoparticles (A) and the matrix raw material component (B') described later, but are not limited to this method.

[0090] [Adhesion force of polymer nanoparticles (A) F A and the adhesive force F of the matrix component (B) B ] The adhesive force F of the polymer nanoparticles (A) in this embodiment A and the adhesive force F of the matrix component (B) B It is preferable that the relationship of the following formula (2) is satisfied. F A / F B >1 Formula (2) As with formula (1) above, formula (2) also expresses the presence of soft polymer nanoparticles (A) in a hard matrix component (B), and the layer (C) tends to be able to impart abrasion resistance not seen in conventional coating films due to the three-dimensional gradient in hardness. The reasons for this, although not limited to the following, are presumed to be that the soft nanoparticles absorb impact and the hard matrix component suppresses deformation. As described above, the adhesive force F of the polymer nanoparticles (A) A and the adhesive force F of the matrix component (B) B is correlated with the hardness of each component, and can be adjusted to satisfy the above-mentioned magnitude relationship by adjusting the structures and composition ratios of the constituent components of the polymer nanoparticles (A) and the matrix raw material component (B') described later, but is not limited to this method.

[0091] [Martens hardness HM of layer (C)] The Martens hardness HM of layer (C) is 100N / mm 2 The higher the hardness, the less deformation there is upon impact and the less damage accompanied by destruction. The Martens hardness HM of the layer (C) is preferably 100 N / mm 2 More preferably, it is 150N / mm 2 More preferably, it is 200N / mm 2 From the viewpoint of bending resistance, it is preferably 4000N / mm 2 Less than or equal to 2000N / mm 2 Less than 1500N / mm 2The method for adjusting the Martens hardness HM of the layer (C) within the above range includes, but is not limited to, for example, dispersing and dissolving a composition obtained by mixing polymer nanoparticles (A) and a matrix raw material component (B') described later in a solvent, which satisfies a predetermined relationship represented by the formula (3) described later, on a substrate, and forming a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, etc. In particular, when the content of the matrix component (B) relative to the total amount of the polymer nanoparticles (A) and the matrix component (B) is increased, the Martens hardness HM of the layer (C) tends to increase, and when the content of the matrix component (B) is reduced, the Martens hardness HM of the layer (C) tends to decrease.

[0092] [Haze change in Taber abrasion test] The Taber abrasion test in this embodiment is based on the method described in ASTM D1044, and is performed under the conditions of an abrasion wheel CS-10F and a load of 500 g. The smaller the haze change, the more excellent the abrasion resistance of the material. If the haze change at 500 revolutions relative to the haze before the test, i.e., the difference between the haze at 500 revolutions and the haze before the Taber abrasion test, is 10 or less, it complies with the ECE R43 rear quarter glass standard, and if it is 4 or less, it complies with the ANSI / SAE Z.26.1 standard and can be suitably used as an automobile window material. In addition, if the haze change at 1000 revolutions, that is, the difference between the haze at 1000 revolutions and the haze before the Taber abrasion test, is 10 or less, it complies with the standards for automobile windows and can be suitably used as an automobile window material, and if it is 2 or less, it complies with the standards of ANSI / SAE Z.26.1, ECE R43, and JIS R3211 / R3212 and can be suitably used for all automobile window materials. It is preferable that the haze change at 1000 revolutions is 10 or less, more preferably 6 or less, and even more preferably 2 or less. The method for adjusting the haze change within the above range is not limited to the following, but for example, a coating composition in which a composition containing a mixture of polymer nanoparticles (A) and a matrix raw material component (B') described later is dispersed and dissolved in a solvent, which satisfies a predetermined relationship represented by formula (3) described later, is applied to a substrate, and a coating film is formed by heat treatment, ultraviolet irradiation, infrared irradiation, etc.

[0093] [Elastic recovery rate of layer (C) η IT ] Elastic recovery rate η of layer (C) IT is the total mechanical work of the cavity W total and the elastic return deformation work of the dent W elast This is the ratio of "W elast / W total Ratio of η IT " is a parameter described as "elastic recovery rate η IT The higher the elastic recovery rate η, the more the coating film can return to its original state when deformed, and the higher its self-repairing ability against deformation. ITis preferably 0.50 or more under the measurement conditions (Vickers square pyramid diamond indenter, load increase condition 2 mN / 20 sec, load decrease condition 2 mN / 20 sec), and within this range, the larger the value, the more preferable. More specifically, the elastic recovery rate η IT is more preferably 0.55 or more, even more preferably 0.60 or more, and even more preferably 0.65 or more. The measurement of the elastic recovery rate of the coating film in this embodiment is not limited to the following, but can be measured, for example, by performing an indentation test on the surface of the hard coat layer using a microhardness tester Fischerscope (HM2000S manufactured by Fisher Instruments), an ultra-microindentation hardness tester (ENT-NEXUS manufactured by Elionix Co., Ltd.), a nanoindenter (iNano, G200 manufactured by Toyo Corporation), a nanoindentation system (TI980 manufactured by Bruker), or the like. Elastic recovery rate η IT Methods for adjusting within the above range include, but are not limited to, a coating composition prepared by dispersing and dissolving a composition of polymer nanoparticles (A) and a matrix raw material component (B') described later, which satisfies a specific relationship represented by formula (3) described later, in a solvent, and coating the resulting coating composition on a substrate and forming a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, or the like.

[0094] [Thickness of layer (C)] In this embodiment, it is preferable to adjust the film thickness appropriately from the viewpoint of further expressing the abrasion resistance of the hard coat layer and from the viewpoint of sufficiently ensuring the conformability to the deformation of the substrate. Specifically, the film thickness of the layer (C) is preferably 1.0 μm or more from the viewpoint of abrasion resistance, more preferably 3.0 μm or more. Furthermore, the film thickness of the layer (C) is preferably 100.0 μm or less from the viewpoint of the conformability to the substrate, more preferably 50.0 μm or less, and even more preferably 20.0 μm or less.

[0095] [Polymer nanoparticles (A)] By using the polymer nanoparticles (A) in this embodiment, it is possible to impart impact absorption properties to the hard coat layer, and the amount of haze change in the hard coat layer in the Taber abrasion test tends to be small. The shape of the polymer nanoparticles (A) is not particularly limited as long as the particle size is on the order of nm (less than 1 μm). The Martens hardness HM of the polymer nanoparticles (A) is A Regarding the above, it can be controlled within the above-mentioned range depending on the structure and composition ratio of the components of the polymer nanoparticles (A), but is not particularly limited to this method.

[0096] [Average particle size of polymer nanoparticles (A)] The average particle size of the polymer nanoparticles (A) in this embodiment is not particularly limited as long as it is on the order of nm (less than 1 μm), and is determined from the size of particles observed by cross-sectional SEM or dynamic light scattering. The average particle size of the polymer nanoparticles (A) is preferably 10 nm or more from the viewpoint of optical properties, more preferably 15 nm or more, more preferably 20 nm or more, and is preferably 400 nm or less from the viewpoint of transparency, more preferably 200 nm or less, and even more preferably 100 nm or less. The method for measuring the average particle size of the polymer nanoparticles (A) is not limited to the following, but can be, for example, measured by measuring the cumulant particle size using a dynamic light scattering particle size distribution analyzer (product number: ELSZ-1000) manufactured by Otsuka Electronics Co., Ltd. using a water dispersion of the polymer nanoparticles (A).

[0097] [Volume fraction of polymer nanoparticles (A) in layer (C)] In this embodiment, the volume fraction of the polymer nanoparticles (A) in the layer (C) is preferably 2% or more, more preferably 3% or more, and even more preferably 5% or more from the viewpoint of film-forming property, and is preferably 80% or less, more preferably 70% or less, and even more preferably 45% or less from the viewpoint of transparency. The volume fraction of the polymer nanoparticles (A) in the layer (C) can be calculated, for example, from the ratio of the polymer nanoparticles (A) in the entire coating film in the cross-sectional SEM image of the layer (C) or the component ratio of the polymer nanoparticles (A) in the components constituting the layer (C).

[0098] [Components of polymer nanoparticles (A)] [Hydrolyzable silicon compounds (a)] The polymer nanoparticles (A) in this embodiment preferably contain a hydrolyzable silicon compound (a). The hydrolyzable silicon compound (a) is not particularly limited as long as it is a silicon compound having hydrolysis properties, its hydrolysis product, or its condensation product.

[0099] From the viewpoint of improving abrasion resistance and weather resistance, the hydrolyzable silicon compound (a) is preferably a compound containing an atomic group represented by the following formula (a-1), or a hydrolysis product or condensation product thereof. -R 1 n1 Six 1 3-n1 (a-1)

[0100] In formula (a-1), R 1 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group, an alkynyl group, or an aryl group; R 1 may have a substituent containing a halogen, a hydroxy group, a mercapto group, an amino group, a (meth)acryloyl group, or an epoxy group, and X 1 represents a hydrolyzable group, and n1 represents an integer of 0 to 2. The hydrolyzable group is not particularly limited as long as it is a group that generates a hydroxyl group upon hydrolysis, and examples of such groups include halogen, an alkoxy group, an acyloxy group, an amino group, a phenoxy group, and an oxime group.

[0101] Specific examples of the compound containing the atomic group represented by formula (a-1) include, but are not limited to, trimethoxysilane, triethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, isobutyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, dec ... Ethoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethoxysilane, diethoxysilane, methyldimethoxysilane, methyldiethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethoxydiphenylsilane, diethoxydiphenylsilane, bis(trimethoxysilyl)methane, bis(triethoxysilyl)methane, bis(triphenoxysilyl)ethane, 1,1-bis(triethoxysilyl) 1,2-bis(triethoxysilyl)ethane, 1,1-bis(triethoxysilyl)propane, 1,2-bis(triethoxysilyl)propane, 1,3-bis(triethoxysilyl)propane, 1,4-bis(triethoxysilyl)butane, 1,5-bis(triethoxysilyl)pentane, 1,1-bis(trimethoxysilyl)ethane, 1,2-bis(trimethoxysilyl)ethane, 1,1-bis(trimethoxysilyl)propane, 1,2-bis(trimethoxysilyl)propane, 1,3-bis(trimeth 1,4-bis(trimethoxysilyl)propane, 1,4-bis(trimethoxysilyl)butane, 1,5-bis(trimethoxysilyl)pentane, 1,3-bis(triphenoxysilyl)propane, 1,4-bis(trimethoxysilyl)benzene, 1,4-bis(triethoxysilyl)benzene, 1,6-bis(trimethoxysilyl)hexane, 1,6-bis(triethoxysilyl)hexane, 1,7-bis(trimethoxysilyl)heptane, 1,7-bis(triethoxysilyl)heptane, 1,8-bis(trimethoxysilyl)octane, 1,8-Bis(triethoxysilyl)octane, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, trifluoropropyltrimethoxysilane, trifluoropropyltriethoxysilane, 3-hydroxypropyltrimethoxysilane, 3-hydroxypropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3 -Methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane Silane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane, 3-trimethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-triethoxysilyl-N-(1,3-Dimethyl-butylidene)propylamine, triacetoxysilane, tris(trichloroacetoxy)silane, tris(trifluoroacetoxy)silane, tris-(trimethoxysilylpropyl)isocyanurate, tris-(triethoxysilylpropyl)isocyanurate, methyltriacetoxysilane, methyltris(trichloroacetoxy)silane, trichlorosilane, tribromosilane, methyltrifluorosilane, tris(methylethylketoxime)silane, phenyltris(methylethylketoxime)silane, bis(methylethylketoxime)silane, methylbis(methylethylketoxime)silane, hexamethyldisilane, hexamethylcyclotrisilazane, bi Bis(dimethylamino)dimethylsilane, bis(diethylamino)dimethylsilane, bis(dimethylamino)methylsilane, bis(diethylamino)methylsilane, 2-[(triethoxysilyl)propyl]dibenzylresorcinol, 2-[(trimethoxysilyl)propyl]dibenzylresorcinol, 2,2,6,6-tetramethyl-4-[3-(triethoxysilyl)propoxy]piperidine, 2,2,6,6-tetramethyl-4-[3-(trimethoxysilyl)propoxy]piperidine, 2-hydroxy-4-[3-(triethoxysilyl)propoxy]benzophenone, 2-hydroxy-4-[3-(trimethoxysilyl)propoxy]benzophenone, and the like.

[0102] From the viewpoint of imparting high hardness to the hard coat layer and further improving abrasion resistance, the hydrolyzable silicon compound (a) preferably contains a compound represented by the following formula (a-2), its hydrolysis product, and its condensation product. Six 2 4(a-2) In formula (a-2), X 2 represents a hydrolyzable group. The hydrolyzable group is not particularly limited as long as it is a group that generates a hydroxyl group upon hydrolysis, and examples thereof include halogen, an alkoxy group, an acyloxy group, an amino group, a phenoxy group, and an oxime group.

[0103] Specific examples of the compound represented by formula (a-2) include, but are not limited to, tetramethoxysilane, tetraethoxysilane, tetra(n-propoxy)silane, tetra(i-propoxy)silane, tetra(n-butoxy)silane, tetra(i-butoxy)silane, tetra-sec-butoxysilane, tetra-tert-butoxysilane, tetraacetoxysilane, tetra(trichloroacetoxy)silane, tetra(trifluoroacetoxy)silane, tetrachlorosilane, tetrabromosilane, tetrafluorosilane, tetra(methylethylketoxime)silane, tetramethoxysilane, or tetraethoxysilane. Examples of the hydrolyzed condensates of orchid include those sold under the trade names "M Silicate 51", "Silicate 35", "Silicate 45", "Silicate 40" and "FR-3" by Tama Chemical Co., Ltd.; those sold under the trade names "MS51", "MS56", "MS57" and "MS56S" by Mitsubishi Chemical; and those sold under the trade names "Methyl Silicate 51", "Methyl Silicate 53A", "Ethyl Silicate 40", "Ethyl Silicate 48", "EMS-485", "N-103X", "PX", "PS-169", "PS-162R", "PC-291", "PC-301", "PC-302R", "PC-309" and "EMSi48" by Colcoat Co., Ltd.

[0104] As described above, in this embodiment, it is preferable that the hydrolyzable silicon compound (a) contains at least one selected from the compound containing the atomic group represented by the above formula (a-1), its hydrolysis product and condensation product, and the compound represented by the above formula (a-2), its hydrolysis product and condensation product.

[0105] [Content of hydrolyzable silicon compound (a) in polymer nanoparticles (A)] The content of hydrolyzable silicon compound (a) in this embodiment refers to the solid weight ratio of hydrolyzable silicon compound (a) contained in polymer nanoparticle (A), and the higher the content, the better from the viewpoint of improving wear resistance, weather resistance, and heat resistance, and the content is preferably 50 mass% or more, more preferably 60 mass% or more. The content of hydrolyzable silicon compound (a) in polymer nanoparticle (A) is not limited to the following, but can be measured by, for example, IR analysis, NMR analysis, elemental analysis, etc. of polymer nanoparticle (A).

[0106] [Matrix component (B)] By using the matrix component (B) in this embodiment, it is possible to impart impact absorbing properties to the hard coat layer, and to reduce the amount of haze change in the hard coat layer in the Taber abrasion test. B The amount of the matrix can be controlled within the above-mentioned range by adjusting the structure and composition ratio of the components of the matrix raw material component (B') described later, but is not limited to this method.

[0107] [Components of matrix component (B)] [Hydrolyzable silicon compounds (b)] The matrix component (B) in this embodiment is not particularly limited as long as it is a component in which the polymer nanoparticles (A) can be dispersed. In this embodiment, from the viewpoint of high toughness, it is preferable that the matrix component (B) contains a hydrolyzable silicon compound (b). In this specification, "the matrix component (B) contains a hydrolyzable silicon compound (b)" means that the matrix component (B) contains a polymer having a constitutional unit derived from the hydrolyzable silicon compound (b). The hydrolyzable silicon compound (b) is not particularly limited as long as it is a silicon compound having hydrolysis properties, its hydrolysis product, and its condensation product. The matrix component (B) may contain various components other than the polymer nanoparticles (A) in addition to the above-mentioned polymers. Among them, examples of other polymers that may be contained in addition to the above-mentioned polymers include water-soluble resins such as polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, and polyacrylic acid; acrylic resins such as PMMA, PAN, and polyacrylamide; polymers such as polystyrene, polyurethane, polyamide, polyimide, polyvinylidene chloride, polyester, polycarbonate, polyether, polyethylene, polysulfone, polypropylene, polybutadiene, PTFE, PVDF, and EVA; and copolymers thereof.

[0108] From the viewpoint of further improving the abrasion resistance and weather resistance, the hydrolyzable silicon compound (b) preferably contains one or more compounds selected from the group consisting of compounds containing an atomic group represented by the following formula (b-1), their hydrolysis products and condensation products, and compounds represented by the following formula (b-2), their hydrolysis products and condensation products. -R 2 n2 Six 3 3-n2 (b-1) In formula (b-1), R 2 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group, an alkynyl group, or an aryl group; R 2 may have a substituent containing a halogen, a hydroxy group, a mercapto group, an amino group, a (meth)acryloyl group, or an epoxy group, and X 3 represents a hydrolyzable group, and n2 represents an integer of 0 to 2. The hydrolyzable group is not particularly limited as long as it is a group that generates a hydroxyl group upon hydrolysis, and examples of such groups include a halogen atom, an alkoxy group, an acyloxy group, an amino group, a phenoxy group, and an oxime group. Six 4 4(b-2) In formula (b-2), X 4represents a hydrolyzable group. The hydrolyzable group is not particularly limited as long as it is a group that generates a hydroxyl group upon hydrolysis, and examples of such groups include halogen, an alkoxy group, an acyloxy group, an amino group, a phenoxy group, and an oxime group.

[0109] Specific examples of the compound containing the atomic group represented by general formula (b-1) include, but are not limited to, trimethoxysilane, triethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, isobutyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, decyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, octyltriethoxy ... Silane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethoxysilane, diethoxysilane, methyldimethoxysilane, methyldiethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethoxydiphenylsilane, diethoxydiphenylsilane, bis(trimethoxysilyl)methane, bis(triethoxysilyl)methane, bis(triphenoxysilyl)ethane, 1,1-bis(triethoxysilyl) Ethane, 1,2-bis(triethoxysilyl)ethane, 1,1-bis(triethoxysilyl)propane, 1,2-bis(triethoxysilyl)propane, 1,3-bis(triethoxysilyl)propane, 1,4-bis(triethoxysilyl)butane, 1,5-bis(triethoxysilyl)pentane, 1,1-bis(trimethoxysilyl)ethane, 1,2-bis(trimethoxysilyl)ethane, 1,1-bis(trimethoxysilyl)propane, 1,2-bis(trimethoxysilyl)propane, 1,3-bis(trimethoxysilyl)propane, 1,4-bis(trimethoxysilyl)propane, 1,4-bis(trimethoxysilyl)butane, 1,5-bis(trimethoxysilyl)pentane, 1,3-bis(triphenoxysilyl)propane, 1,4-bis(trimethoxysilyl)benzene, 1,4-bis(triethoxysilyl)benzene, 1,6-bis(trimethoxysilyl)hexane, 1,6-bis(triethoxysilyl)hexane, 1,7-bis(trimethoxysilyl)heptane, 1,7-bis(triethoxysilyl)heptane, 1,8-bis(trimethoxysilyl)octane, 1,8-Bis(triethoxysilyl)octane, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, trifluoropropyltrimethoxysilane, trifluoropropyltriethoxysilane, 3-hydroxypropyltrimethoxysilane, 3-hydroxypropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3 -Methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane Silane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane, 3-trimethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-triethoxysilyl-N-(1,3-Dimethyl-butylidene)propylamine, triacetoxysilane, tris(trichloroacetoxy)silane, tris(trifluoroacetoxy)silane, tris-(trimethoxysilylpropyl)isocyanurate, tris-(triethoxysilylpropyl)isocyanurate, methyltriacetoxysilane, methyltris(trichloroacetoxy)silane, trichlorosilane, tribromosilane, methyltrifluorosilane, tris(methylethylketoxime)silane, phenyltris(methylethylketoxime)silane, bis(methylethylketoxime)silane, methylbis(methylethylketoxime)silane, hexamethyldisilane, hexamethylcyclotrisilazane, bi Bis(dimethylamino)dimethylsilane, bis(diethylamino)dimethylsilane, bis(dimethylamino)methylsilane, bis(diethylamino)methylsilane, 2-[(triethoxysilyl)propyl]dibenzylresorcinol, 2-[(trimethoxysilyl)propyl]dibenzylresorcinol, 2,2,6,6-tetramethyl-4-[3-(triethoxysilyl)propoxy]piperidine, 2,2,6,6-tetramethyl-4-[3-(trimethoxysilyl)propoxy]piperidine, 2-hydroxy-4-[3-(triethoxysilyl)propoxy]benzophenone, 2-hydroxy-4-[3-(trimethoxysilyl)propoxy]benzophenone, and the like.

[0110] Specific examples of the compound represented by formula (b-2) include, but are not limited to, tetramethoxysilane, tetraethoxysilane, tetra(n-propoxy)silane, tetra(i-propoxy)silane, tetra(n-butoxy)silane, tetra(i-butoxy)silane, tetra-sec-butoxysilane, tetra-tert-butoxysilane, tetraacetoxysilane, tetra(trichloroacetoxy)silane, tetra(trifluoroacetoxy)silane, tetrachlorosilane, tetrabromosilane, tetrafluorosilane, tetra(methylethylketoxime)silane, tetramethoxysilane, or tetraethoxysilane. Examples of the hydrolyzed condensates of orchid include those sold under the trade names "M Silicate 51", "Silicate 35", "Silicate 45", "Silicate 40" and "FR-3" by Tama Chemical Co., Ltd.; those sold under the trade names "MS51", "MS56", "MS57" and "MS56S" by Mitsubishi Chemical; and those sold under the trade names "Methyl Silicate 51", "Methyl Silicate 53A", "Ethyl Silicate 40", "Ethyl Silicate 48", "EMS-485", "N-103X", "PX", "PS-169", "PS-162R", "PC-291", "PC-301", "PC-302R", "PC-309" and "EMSi48" by Colcoat Co., Ltd.

[0111] As described above, in this embodiment, it is preferable that the hydrolyzable silicon compound (b) contains at least one selected from the compound containing the atomic group represented by the above formula (b-1), its hydrolysis product and condensation product, and the compound represented by the above formula (b-2), its hydrolysis product and condensation product.

[0112] In this embodiment, the "hydrolyzable silicon compound (a) contained in the polymer nanoparticles (A)" may be the same as or different from the "hydrolyzable silicon compound (b) contained in the matrix component (B)". Even if the two are the same type, they are distinguished by calling the one contained in the polymer nanoparticles (A) the hydrolyzable silicon compound (a) and the one contained in the matrix component (B) the hydrolyzable silicon compound (b).

[0113] [Inorganic oxides (D)] The matrix component (B) in this embodiment contains an inorganic oxide (D). By containing the inorganic oxide (D), the hardness of the matrix component (B) is improved, and the abrasion resistance is improved. In addition, the hydrophilicity of the hydroxyl groups on the particle surface of the inorganic oxide (D) tends to improve the stain resistance of the coating film.

[0114] Specific examples of the inorganic oxide (D) in this embodiment include, but are not limited to, oxides of silicon, aluminum, titanium, zirconium, zinc, cerium, tin, indium, gallium, germanium, antimony, molybdenum, niobium, magnesium, bismuth, cobalt, copper, etc. These may be used alone or as a mixture regardless of the shape. From the viewpoint of the interaction with the hydrolyzable silicon compound (b) described above, it is preferable that the inorganic oxide (D) further contains silica particles represented by dry silica and colloidal silica, and from the viewpoint of dispersibility, it is preferable that the inorganic oxide (D) further contains colloidal silica as the form of silica particles. When the inorganic oxide (D) contains colloidal silica, it is preferable that it is in the form of an aqueous dispersion, and either acidic or basic can be used. In this embodiment, the inorganic oxide (D) preferably contains at least one inorganic component selected from the group consisting of Ce, Nb, Al, Zn, Ti, Zr, Sb, Mg, Sn, Bi, Co and Cu (hereinafter, simply referred to as "inorganic component"). When the inorganic oxide (D) contains the inorganic component, the weather resistance tends to be improved without impairing the wear resistance and durability. In the case of using a commercially available product, examples include, but are not limited to, ultrafine particle material products of cerium oxide, zinc oxide, aluminum oxide, bismuth oxide, cobalt oxide, copper oxide, tin oxide, and titanium oxide manufactured by CIK Nanotech Co., Ltd.; titanium oxide "Tinock" (trade name), cerium oxide "Needral" (trade name), tin oxide "Ceramece" (trade name), niobium oxide sol, and zirconium oxide sol manufactured by Taki Chemical Co., Ltd. From the viewpoint of improving weather resistance, it is preferable that the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Zn, Ti and Zr, and more preferably contains Ce. In the present embodiment, the inorganic oxide (D) preferably contains at least one inorganic oxide (D') selected from the group consisting of Ce, Nb, Zn, Ti and Zr from the viewpoint of balance of abrasion resistance, durability and weather resistance, and the content of the inorganic oxide (D') in the hard coat coating film is not particularly limited, but from the viewpoint of balance of abrasion resistance, durability and weather resistance, it is preferably 1 mass% or more, more preferably 2 mass% or more. In addition, from the viewpoint of transparency, the content is preferably 50 mass% or less, more preferably 30 mass% or less. Here, the content can be specified as the total amount of Ce, Nb, Zn, Ti and Zr when the hard coat coating film is 100 mass%.

[0115] [Average particle size of inorganic oxide (D)] In the present embodiment, the average particle diameter of the inorganic oxide (D) is preferably 2 nm or more from the viewpoint of improving the storage stability of the composition of the hard coat layer. From the viewpoint of improving the transparency of the laminate as a whole, it is preferably 150 nm or less, more preferably 100 nm or less, and even more preferably 50 nm or less. Therefore, the average particle diameter is preferably 2 nm or more and 100 nm or less, more preferably 2 nm or more and 50 nm or less. The method for measuring the average particle diameter (D) of the inorganic oxide is not limited to the following, but for example, the water-dispersed colloidal silica is observed at a magnification of 50,000 to 100,000 times using a transmission microscope, and 100 to 200 inorganic oxide particles are photographed, and the average diameter of the inorganic oxide particles can be measured.

[0116] [Colloidal silica that may be contained in inorganic oxide (D)] The acidic colloidal silica with water as a dispersion medium that is preferably used in this embodiment is not particularly limited, but can be prepared by the sol-gel method or a commercially available product. When preparing by the sol-gel method, reference can be made to Werner Stober et al.; J. Colloid and Interface Sci., 26, 62-69 (1968), Rickey D. Badley et al.; Lang muir 6, 792-801 (1990), and Journal of the Color Materials Association, 61[9], 488-493 (1988), etc. When using commercially available products, examples include Snowtex-O, Snowtex-OS, Snowtex-OXS, Snowtex-O-40, Snowtex-OL, Snowtex-OYL, Snowtex-OUP, Snowtex-PS-SO, Snowtex-PS-MO, Snowtex-AK-XS, Snowtex-AK, Snowtex-AK-L, Snowtex-AK-YL, Snowtex-AK-PS-S (product names, manufactured by Nissan Chemical Industries, Ltd.), Adelite AT-20Q (product name, manufactured by Asahi Denka Kogyo Co., Ltd.), Crebosol 20H12, Crebosol 30CAL25 (product names, manufactured by Clariant Japan Co., Ltd.), and the like.

[0117] In addition, examples of basic colloidal silica include silica stabilized by the addition of alkali metal ions, ammonium ions, and amines, and are not particularly limited. Examples of such basic colloidal silica include, but are not limited to, Snowtex-20, Snowtex-30, Snowtex-XS, Snowtex-50, Snowtex-30L, Snowtex-XL, Snowtex-YL, Snowtex-ZL, Snowtex-UP, Snowtex-ST-PS-S, Snowtex-ST-PS-M, Snowtex-C, Snowtex-CXS, Snowtex-CM, Snowtex-N, Snowtex-NXS, Snowtex-NS, Snowtex-N-4, 0 (trade name, manufactured by Nissan Chemical Industries, Ltd.), Adelite AT-20, Adelite AT-30, Adelite AT-20N, Adelite AT-30N, Adelite AT-20A, Adelite AT-30A, Adelite AT-40, Adelite AT-50 (trade name, manufactured by Asahi Denka Kogyo Co., Ltd.), Crebosol 30R9, Crebosol 30R50, Crebosol 50R50 (trade name, manufactured by Clariant Japan Co., Ltd.), Ludox HS-40, Ludox HS-30, Ludox LS, Ludox AS-30, Ludox SM-AS, Ludox AM, Ludox HSA and Ludox SM (trade name, manufactured by DuPont) are examples of such.

[0118] Furthermore, the colloidal silica having a water-soluble solvent as a dispersion medium is not particularly limited, but examples thereof include MA-ST-M (methanol dispersion type having a particle size of 20 to 25 nm), IPA-ST (isopropyl alcohol dispersion type having a particle size of 10 to 15 nm), EG-ST (ethylene glycol dispersion type having a particle size of 10 to 15 nm), EGST-ZL (ethylene glycol dispersion type having a particle size of 70 to 100 nm), NPC-ST (ethylene glycol monopropyl ether dispersion type having a particle size of 10 to 15 nm), and TOL-ST (toluene dispersion type having a particle size of 10 to 15 nm), all manufactured by Nissan Chemical Industries, Ltd.

[0119] The dry silica particles are not particularly limited, but examples thereof include AEROSIL manufactured by Nippon Aerosil Co., Ltd. and Reolosil manufactured by Tokuyama Corporation.

[0120] Furthermore, these silica particles may contain an inorganic base (sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia, etc.) or an organic base (tetramethylammonium, triethylamine, etc.) as a stabilizer.

[0121] [Shape of inorganic oxide (D)] Furthermore, the shape of the inorganic oxide (D) in this embodiment is not limited to the following, but examples thereof include spherical, angular, polyhedral, elliptical, flat, linear, beaded, and chain-like shapes, and from the viewpoints of hardness and transparency of the hard coat layer, spherical shapes are particularly preferred.

[0122] [Functional group (e)] In this embodiment, the polymer nanoparticles (A) preferably have a functional group (e) that interacts with the matrix component (B) in order to improve the dispersibility of the polymer nanoparticles (A) in the matrix component (B) and improve the wear resistance. The fact that the polymer nanoparticles (A) have a functional group (e) can be confirmed by, for example, IR, GC-MS, pyrolysis GC-MS, LC-MS, GPC, MALDI-MS, TOF-SIMS, TG-DTA, composition analysis by NMR, and analysis by a combination of these.

[0123] Specific examples of the functional group (e) in this embodiment include, but are not limited to, a hydroxyl group, a carboxyl group, an amino group, an amide group, and a functional group consisting of an ether bond. From the viewpoint of interaction, a functional group having a hydrogen bond is preferable, and from the viewpoint of high hydrogen bonding property, an amide group is more preferable, and a secondary amide group and / or a tertiary amide group is even more preferable.

[0124] Examples of compounds containing the functional group (e) and their reaction products include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl vinyl ether or 4-hydroxybutyl vinyl ether, 2-hydroxyethyl allyl ether, (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, 2-dimethylaminoethyl (meth)acrylate, 2-diethylaminoethyl (meth)acrylate, 2-di-n-propylaminoethyl (meth)acrylate, 3-dimethylaminopropyl (meth)acrylate, 4-dimethylaminobutyl (meth)acrylate, N-[2-(meth)acryloyloxy]ethylmorpholine, vinylpyridine, N-vinylcarbazole, N-vinylquinoline, N-methylacrylamide, N-methylmeth ... N-ethylacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N-ethylmethacrylamide, N-methyl-N-ethylacrylamide, N-methyl-N-ethylmethacrylamide, N-isopropylacrylamide, Nn-propylacrylamide, N-isopropylmethacrylamide, Nn-propylmethacrylamide, N-methyl-Nn-propylacrylamide, N-methyl-N-isopropylacrylamide, N-acryloylpyrrolidine, N-methacryloylpyrrolidine, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylhexahydroazepine, N-acryloylmorpholine, N-methacryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, N,N'-methylenebisacrylamide, N,Examples of such an acrylic acid include N'-methylenebismethacrylamide, N-vinylacetamide, diacetone acrylamide, diacetone methacrylamide, N-methylolacrylamide, N-methylolmethacrylamide, Blenmer PE-90, PE-200, PE-350, PME-100, PME-200, PME-400, AE-350 (trade name, manufactured by Nippon Oil & Fats Co., Ltd.), MA-30, MA-50, MA-100, MA-150, RA-1120, RA-2614, RMA-564, RMA-568, RMA-1114, and MPG130-MA (trade name, manufactured by Nippon Nyukazai Co., Ltd.). In this specification, (meth)acrylate is a simple expression for acrylate or methacrylate, and (meth)acrylic acid is a simple expression for acrylic acid or methacrylic acid.

[0125] [Core / shell structure of polymer nanoparticles (A)] The polymer nanoparticle (A) in this embodiment preferably has a core / shell structure having a core layer and one or more shell layers covering the core layer. From the viewpoint of interaction with the matrix component (B) in the outermost layer of the core / shell structure, the polymer nanoparticle (A) preferably has a functional group (e).

[0126] [Other compounds that may be contained in the polymer nanoparticles (A)] The polymer nanoparticles (A) according to the present embodiment may contain the following polymers in order to improve the stability of the particles by providing electrostatic repulsion between the particles. For example, polyurethane-based, polyester-based, poly(meth)acrylate-based, poly(meth)acrylic acid, polyvinyl acetate-based, polybutadiene-based, polyvinyl chloride-based, chlorinated polypropylene-based, polyethylene-based, polystyrene-based polymers, or poly(meth)acrylate-silicone-based, polystyrene-(meth)acrylate-based, and styrene-maleic anhydride-based copolymers may be mentioned.

[0127] Among the polymers that may be contained in the above-mentioned polymer nanoparticles (A), a compound that is particularly excellent in electrostatic repulsion may be a polymer or copolymer of (meth)acrylic acid and (meth)acrylate. Specific examples include, but are not limited to, methyl acrylate, (meth)acrylic acid, methyl methacrylate, butyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl acrylate, n-butyl acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate polymers or copolymers. In this case, in order to further improve the electrostatic repulsion, the (meth)acrylic acid may be partially or completely neutralized with amines such as ammonia, triethylamine, and dimethylethanolamine, or bases such as NaOH and KOH.

[0128] The polymer nanoparticles (A) may also contain an emulsifier. The emulsifier is not particularly limited, and examples thereof include acidic emulsifiers such as alkylbenzenesulfonic acid, alkylsulfonic acid, alkylsulfosuccinic acid, polyoxyethylene alkylsulfuric acid, polyoxyethylene alkylarylsulfuric acid, and polyoxyethylene distyrylphenyl ether sulfonic acid; anionic surfactants such as alkali metal (Li, Na, K, etc.) salts of acidic emulsifiers, ammonium salts of acidic emulsifiers, and fatty acid soaps; cationic surfactants of quaternary ammonium salts, pyridinium salts, and imidazolinium salts, such as alkyltrimethylammonium bromide, alkylpyridinium bromide, and imidazolinium laurate; nonionic surfactants such as polyoxyethylene alkylaryl ether, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene oxypropylene block copolymers, and polyoxyethylene distyrylphenyl ether, and reactive emulsifiers having a radical polymerizable double bond.

[0129] Examples of the reactive emulsifier having a radically polymerizable double bond include, but are not limited to, Eleminol JS-2 (trade name, manufactured by Sanyo Chemical Industries, Ltd.), Latemul S-120, S-180A or S-180 (trade name, manufactured by Kao Corporation), Aqualon HS-10, KH-1025, RN-10, RN-20, RN30, RN50 (trade name, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), Adeka Reasoap SE1025, SR-1025, NE-20, NE-30, NE-40 (trade name, manufactured by Asahi Denka Kogyo Co., Ltd.), ammonium salt of p-styrenesulfonic acid, sodium salt of p-styrenesulfonic acid, potassium salt of p-styrenesulfonic acid, alkylsulfonic acid (meth)acrylate such as 2-sulfoethyl acrylate, methylpropanesulfonic acid (meth)acrylamide, ammonium salt of allylsulfonic acid, sodium salt of allylsulfonic acid, potassium salt of allylsulfonic acid, and the like.

[0130] [Other components that may be contained in layer (C)] The layer (C) of this embodiment may contain a solvent, an emulsifier, a plasticizer, a pigment, a dye, a filler, an anti-aging agent, a conductive material, an ultraviolet absorber, a light stabilizer, a release adjuster, a softener, a surfactant, a flame retardant, an antioxidant, and a catalyst as a matrix component (B) according to the application. Since high weather resistance is required especially for outdoor applications, it is preferable to contain a light shielding agent (S2) and a light stabilizer. As the light shielding agent (S2), it is preferable to contain an ultraviolet absorber. Specific examples of the ultraviolet absorber and the light stabilizer include, but are not limited to, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2' benzophenone-based ultraviolet absorbers such as 2,2',4,4'-dihydroxy-4,4'-dimethoxybenzophenone (BASF's trade name "UVINUL3049"), 2,2',4,4'-tetrahydroxybenzophenone (BASF's trade name "UVINUL3050"), 4-dodecyloxy-2-hydroxybenzophenone, 5-benzoyl-2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-hydroxy-4-stearyloxybenzophenone, and 4,6-dibenzoylresortinol;2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-octylphenyl)benzotriazole, 2-[2'-hydroxy-3',5'-bis(α,α'-dimethylbenzyl)phenyl] Benzotriazole), methyl-3-[3-tert-butyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]propionate and polyethylene glycol (molecular weight 300) condensation product (BASF product name "TINUVIN 1130"), isooctyl-3-[3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionate (BASF product name "TINUVIN 384"), 2-(3-dodecyl-5-methyl-2-hydroxyphenyl)propionate (BASF product name "TINUVIN 384"), nyl)benzotriazole (trade name "TINUVIN571" manufactured by BASF), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-4'-octoxyphenyl)benzotriazole, 2-[2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole, benzotriazole-based ultraviolet absorbers such as 2,2-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (trade name "TINUVIN 900" manufactured by BASF), TINUVIN 384-2, TINUVIN 326, TINUVIN 327, TINUVIN 109, TINUVIN 970, TINUVIN 328, TINUVIN 171, TINUVIN 970, TINUVIN PS, TINUVIN P, TINUVIN 99-2, and TINVIN 928 (trade names, manufactured by BASF);2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bisbutyloxyphenyl) -1,3,5-triazine (trade name "TINUVIN 460" manufactured by BASF), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (trade name "TINUVIN 479" manufactured by BASF), TINUVIN 400, TINUVIN 405, TINUVIN 477, TINUVIN 1600 (trade names, manufactured by BASF), and other triazine-based ultraviolet absorbers; HOSTAVIN PR25, HOSTAVIN B-CAP, HOSTAVIN VSU (trade names, manufactured by Clariant), and other malonic acid ester-based ultraviolet absorbers; HOSTAVIN 3206 LIQ, HOSTAVIN VSU P, HOSTAVIN 3212 LIQ (trade name, manufactured by Clariant) and other anilide-based ultraviolet absorbers; amyl salicylate, menthyl salicylate, homomenthyl salicylate, octyl salicylate, phenyl salicylate, benzyl salicylate, p-isopropanol phenyl salicylate and other salicylate-based ultraviolet absorbers; ethyl-2-cyano-3,3-diphenylacrylate (trade name "UVINUL3035" manufactured by BASF) cyanoacrylate-based ultraviolet absorbers such as (2-ethylhexyl)-2-cyano-3,3-diphenylacrylate (BASF's trade name "UVINUL3039") and 1,3-bis((2'-cyano-3',3'-diphenylacryloyl)oxy)-2,2-bis-(((2'-cyano-3',3'-diphenylacryloyl)oxy)methyl)propane (BASF's trade name "UVINUL3030");2-hydroxy-4-acryloxybenzophenone, 2-hydroxy-4-methacryloxybenzophenone, 2-hydroxy-5-acryloxybenzophenone, 2-hydroxy-5-methacryloxybenzophenone, 2-hydroxy-4-(acryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-diethoxy)benzophenone, 2-hydroxy-4-(acryloxy-triethoxy)benzophenone, 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole (trade name "RUVA-93" manufactured by Otsuka Chemical Co., Ltd.), 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole (trade name "RUVA-93" manufactured by Otsuka Chemical Co., Ltd.), radical polymerizable ultraviolet absorbers having a radical polymerizable double bond in the molecule, such as 2-(2'-hydroxy-5'-methacrylyloxypropyl-3-tert-butylphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-methacrylyloxypropyl-3-tert-butylphenyl)-5-chloro-2H-benzotriazole, and 3-methacryloyl-2-hydroxypropyl-3-[3'-(2''-benzotriazolyl)-4-hydroxy-5-tert-butyl]phenylpropionate (trade name "CGL-104" manufactured by Ciba-Geigy Japan Ltd.); ultraviolet absorbing polymers, such as UV-G101, UV-G301, UV-G137, UV-G12, and UV-G13 (trade names manufactured by Nippon Shokubai Co., Ltd.);Bis(2,2,6,6-tetramethyl-4-piperidyl) succinate, bis(2,2,6,6-tetramethylpiperidyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl) 2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2-butylmalonate, 1-[2-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propynyloxy]ethyl]-4-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propynyloxy]-2,2,6,6 - Tetramethylpiperidine, a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl-1,2,2,6,6-pentamethyl-4-piperidyl-sebacate (BASF's trade name "TINUVIN 292"), bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, TINUVIN 123, TINUVIN 144, TINUVIN 152, TINUVIN 249, TINUVIN 292, TINUVIN 5100 (BASF's trade names), etc. Daled amine light stabilizers; 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, 1,2,2,6,6-pentamethyl-4-piperidyl acrylate, 2,2,6,6-tetramethyl-4-piperidyl methacrylate, 2,2,6,6-tetramethyl-4-piperidyl acrylate, 1,2,2,6,6-pentamethyl-4-iminopiperidyl methacrylate, 2,2,6,6-tetramethyl-4-iminopiperidyl methacrylate, 4-cyano-2,2,6,6-tetramethyl-4-piperidyl radically polymerizable hindered amine-based light stabilizers such as methacrylate and 4-cyano-1,2,2,6,6-pentamethyl-4-piperidyl methacrylate; light-stable polymers such as U-DOUBLE E-133, U-DOUBLE E-135, U-DOUBLE S-2000, U-DOUBLE S-2834, U-DOUBLE S-2840, U-DOUBLE S-2818, and U-DOUBLE S-2860 (trade names, manufactured by Nippon Shokubai Co., Ltd.); ultraviolet absorbers reactive with silanol groups, isocyanate groups, epoxy groups, semicarbazide groups, and hydrazide groups;Examples of the inorganic ultraviolet absorbents include cerium oxide, zinc oxide, aluminum oxide, zirconium oxide, niobium oxide, bismuth oxide, cobalt oxide, copper oxide, tin oxide, and titanium oxide, and these may be used alone or in combination of two or more kinds.

[0131] [Transparency of hard coat layer] In this embodiment, the transparency of the hard coat layer can be evaluated from the viewpoint of appearance change by the total light transmittance maintenance rate obtained by the following formula. In this embodiment, the total light transmittance maintenance rate of the hard coat layer is preferably 90% or more, more preferably 95% or more from the viewpoint of ensuring natural lighting, and particularly preferably 98% or more from the viewpoint of ensuring visibility through the material. The total light transmittance maintenance rate of the hard coat layer can be adjusted to the above-mentioned range, for example, by adopting the above-mentioned preferred embodiments of the polymer nanoparticles (A) and the matrix component (B). Total light transmittance maintenance rate (%) of hard coat layer = (total light transmittance (%) of laminate / total light transmittance (%) of substrate) × 100

[0132] <Paint composition (I)> In this embodiment, the layer (C) is preferably obtained, for example, by using the following coating composition (I). The coating composition (I) is a coating composition containing polymer nanoparticles (A) and a matrix raw material component (B'), and has an elastic recovery rate η of the polymer nanoparticles (A) measured by an indentation test in accordance with ISO14577-1. ITA is 0.30 or more and 0.90 or less, and the Martens hardness HM A and the Martens hardness HM of the matrix raw material component (B'). B' But, HM B' / HM A >1, and the matrix raw material component (B') preferably contains an inorganic oxide (D). The inorganic oxide (D) in the coating composition (I) preferably contains at least one inorganic component selected from the group consisting of Ce, Nb, Al, Zn, Ti, Zr, Sb, Mg, Sn, Bi, Co and Cu. Details of each component contained in the coating composition (I) that are not mentioned below are the same as those described above for each component contained in the layer (C).

[0133] [Hardness HM of polymer nanoparticles (A) A and the hardness HM of the matrix raw material component (B') B ] In the coating composition (I), the Martens hardness HM of the polymer nanoparticles (A) A and the Martens hardness HM of the matrix raw material component (B') B' It is preferable that the relationship of the following formula (3) is satisfied. HM B' / HM A >1 Formula (3) As described above, the above relationship is satisfied in the coating composition (I), and therefore, in the layer (C) obtained by using the coating composition (I), the Martens hardness HM A and the Martens hardness HM of the matrix raw material component (B') B' The Martens hardness of each of the coating compositions (I) can be measured, for example, by separating the polymer nanoparticles (A) and the matrix raw material component (B') by an operation such as centrifugation or ultrafiltration, and measuring each of the separated components based on the method described in the examples below. The above HM A and H.M. B The values ​​of can be adjusted to satisfy the above-mentioned magnitude relationship depending on the structures and composition ratios of the constituent components of the polymer nanoparticles (A) and the matrix raw material component (B'), but are not limited to this method.

[0134] [Elastic recovery η of polymer nanoparticles (A) ITA ] Elastic recovery rate η of the polymer nanoparticles (A) in this embodiment ITA is W in ISO14577-1 elast / W total Ratio of η IT The parameter described as the total mechanical work of the indentation W was measured on the coating of the deposited polymeric nanoparticles (A).total and the elastic return deformation work of the dent W elast It is expressed as the ratio of elastic recovery η ITA The higher the elastic recovery rate η of the polymer nanoparticles (A), the more the coating film can return to its original state when it is subjected to an impact, and the higher the self-repairing ability against the impact. ITA is preferably 0.30 or more under the measurement conditions (Vickers square pyramid diamond indenter, load increase condition 2mN / 20sec, load decrease condition 2mN / 20sec), and η ITA The elastic recovery rate η of the polymer nanoparticles (A) is preferably 0.90 or less. ITA is more preferably 0.50 or more, and even more preferably 0.60 or more. The measurement of the elastic recovery rate of the polymer nanoparticles (A) is not limited to the following, but for example, the polymer nanoparticles (A) and the matrix raw material component (B') are separated by an operation such as centrifugation or ultrafiltration, and the separated polymer nanoparticles (A) are dispersed in a solvent to obtain a composition, which is then coated and dried to form a coating film. The coating film can be measured using a microhardness tester Fischerscope (HM2000S manufactured by Fisher Instruments), an ultra-microindentation hardness tester (ENT-NEXUS manufactured by Elionix Co., Ltd.), a nanoindenter (iNano, G200 manufactured by Toyo Corporation), a nanoindentation system (TI980 manufactured by Bruker), or the like. Elastic recovery rate η ITA The method for adjusting to within the above range is not limited to the following, but examples thereof include adjusting the structure and composition ratio of the components constituting the polymer nanoparticles (A). The layer (C) can be obtained as a cured product obtained by curing the coating composition (I) by hydrolysis and condensation or the like. The composition of the polymer nanoparticles (A) usually does not change during the curing process. Therefore, the elastic recovery η of the polymer nanoparticles (A) in the coating composition (I) measured by the method described in the examples below can be calculated by the following formula: ITA The value of the elastic recovery η of the polymer nanoparticles (A) in the layer (C) ITA The elastic recovery η in layer (C) is in good agreement withITA The value of can be determined.

[0135] [Solvent (H)] The coating composition (I) in this embodiment preferably contains a solvent (H). The solvent (H) that can be used is not particularly limited, and a general solvent can be used. Examples of the solvent include, but are not limited to, water; ethylene glycol, butyl cellosolve, isopropanol, n-butanol, 2-butanol, ethanol, methanol, denatured ethanol, 2-methoxy-1-propanol, 1-methoxy-2-propanol, diacetone alcohol, glycerin, monoalkyl monoglyceryl ether, propylene glycol monomethyl ether, diethylene glycol monobutyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monobutyl ether, diethylene glycol mono Examples of the solvent include alcohols such as phenyl ether and tetraethylene glycol monophenyl ether; aromatic hydrocarbons such as toluene and xylene; aliphatic hydrocarbons such as hexane, cyclohexane, and heptane; esters such as ethyl acetate and n-butyl acetate; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ethers such as tetrahydrofuran and dioxane; amides such as dimethylacetamide and dimethylformamide; halogen compounds such as chloroform, methylene chloride, and carbon tetrachloride; dimethylsulfoxide, and nitrobenzene; and the like. These may be used alone or in combination of two or more. Among these, from the viewpoint of reducing the environmental load when removing the solvent, it is particularly preferable to include water and alcohols.

[0136] The components, size, composition ratio, etc. of the polymer nanoparticles (A) contained in the coating composition (I) will be explained below. Details of points not mentioned below are as described above for the polymer nanoparticles (A) contained in layer (C). In addition, the matrix raw material component (B') contained in the coating composition (I) is cured by hydrolysis condensation or the like in the process of obtaining the layer (C). That is, the matrix raw material component (B') contained in the coating composition (I) is in a relationship where it becomes the corresponding matrix component (B) in the obtained layer (C). The components, size, composition ratio, etc. of the matrix raw material component (B') will be explained below, but details of points not mentioned below are as described above for the matrix component (B) contained in the layer (C).

[0137] In the coating composition (I), the polymer nanoparticles (A) preferably contain the hydrolyzable silicon compound (a) described above, and the matrix raw material component (B') preferably contains the hydrolyzable silicon compound (b) described above. In addition, the hydrolyzable silicon compound (a) in the coating composition (I) preferably contains one or more selected from the compounds containing the atomic group represented by the above formula (a-1), their hydrolysis products and condensates, and the compounds represented by the above formula (a-2), their hydrolysis products and condensates. Similarly, the hydrolyzable silicon compound (b) in the coating composition (I) preferably contains one or more selected from the compounds containing the atomic group represented by the above formula (b-1), their hydrolysis products and condensates, and the compounds represented by the above formula (b-2), their hydrolysis products and condensates. Details of the hydrolyzable silicon compounds (a) and (b) in the coating composition (I) are as described above for the polymer nanoparticles (A) and matrix component (B) contained in the layer (C).

[0138] [Content of hydrolyzable silicon compound (a) in polymer nanoparticles (A)] In the coating composition (I), the content of the hydrolyzable silicon compound (a) refers to the solid weight ratio of the hydrolyzable silicon compound (a) contained in the polymer nanoparticle (A), and the higher the content, the better the abrasion resistance, weather resistance, and heat resistance are improved. The content is preferably 50% by mass or more, more preferably 60% by mass or more. The content of the hydrolyzable silicon compound (a) in the polymer nanoparticle (A) can be measured, for example, by IR analysis, NMR analysis, elemental analysis, etc. of the polymer nanoparticle (A), but is not limited to the following.

[0139] [Functional group (e)] In the coating composition (I), the polymer nanoparticles (A) preferably have a functional group (e) that interacts with the matrix raw material component (B'). When the polymer nanoparticles (A) have a functional group (e), the matrix raw material component (B') tends to be easily adsorbed on the surface of the polymer nanoparticles (A) and tends to be stabilized as a protective colloid, and as a result, the storage stability of the coating composition (I) tends to be improved. Furthermore, when the polymer nanoparticles (A) have a functional group (e), the interaction between the polymer nanoparticles (A) and the matrix raw material component (B') becomes stronger, which increases the viscosity of the coating composition (I) relative to the solid content concentration, and tends to suppress sagging when coating a complex shape, and as a result, the film thickness of the layer (C) tends to be uniform. The fact that the polymer nanoparticles (A) have a functional group (e) can be confirmed by, for example, composition analysis by IR, GC-MS, pyrolysis GC-MS, LC-MS, GPC, MALDI-MS, TOF-SIMS, TG-DTA, NMR, and combinations thereof.

[0140] Specific examples of the functional group (e) in this embodiment include, but are not limited to, a hydroxyl group, a carboxyl group, an amino group, an amide group, and a functional group consisting of an ether bond. From the viewpoint of interaction, a functional group having a hydrogen bond is preferable, and from the viewpoint of high hydrogen bonding property, an amide group is more preferable, and a secondary amide group and / or a tertiary amide group is even more preferable.

[0141] Examples of compounds containing the functional group (e) and their reaction products include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl vinyl ether or 4-hydroxybutyl vinyl ether, 2-hydroxyethyl allyl ether, (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, 2-dimethylaminoethyl (meth)acrylate, 2-diethylaminoethyl (meth)acrylate, 2-di-n-propylaminoethyl (meth)acrylate, 3-dimethylaminopropyl (meth)acrylate, 4-dimethylaminobutyl (meth)acrylate, N-[2-(meth)acryloyloxy]ethylmorpholine, vinylpyridine, N-vinylcarbazole, N-vinylquinoline, N-methylacrylamide, N-methylmeth ... N-ethylacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N-ethylmethacrylamide, N-methyl-N-ethylacrylamide, N-methyl-N-ethylmethacrylamide, N-isopropylacrylamide, Nn-propylacrylamide, N-isopropylmethacrylamide, Nn-propylmethacrylamide, N-methyl-Nn-propylacrylamide, N-methyl-N-isopropylacrylamide, N-acryloylpyrrolidine, N-methacryloylpyrrolidine, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylhexahydroazepine, N-acryloylmorpholine, N-methacryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, N,N'-methylenebisacrylamide, N,Examples of such an acrylic acid include N'-methylenebismethacrylamide, N-vinylacetamide, diacetone acrylamide, diacetone methacrylamide, N-methylolacrylamide, N-methylolmethacrylamide, Blenmer PE-90, PE-200, PE-350, PME-100, PME-200, PME-400, AE-350 (trade name, manufactured by Nippon Oil & Fats Co., Ltd.), MA-30, MA-50, MA-100, MA-150, RA-1120, RA-2614, RMA-564, RMA-568, RMA-1114, and MPG130-MA (trade name, manufactured by Nippon Nyukazai Co., Ltd.). In this specification, (meth)acrylate is a simple expression for acrylate or methacrylate, and (meth)acrylic acid is a simple expression for acrylic acid or methacrylic acid.

[0142] [Elastic recovery rate η of matrix raw material component (B') ITB' and elastic recovery rate η of matrix component (B) ITB ] In the coating composition (I), the elastic recovery rate η of the matrix raw material component (B') ITB' is defined as "W elast / W total Ratio of η IT The coating of the matrix raw material component (B') formed was measured using the parameters described as "total mechanical work W total and the elastic return deformation work of the dent W elast It is expressed as the ratio of elastic recovery η ITB' The higher the elastic recovery rate η of the matrix raw material component (B'), the more the coating film can return to its original state when it is subjected to an impact, and the higher the self-repairing ability against the impact. ITB' is preferably 0.60 or more, more preferably 0.65 or more, under the measurement conditions (Vickers square pyramid diamond indenter, load increase condition 2mN / 20sec, load decrease condition 2mN / 20sec). In addition, from the viewpoint of being able to follow the deformation of the substrate and component (A) when forming a coating film, η ITB'is preferably 0.95 or less. The elastic recovery rate of the matrix raw material component (B') can be measured, but is not limited to the following, by, for example, separating the polymer nanoparticles (A) and the matrix raw material component (B') by an operation such as centrifugation, dissolving the separated matrix raw material component (B') in a solvent, coating the composition, and drying the coating film to form a film. The film can be measured using a microhardness tester Fischerscope (HM2000S manufactured by Fisher Instruments), a super-microindentation hardness tester (ENT-NEXUS manufactured by Elionix Co., Ltd.), a nanoindenter (iNano, G200 manufactured by Toyo Corporation), a nanoindentation system (TI980 manufactured by Bruker), or the like. As described above, the matrix component (B) is a cured product obtained by curing the matrix raw material component (B') through hydrolysis and condensation. Therefore, the elastic recovery rate η of the matrix raw material component (B') measured by the method described in the examples described later is ITB' The value of the elastic recovery η of the corresponding matrix component (B) ITB The elastic recovery η ITB That is, the elastic recovery rate η of the matrix component (B) in this embodiment can be determined. ITB is preferably 0.60 or more, more preferably 0.65 or more. From the viewpoint of being able to follow the deformation of the substrate and component (A) when forming a coating film, η ITB is preferably 0.95 or less. Elastic recovery rate η ITB' and elastic recovery η ITB The method for adjusting to within the above range is not limited to the following, but examples thereof include adjusting the structure and composition ratio of the components constituting the matrix raw material component (B').

[0143] In the coating composition (I), the "hydrolyzable silicon compound (a) contained in the polymer nanoparticles (A)" may be the same as or different from the "hydrolyzable silicon compound (b) contained in the matrix raw material component (B')". Even if the two are the same type, they are distinguished by calling the one contained in the polymer nanoparticles (A) the hydrolyzable silicon compound (a) and the one contained in the matrix raw material component (B') the hydrolyzable silicon compound (b).

[0144] [Inorganic oxides (D)] In the coating composition (I), the matrix raw material component (B') contains an inorganic oxide (D). By containing the inorganic oxide (D), not only is the hardness of the matrix raw material component (B') improved and the abrasion resistance improved, but also the contamination resistance of the coating film tends to be improved due to the hydrophilicity of the hydroxyl groups on the particle surfaces.

[0145] The inorganic oxide (D) in the coating composition (I) may be in any form, either alone or in a mixture. From the viewpoint of the interaction with the hydrolyzable silicon compound (b) described above, it is preferable to further include silica particles, and from the viewpoint of dispersibility, it is preferable to further include colloidal silica as the form of silica particles. When the inorganic oxide (D) includes colloidal silica, it is preferable that it is in the form of an aqueous dispersion, and it can be used whether it is acidic or basic.

[0146] The average particle size of the inorganic oxide (D) in the coating composition (I) is preferably 2 nm or more from the viewpoint of good storage stability of the coating composition (I). From the viewpoint of good transparency of the laminate as a whole, it is preferably 150 nm or less, more preferably 100 nm or less, and even more preferably 50 nm or less. Therefore, the average particle size is preferably 2 nm or more and 100 nm or less, more preferably 2 nm or more and 50 nm or less. The method for measuring the average particle size of the inorganic oxide (D) in the coating composition (I) is as described above for the inorganic oxide (D) contained in the layer (C).

[0147] Other characteristics of the inorganic oxide (D) in the coating composition (I) are as described above for the inorganic oxide (D) contained in the layer (C).

[0148] [Volume fraction of polymer nanoparticles (A) relative to the total volume of polymer nanoparticles (A) and matrix raw material component (B')] In the coating composition (I), the volume fraction of the polymer nanoparticles (A) relative to the total of the polymer nanoparticles (A) and the matrix raw material component (B') is preferably 2% or more, more preferably 3% or more, and even more preferably 5% or more from the viewpoint of film-forming properties, and is preferably 80% or less, more preferably 70% or less, and even more preferably 45% or less from the viewpoint of transparency. The volume fraction of the polymer nanoparticles (A) in the coating composition (I) can be calculated, for example, from the ratio of the polymer nanoparticles (A) in the entire coating film in the cross-sectional SEM image after forming the layer (C) or the component ratio of the polymer nanoparticles (A) in the components constituting the coating composition (I).

[0149] [Core / shell structure of polymer nanoparticles (A)] In the coating composition (I), the polymer nanoparticles (A) preferably have a core / shell structure with a core layer and one or more shell layers covering the core layer. The polymer nanoparticles (A) preferably have the above-mentioned functional group (e) from the viewpoint of the interaction with the matrix raw material component (B') in the outermost layer of the core / shell structure. The fact that the polymer nanoparticles (A) have a core / shell structure can be confirmed, for example, by a transmission electron microscope image of the cross section of the coating film.

[0150] [Other components that may be included in the coating composition (I)] From the viewpoint of further improving the coating properties of the coating composition (I), the coating composition (I) may contain, in addition to the above-mentioned components as the matrix raw material component (B'), thickeners, leveling agents, thixotropic agents, defoamers, freeze stabilizers, dispersants, wetting agents, rheology control agents, film-forming aids, rust inhibitors, plasticizers, lubricants, preservatives, antifungal agents, antistatic agents, antistatic agents, etc., as necessary. From the viewpoint of improving the film-forming properties, it is preferable to use wetting agents and film-forming aids, and specific examples thereof include, but are not limited to, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, ethylene glycol mono-2-ethylhexyl ether, 2,2,4-trimethyl-1,3-butanediol isobutyrate, diisopropyl glutarate, propylene glycol-n-butyl ether, dipropylene glycol-n-butyl ether, tripropylene glycol-n-butyl ether, dipropylene glycol methyl ether, tripropylene glycol methyl ether, Megafac F-443, F-444, F-445, F-470, F-471, F-472SF, F-474, F-475, F-477, F-479, F-480SF, F-482, F-483, F-489, F-172D, F-178K (trade names, manufactured by DIC Corporation), SN Wet 366, SN Wet 980, SN Wet L, SN Wet S, SN Wet 125, SN Wet 126, SN Wet 970 (trade names, manufactured by San Nopco Co., Ltd.), etc. These compounds may be used alone or in combination of two or more kinds.

[0151] [Light blocking agent (S2)] The coating composition (I) may contain a light-shielding agent (S2). It is preferable that the coating composition (I) contains a light-shielding agent (S2). The light-shielding agent (S2) is not particularly limited, but for example, the light-shielding agent (S1) in the coating composition (J) can be appropriately used.

[0152] [catalyst] The coating composition (I) may contain a catalyst as the matrix raw material component (B'). When the coating composition (I) contains a catalyst that promotes the reaction between reactive groups, it is preferable in that unreactive groups are less likely to remain in the coating film, and the hardness is increased, and not only the abrasion resistance is improved, but also the weather resistance is improved. The catalyst is not particularly limited, but it is preferable that it is dissolved or dispersed when obtaining a hard coat coating film. Such catalysts are not particularly limited, but for example, organic acids, inorganic acids, organic bases, inorganic bases, metal alkoxides, metal chelates, etc. can be mentioned, and these catalysts may be used alone or in combination of two or more kinds.

[0153] [Properties of coating composition (I)] From the viewpoint of coatability, the coating composition (I) has a solids concentration of preferably 0.01 to 60 mass%, more preferably 1 to 40 mass%, and from the viewpoint of coatability, the viscosity of the coating composition (I) at 20°C is preferably 0.1 to 100,000 mPa s, more preferably 1 to 10,000 mPa s.

[0154] <Method of manufacturing hard coat layer> The method for producing the hard coat layer in this embodiment is not particularly limited, but for example, a coating composition (I) obtained by dispersing and dissolving polymer nanoparticles (A), matrix raw material components (B'), inorganic oxides (D), and other components as appropriate in a solvent is applied to the substrate, and a coating film is formed by heat treatment, ultraviolet irradiation, infrared irradiation, etc. Furthermore, the coating method is not limited to the following, but examples thereof include spray spraying, flow coating, brush coating, dip coating, spin coating, screen printing, casting, gravure printing, and flexographic printing. The applied coating composition (I) can be formed into a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, etc., preferably at room temperature to 250 ° C, more preferably at 40 ° C to 150 ° C. Furthermore, this coating can be applied not only to already molded substrates, but also to flat plates before molding, such as pre-coated metals including rust-resistant steel plates.

[0155] [Surface treatment of hard coat layer] In the present embodiment, the hard coat layer may be silica-processed on the surface to form a silica layer from the viewpoint of weather resistance. The method of forming the silica layer is not particularly limited, but specific examples include silica processing by PECVD in which silicone or silazane is vapor-deposited / cured, and silica processing technology in which the surface is modified to silica by irradiating 155 nm ultraviolet light. In particular, surface processing by PECVD is preferred because it can produce a layer that is difficult for oxygen and water vapor to pass through without deteriorating the surface. Silicones or silazanes that can be used for PECVD are not limited to the following, but specific examples include octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, decamethylcyclopentasiloxane, hexamethyldisiloxane, vinylmethysilane, vinylmethoxysilane, dimethyldimethoxysilane, TEOS, tetramethyldisiloxane, tetramethyltetravinylcyclotetrasiloxane, hexamethyldisilazane, and the like, and these may be used alone or in combination of two or more kinds.

[0156] In this embodiment, the hard coat layer may further have a functional layer on at least one surface thereof. Examples of the functional layer include, but are not limited to, an anti-reflection layer, an anti-fouling layer, a polarizing layer, and an impact absorbing layer.

[0157] [Haze value H1 of the substrate with adhesive layer and haze value H2 of the laminate] In the laminate of this embodiment, the haze value H1 of the substrate with the adhesive layer is larger than the haze value H2 of the laminate. By satisfying such a relationship, in the laminate of this embodiment, a scattering layer is formed at the interface between the substrate with the adhesive layer and the hard coat layer, so that the generation of interference fringes is suppressed and the optical properties are improved.

[0158] In this embodiment, from the viewpoint of transparency, the haze value H1 of the substrate with the adhesive layer is preferably 60% or less, more preferably 50% or less, and even more preferably 30% or less. From the same viewpoint, the haze value H2 of the laminate is preferably 5% or less, more preferably 2% or less, and even more preferably 1% or less. Methods for adjusting each haze value within the above range include, but are not limited to, the following: H1 is controlled by the particle size of the adhesive emulsion particles (F), the particle size and shape of the inorganic oxide (G), the weight ratio of the adhesive emulsion particles (F) to the inorganic oxide (G), the content of the light shielding agent, and the content of the curing agent and other additives; and H2 is controlled by the particle size of the polymer nanoparticles (A), the component ratio of the polymer nanoparticles (A) to the matrix component (B), and the content of the inorganic oxide (D) in the matrix component (B). In particular, when the amount of the inorganic oxide (G) or the inorganic oxide (D) is increased, each haze value tends to increase, and when the amount is decreased, each haze value tends to decrease. Each haze value can be measured by the method described in the examples below. The haze value H1 can be measured on the substrate with the adhesive layer, and the haze value H2 can be measured on the laminate (substrate with the adhesive layer and hard coat layer). The haze values ​​H1 and H2 may be measured after forming the substrate with the adhesive layer and the laminate, respectively.

[0159] [Surface roughness Ra1 of substrate with adhesive layer and surface roughness Ra2 of laminate] In the laminate of this embodiment, the surface roughness Ra1 of the substrate with the adhesive layer is larger than the surface roughness Ra2 of the laminate of the laminate. By satisfying such a relationship, in the laminate of this embodiment, a scattering layer is formed at the interface between the substrate with the adhesive layer and the hard coat layer, so that the generation of interference fringes is suppressed and the optical properties are improved.

[0160] In this embodiment, from the viewpoint of transparency, the surface roughness Ra1 of the substrate with an adhesive layer is preferably 500 nm or less, more preferably 300 nm or less, even more preferably 200 nm or less, and most preferably 150 nm or less. Also, in this embodiment, from the viewpoint of adhesion, the surface roughness Ra1 of the substrate with an adhesive layer is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 40 nm or more. Moreover, from the viewpoint of transparency, the surface roughness Ra2 of the laminate is preferably less than 100 nm, more preferably 50 nm or less, even more preferably 30 nm or less, and still more preferably 20 nm or less. Methods for adjusting the surface roughnesses Ra1 and Ra2 within the above ranges include, but are not limited to, for example, controlling the particle size of the adhesive emulsion particles (F), the weight ratio of the adhesive emulsion particles (F) to the inorganic oxide (G), and the content of the light-shielding agent for Ra1, and controlling the particle size of the polymer nanoparticles (A), the component ratio of the polymer nanoparticles (A) to the matrix component (B), and the content of the inorganic oxide (D) in the matrix component (B) for Ra2. In particular, increasing the amount of the inorganic oxide (G) or the inorganic oxide (D) tends to increase each surface roughness Ra, and decreasing it tends to decrease it. Each surface roughness Ra1 and Ra2 can be measured by the method described in the examples below. The surface roughness Ra1 can be measured on the substrate with the adhesive layer, and the surface roughness Ra2 can be measured on the laminate (substrate with the adhesive layer and hard coat layer). The surface roughness Ra1 and Ra2 may be measured after forming the substrate with the adhesive layer and the laminate, respectively. The surface roughness Ra may also be calculated by measuring the shape of the interface between the adhesive layer and the hard coat layer from a cross-sectional SEM image of the laminate.

[0161] <Applications of laminates> The laminate of the present embodiment has excellent abrasion resistance and durability. Therefore, the applications of the hard coat film and the substrate with the hard coat film are not particularly limited, but examples thereof include building materials, vehicle parts, electronic devices, and electrical products. Examples of building material applications include, but are not limited to, window glass for construction machinery, window glass for buildings, houses, greenhouses, etc., roofs for garages and arcades, lighting fixtures and traffic lights, wallpaper covering materials, signs, sanitary products such as bathtubs and washbasins, building materials for kitchens, exterior wall materials, and interior flooring materials such as flooring materials, cork materials, tiles, cushion flooring, and linoleum. Examples of vehicle members include, but are not limited to, parts used in automobiles, aircraft, and trains. Specific examples include glass for front, rear, front door, rear door, rear quarter, sunroof, etc., exterior members such as front bumpers, rear bumpers, spoilers, door mirrors, front grilles, emblem covers, and bodies, interior members such as center panels, door panels, instrument panels, and center consoles, lamp members such as headlamps and rear lamps, lens members for vehicle-mounted cameras, lighting covers, decorative films, and various glass substitute members. Preferred examples of electronic devices and electrical products include, but are not limited to, mobile phones, personal digital assistants, personal computers, portable game consoles, office automation equipment, solar cells, flat panel displays, touch panels, optical discs such as DVDs and Blu-ray discs, optical components such as polarizing plates, optical filters, lenses, prisms, and optical fibers, and optical films such as anti-reflection films, alignment films, polarizing films, and retardation films. In addition to the above, the laminate of this embodiment can be applied to various fields such as machine parts, agricultural materials, fishing materials, transport containers, packaging containers, toys, and miscellaneous goods.

[0162] <<Second embodiment>> Here, a second aspect according to this embodiment (hereinafter also referred to as "second embodiment") will be described in detail.

[0163] <Hard coat coating> The hard coat film (hereinafter, also referred to as "coating film (C)") of this embodiment (hereinafter, unless otherwise specified, "this embodiment" in the section <<Second embodiment>> means the second embodiment) is a hard coat film containing polymer nanoparticles (A) and a matrix component (B), and the Martens hardness HM A and the Martens hardness HM of the matrix component (B). B But, HM B / HM A > 1, and the Martens hardness HM of the hard coat coating is 100 N / mm 2 The matrix component (B) contains an inorganic oxide (D), and the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Al, Zn, Ti, Zr, Sb, Mg, Sn, Bi, Co, and Cu. The above Martens hardness HM A and Martens hardness HM B Even when it is difficult to confirm the magnitude relationship between the adhesive forces F and B, the magnitude relationship between the Martens hardnesses can be estimated by comparing the adhesive forces of the polymer nanoparticles (A) and the matrix component (B) described below. Since the lower the adhesive force, the higher the elasticity, the lower the adhesive force, the less the coating is deformed and the higher the hardness. Specifically, the hard coat coating of this embodiment can also be specified as follows. That is, the hard coat coating of this embodiment is a hard coat coating containing polymer nanoparticles (A) and a matrix component (B), and the adhesive force F of the polymer nanoparticles (A) measured in the adhesive force mode of a scanning probe microscope (SPM) is A and the adhesive force F of the matrix component (B). B But, F A / F B > 1, and the Martens hardness HM of the hard coat coating is 100 N / mm 2 The matrix component (B) contains an inorganic oxide (D), and the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Al, Zn, Ti, Zr, Sb, Mg, Sn, Bi, Co, and Cu. The hard coat coating film of the present embodiment is configured as described above, and therefore has high abrasion resistance, durability and weather resistance.The hard coat coating film of the present embodiment exhibits high levels of abrasion resistance, durability and weather resistance, and is useful as a hard coat for, but not limited to, building materials, automobile parts, electronic devices, electrical products, etc., and is particularly preferably used for automobile parts.

[0164] In the hard coat coating film of this embodiment, the polymer nanoparticles (A) are preferably dispersed in the matrix component (B). In this embodiment, "dispersion" means that the polymer nanoparticles (A) are dispersed in the matrix component (B) as a dispersed phase, and the matrix component (B) is continuous, and the polymer nanoparticles (A) are distributed in the matrix component (B) uniformly or while forming a structure. The dispersion can be confirmed by cross-sectional SEM observation of the hard coat coating film. In the hard coat coating film of this embodiment, the polymer nanoparticles (A) are dispersed in the matrix component (B), so that the hard coat coating film tends to have high abrasion resistance.

[0165] In this specification, the Martens hardness HM is 100 N / mm 2 The coating film described above is specifically referred to as a "hard coat coating film."

[0166] [Martens hardness] The Martens hardness in this embodiment is a hardness in accordance with ISO14577-1, and is a value calculated from the indentation depth at 2mN under the measurement conditions (Vickers square pyramid diamond indenter, load increase condition 2mN / 20sec, load decrease condition 2mN / 20sec). The Martens hardness in this embodiment can be measured using, for example, a microhardness tester Fischerscope (HM2000S manufactured by Fisher Instruments), a super-microindentation hardness tester (ENT-NEXUS manufactured by Elionix Co., Ltd.), a nanoindenter (iNano, G200 manufactured by Toyo Corporation), and a nanoindentation system (TI980 manufactured by Bruker). The shallower the indentation depth, the higher the Martens hardness, and the deeper the indentation depth, the lower the Martens hardness.

[0167] [Adhesion force] The adhesive force in this embodiment can be measured by a scanning probe microscope (SPM), and since the lower the adhesive force, the higher the elasticity, the lower the adhesive force, the less likely the coating film is to deform and the higher the hardness. The method for measuring the adhesive force is not limited to the following, but for example, the measurement can be performed using SPM-970 and SPM-9700HT manufactured by Shimadzu Corporation, Dimension ICON manufactured by Bruker AXS, AFM5000II manufactured by Hitachi High-Tech Science Corporation, etc.

[0168] [Other hardness] The magnitude relationship of the Martens hardness and adhesive force in the above-mentioned embodiment can also be estimated by checking the magnitude relationship of the measured values ​​using other hardness as an index. The other hardness is not particularly limited as long as it is an index indicating the difficulty of deformation of the material when force is applied to the material, and can include Vickers hardness and indentation hardness measured by an indentation hardness tester represented by a microhardness tester or a nanoindentation measuring instrument, and an index expressed by a logarithmic decrement measured by a pendulum-type viscoelasticity represented by a rigid pendulum-type physical property tester. In addition, it can also include indexes expressed by phase, friction force, viscoelasticity, adsorption force, hardness and elastic modulus measured by a scanning probe microscope (SPM). If it is confirmed that the hardness of the matrix component (B) is higher than the hardness of the polymer nanoparticles (A) in these indices, it is estimated that the matrix component (B) is harder than the polymer nanoparticles (A) in terms of Martens hardness and adhesive force.

[0169] [Martens hardness HM of polymer nanoparticles (A) A and the Martens hardness HM of the matrix component (B) B ] Martens hardness HM of the polymer nanoparticles (A) in this embodiment A and the Martens hardness HM of the matrix component (B) B satisfies the relationship of the following formula (1). HM B / HM A >1 formula (1) Formula (1) expresses the presence of soft polymer nanoparticles (A) in a hard matrix component (B), and the three-dimensional gradient in hardness allows the coating film (C) to be endowed with abrasion resistance not achieved by conventional coating films. The reasons for this, although not intended to be limited to the following, are presumed to be that the soft nanoparticles absorb shock and the hard matrix component suppresses deformation. HM A From the viewpoint of shock absorption, the range is 50N / mm 2 More than 100N / mm is preferable. 2 More preferably, from the viewpoint of film forming property, 2000N / mm 2 Less than 800N / mm is preferable. 2 Less than 350N / mm is more preferable. 2 More preferred are: HM B From the viewpoint of shock absorption, the range is 100N / mm 2 More than 150N / mm is preferable. 2 More preferably, from the viewpoint of film forming property, 4000N / mm 2 Less than 2000N / mm is preferable. 2 The following is more preferred: The coating film (C) can be obtained as a cured product obtained by curing the coating composition (I) described later by hydrolysis and condensation. The composition of the polymer nanoparticles (A) usually does not change during the curing process. Therefore, the Martens hardness HM of the polymer nanoparticles (A) in the coating composition (I) measured by the method described in the examples described later can be calculated by the following formula: A The value of is the Martens hardness HM of the polymer nanoparticles (A) in the coating film (C). A The Martens hardness HM of the coating film (C) is in good agreement with A The value of can be determined. The matrix component (B) corresponds to a cured product obtained by curing the matrix raw material component (B') described later by hydrolysis and condensation or the like. Therefore, the Martens hardness HM of the matrix raw material component (B') measured by the method described in the examples described later B' The value of is the Martens hardness HM of the corresponding matrix component (B). BThe Martens hardness HM B The value of can be determined. The above HM A and H.M. B The values ​​of can be adjusted to satisfy the above-mentioned magnitude relationship depending on the structures and composition ratios of the constituent components of the polymer nanoparticles (A) and the matrix raw material component (B') described later, but are not limited to this method.

[0170] [Adhesion force of polymer nanoparticles (A) F A and the adhesive force F of the matrix component (B) B ] The adhesive force F of the polymer nanoparticles (A) in this embodiment A and the adhesive force F of the matrix component (B) B satisfies the relationship of the following formula (2). F A / F B >1 Formula (2) As with formula (1) above, formula (2) also expresses the presence of soft polymer nanoparticles (A) in a hard matrix component (B), and the coating film (C) can be endowed with abrasion resistance not exhibited by conventional coating films due to the three-dimensional gradient in hardness. The reason for this is presumed to be that the soft nanoparticles absorb impact and the hard matrix component suppresses deformation, although this is not intended to be limited to the following. As described above, the adhesive force F of the polymer nanoparticles (A) A and the adhesive force F of the matrix component (B) B is correlated with the hardness of each component, and can be adjusted to satisfy the above-mentioned magnitude relationship by adjusting the structures and composition ratios of the constituent components of the polymer nanoparticles (A) and the matrix raw material component (B') described later, but is not limited to this method.

[0171] [Martens hardness HM of coating film (C)] The Martens hardness HM of the coating (C) is 100N / mm 2The higher the value, the less deformation there is upon impact and the less damage accompanied by destruction is advantageous. From the viewpoint of abrasion resistance, the Martens hardness HM of the coating film (C) is preferably 150 N / mm 2 More preferably, it is 200N / mm 2 From the viewpoint of bending resistance, it is preferably 4000N / mm 2 Less than or equal to 2000N / mm 2 or less, and even more preferably 1500N / mm 2 The method for adjusting the Martens hardness HM of the coating film (C) within the above range includes, but is not limited to, for example, dispersing and dissolving a composition obtained by mixing polymer nanoparticles (A) and a matrix raw material component (B') described later in a solvent, which satisfies a predetermined relationship represented by formula (3) described later, on a substrate, and forming a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, etc. In particular, when the content of the matrix component (B) relative to the total amount of the polymer nanoparticles (A) and the matrix component (B) is increased, the Martens hardness HM of the coating film (C) tends to increase, and when the content of the matrix component (B) is reduced, the Martens hardness HM of the coating film (C) tends to decrease.

[0172] [Haze change in Taber abrasion test] The Taber abrasion test in this embodiment is based on the method measured by the method described in ASTM D1044, and is performed under the conditions of abrasion wheel CS-10F and a load of 500 g. The smaller the haze change, the more excellent the abrasion resistance of the material. If the haze change at 1000 revolutions relative to the haze before the test, i.e., the difference between the haze at 1000 revolutions and the haze before the Taber abrasion test, is 10 or less, it conforms to the standards for automobile windows and can be suitably used as a hard coat coating film for automobile windows, and if it is 2 or less, it conforms to the standards of ANSI / SAE Z.26.1, ECE R43, and JIS R3211 / R3212 and can be suitably used for all automobile window materials. If the difference between the haze at 1000 revolutions and the haze before the Taber abrasion test is 10 or less, it is preferable, if it is 6 or less, and even more preferable if it is 2 or less. Methods for adjusting the amount of haze change within the above range include, but are not limited to, a coating composition prepared by dispersing and dissolving a composition of polymer nanoparticles (A) and a matrix raw material component (B') described later, which satisfies a specific relationship represented by formula (3) described later, in a solvent, and coating the resulting coating composition on a substrate and forming a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, or the like.

[0173] [The difference between the haze at 500 rotations and 10 rotations in the Taber abrasion test (hereinafter also referred to as "ΔA")] ΔA of the coating film (C) indicates the difference between the haze at 500 revolutions and the haze at 10 revolutions in the Taber abrasion test, and the lower ΔA is the better the long-term stain resistance, so it is preferable. That is, from the viewpoint of developing higher stain resistance, ΔA is preferably 10 or less, more preferably 7 or less, and even more preferably 5 or less. Although the detailed reason is unclear, it is presumed that, for example, the lower ΔA is, the less likely the contaminants are to bite into the film, and the better the cleaning ability of the contaminants tends to be. The method for adjusting ΔA of the coating film (C) within the above range is not limited to the following, but for example, a coating composition in which a composition in which polymer nanoparticles (A) and a matrix raw material component (B') described later are mixed and dispersed and dissolved in a solvent, which satisfies a predetermined relationship represented by formula (3) described later, is applied to a substrate, and a coating film is formed by heat treatment, ultraviolet irradiation, infrared irradiation, etc. In particular, examples of the composition of the polymer nanoparticles (A), the composition and blending ratio of the matrix raw material component (B') described below, as well as blending conditions such as the solvent composition, blending order, stirring time, and solids concentration, and film-forming conditions such as the drying temperature, humidity, and drying time in the case of heat treatment, the irradiation intensity, irradiation time, and humidity in the case of ultraviolet irradiation, and the irradiation intensity, irradiation time, and humidity in the case of infrared irradiation.

[0174] [Elastic recovery rate of coating film (C) η IT ] Elastic recovery rate η of coating film (C) IT is the total mechanical work of the cavity W total and the elastic return deformation work of the dent W elast This is the ratio of "W elast / W total Ratio of η IT " is a parameter described as "elastic recovery rate η IT The higher the elastic recovery rate η, the more the coating film can return to its original state when deformed, and the higher its self-repairing ability against deformation. ITis preferably 0.50 or more under the measurement conditions (Vickers square pyramid diamond indenter, load increase condition 2 mN / 20 sec, load decrease condition 2 mN / 20 sec), and within this range, the larger the value, the more preferable. More specifically, the elastic recovery rate η IT is more preferably 0.55 or more, even more preferably 0.60 or more, and even more preferably 0.65 or more. The measurement of the elastic recovery rate of the coating film in this embodiment is not limited to the following, but for example, the surface of the hard coat coating film can be measured by performing an indentation test using a microhardness tester Fischerscope (HM2000S manufactured by Fisher Instruments), an ultra-micro indentation hardness tester (ENT-NEXUS manufactured by Elionix Co., Ltd.), a nanoindenter (iNano, G200 manufactured by Toyo Corporation), a nanoindentation system (TI980 manufactured by Bruker), or the like. Elastic recovery rate η IT Methods for adjusting within the above range include, but are not limited to, a coating composition prepared by dispersing and dissolving a composition of polymer nanoparticles (A) and a matrix raw material component (B') described later, which satisfies a specific relationship represented by formula (3) described later, in a solvent, and coating the resulting coating composition on a substrate and forming a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, or the like.

[0175] [Coating film (C) thickness] In this embodiment, it is preferable to adjust the film thickness appropriately from the viewpoint of further expressing the abrasion resistance of the hard coat film and from the viewpoint of sufficiently ensuring the conformability to the deformation of the substrate.Specifically, the film thickness of the coating film (C) is preferably 1.0 μm or more from the viewpoint of abrasion resistance, more preferably 3.0 μm or more.Furthermore, the film thickness of the coating film (C) is preferably 100.0 μm or less from the viewpoint of weather resistance and conformability to the substrate, more preferably 50.0 μm or less, and even more preferably 20.0 μm or less.

[0176] [Polymer nanoparticles (A)] By using the polymer nanoparticles (A) in this embodiment, it is possible to impart impact absorption properties to the hard coat coating film, and to reduce the amount of haze change in the hard coat coating film in the Taber abrasion test. The shape of the polymer nanoparticles (A) is not particularly limited as long as the particle size is on the order of nm (less than 1 μm). The Martens hardness HM of the polymer nanoparticles (A) is A Regarding the above, it can be controlled within the above-mentioned range depending on the structure and composition ratio of the components of the polymer nanoparticles (A), but is not particularly limited to this method.

[0177] [Average particle size of polymer nanoparticles (A)] The average particle size of the polymer nanoparticles (A) in this embodiment is not particularly limited as long as it is on the order of nm (less than 1 μm), and is determined from the size of particles observed by cross-sectional SEM or dynamic light scattering. The average particle size of the polymer nanoparticles (A) is preferably 10 nm or more from the viewpoint of optical properties, more preferably 15 nm or more, more preferably 20 nm or more, and is preferably 400 nm or less from the viewpoint of transparency, more preferably 200 nm or less, and even more preferably 100 nm or less. The method for measuring the average particle size of the polymer nanoparticles (A) is not limited to the following, but can be, for example, measured by measuring the cumulant particle size using a dynamic light scattering particle size distribution analyzer (product number: ELSZ-1000) manufactured by Otsuka Electronics Co., Ltd. using a water dispersion of the polymer nanoparticles (A).

[0178] [Volume fraction of polymer nanoparticles (A) in coating film (C)] In this embodiment, the volume fraction of the polymer nanoparticles (A) in the coating film (C) is preferably 2% or more from the viewpoint of film-forming property, and preferably 80% or less from the viewpoint of transparency. That is, the volume fraction of the polymer nanoparticles (A) in the coating film (C) is preferably 2% or more and 80% or less, more preferably 3% or more and 70% or less, and even more preferably 5% or more and 45% or less. The volume fraction of the polymer nanoparticles (A) in the coating film (C) can be calculated, for example, from the ratio of the polymer nanoparticles (A) in the entire coating film in the cross-sectional SEM image of the coating film (C) or the component ratio of the polymer nanoparticles (A) in the components constituting the coating film (C).

[0179] [Components of polymer nanoparticles (A)] [Hydrolyzable silicon compounds (a)] The polymer nanoparticles (A) in this embodiment preferably contain a hydrolyzable silicon compound (a). The hydrolyzable silicon compound (a) is not particularly limited as long as it is a silicon compound having hydrolysis properties, its hydrolysis product, or its condensation product.

[0180] From the viewpoint of improving abrasion resistance and weather resistance, the hydrolyzable silicon compound (a) is preferably a compound containing an atomic group represented by the following formula (a-1), or a hydrolysis product or condensation product thereof. -R 1 n1 Six 1 3-n1 (a-1)

[0181] In formula (a-1), R 1 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group, an alkynyl group, or an aryl group; R 1 may have a substituent containing a halogen, a hydroxy group, a mercapto group, an amino group, a (meth)acryloyl group, or an epoxy group, and X 1 represents a hydrolyzable group, and n1 represents an integer of 0 to 2. The hydrolyzable group is not particularly limited as long as it is a group that generates a hydroxyl group upon hydrolysis, and examples of such groups include halogen, an alkoxy group, an acyloxy group, an amino group, a phenoxy group, and an oxime group.

[0182] Specific examples of the compound containing the atomic group represented by formula (a-1) include, but are not limited to, trimethoxysilane, triethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, isobutyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, dec ... Ethoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethoxysilane, diethoxysilane, methyldimethoxysilane, methyldiethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethoxydiphenylsilane, diethoxydiphenylsilane, bis(trimethoxysilyl)methane, bis(triethoxysilyl)methane, bis(triphenoxysilyl)ethane, 1,1-bis(triethoxysilyl) 1,2-bis(triethoxysilyl)ethane, 1,1-bis(triethoxysilyl)propane, 1,2-bis(triethoxysilyl)propane, 1,3-bis(triethoxysilyl)propane, 1,4-bis(triethoxysilyl)butane, 1,5-bis(triethoxysilyl)pentane, 1,1-bis(trimethoxysilyl)ethane, 1,2-bis(trimethoxysilyl)ethane, 1,1-bis(trimethoxysilyl)propane, 1,2-bis(trimethoxysilyl)propane, 1,3-bis(trimeth 1,4-bis(trimethoxysilyl)propane, 1,4-bis(trimethoxysilyl)butane, 1,5-bis(trimethoxysilyl)pentane, 1,3-bis(triphenoxysilyl)propane, 1,4-bis(trimethoxysilyl)benzene, 1,4-bis(triethoxysilyl)benzene, 1,6-bis(trimethoxysilyl)hexane, 1,6-bis(triethoxysilyl)hexane, 1,7-bis(trimethoxysilyl)heptane, 1,7-bis(triethoxysilyl)heptane, 1,8-bis(trimethoxysilyl)octane, 1,8-Bis(triethoxysilyl)octane, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, trifluoropropyltrimethoxysilane, trifluoropropyltriethoxysilane, 3-hydroxypropyltrimethoxysilane, 3-hydroxypropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3 -Methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane Silane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane, 3-trimethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-triethoxysilyl-N-(1,3-Dimethyl-butylidene)propylamine, triacetoxysilane, tris(trichloroacetoxy)silane, tris(trifluoroacetoxy)silane, tris-(trimethoxysilylpropyl)isocyanurate, tris-(triethoxysilylpropyl)isocyanurate, methyltriacetoxysilane, methyltris(trichloroacetoxy)silane, trichlorosilane, tribromosilane, methyltrifluorosilane, tris(methylethylketoxime)silane, phenyltris(methylethylketoxime)silane, bis(methylethylketoxime)silane, methylbis(methylethylketoxime)silane, hexamethyldisilane, hexamethylcyclotrisilazane, bi Bis(dimethylamino)dimethylsilane, bis(diethylamino)dimethylsilane, bis(dimethylamino)methylsilane, bis(diethylamino)methylsilane, 2-[(triethoxysilyl)propyl]dibenzylresorcinol, 2-[(trimethoxysilyl)propyl]dibenzylresorcinol, 2,2,6,6-tetramethyl-4-[3-(triethoxysilyl)propoxy]piperidine, 2,2,6,6-tetramethyl-4-[3-(trimethoxysilyl)propoxy]piperidine, 2-hydroxy-4-[3-(triethoxysilyl)propoxy]benzophenone, 2-hydroxy-4-[3-(trimethoxysilyl)propoxy]benzophenone, and the like.

[0183] From the viewpoint of imparting high hardness to the hard coat film and further improving abrasion resistance, the hydrolyzable silicon compound (a) preferably contains a compound represented by the following formula (a-2), its hydrolysis product, and its condensation product. Six 2 4(a-2) In formula (a-2), X 2 represents a hydrolyzable group. The hydrolyzable group is not particularly limited as long as it is a group that generates a hydroxyl group upon hydrolysis, and examples thereof include halogen, an alkoxy group, an acyloxy group, an amino group, a phenoxy group, and an oxime group.

[0184] Specific examples of the compound represented by formula (a-2) include, but are not limited to, tetramethoxysilane, tetraethoxysilane, tetra(n-propoxy)silane, tetra(i-propoxy)silane, tetra(n-butoxy)silane, tetra(i-butoxy)silane, tetra-sec-butoxysilane, tetra-tert-butoxysilane, tetraacetoxysilane, tetra(trichloroacetoxy)silane, tetra(trifluoroacetoxy)silane, tetrachlorosilane, tetrabromosilane, tetrafluorosilane, tetra(methylethylketoxime)silane, tetramethoxysilane, or tetraethoxysilane. Examples of the hydrolyzed condensates of orchid include those sold under the trade names "M Silicate 51", "Silicate 35", "Silicate 45", "Silicate 40" and "FR-3" by Tama Chemical Co., Ltd.; those sold under the trade names "MS51", "MS56", "MS57" and "MS56S" by Mitsubishi Chemical; and those sold under the trade names "Methyl Silicate 51", "Methyl Silicate 53A", "Ethyl Silicate 40", "Ethyl Silicate 48", "EMS-485", "N-103X", "PX", "PS-169", "PS-162R", "PC-291", "PC-301", "PC-302R", "PC-309" and "EMSi48" by Colcoat Co., Ltd.

[0185] As described above, in this embodiment, it is preferable that the hydrolyzable silicon compound (a) contains at least one selected from the compound containing the atomic group represented by the above formula (a-1), its hydrolysis product and condensation product, and the compound represented by the above formula (a-2), its hydrolysis product and condensation product.

[0186] [Content of hydrolyzable silicon compound (a) in polymer nanoparticles (A)] The content of hydrolyzable silicon compound (a) in this embodiment refers to the solid weight ratio of hydrolyzable silicon compound (a) contained in polymer nanoparticle (A), and the higher the content, the better from the viewpoint of improving wear resistance, weather resistance, and heat resistance, and the content is preferably 50 mass% or more, more preferably 60 mass% or more. The content of hydrolyzable silicon compound (a) in polymer nanoparticle (A) is not limited to the following, but can be measured by, for example, IR analysis, NMR analysis, elemental analysis, etc. of polymer nanoparticle (A).

[0187] [Matrix component (B)] By using the matrix component (B) in this embodiment, it is possible to impart impact absorption properties to the hard coat film, and to reduce the amount of haze change in the hard coat film in the Taber abrasion test. B The amount of the matrix can be controlled within the above-mentioned range by adjusting the structure and composition ratio of the components of the matrix raw material component (B') described later, but is not limited to this method.

[0188] [Components of matrix component (B)] [Hydrolyzable silicon compounds (b)] The matrix component (B) in this embodiment is not particularly limited as long as it is a component in which the polymer nanoparticles (A) can be dispersed. In this embodiment, from the viewpoint of high toughness, it is preferable that the matrix component (B) contains a hydrolyzable silicon compound (b). In this specification, "the matrix component (B) contains a hydrolyzable silicon compound (b)" means that the matrix component (B) contains a polymer having a constitutional unit derived from the hydrolyzable silicon compound (b). The hydrolyzable silicon compound (b) is not particularly limited as long as it is a silicon compound having hydrolysis properties, its hydrolysis product, and its condensation product. The matrix component (B) may contain various components other than the polymer nanoparticles (A) in addition to the above-mentioned polymers. Among them, examples of other polymers that may be contained in addition to the above-mentioned polymers include water-soluble resins such as polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, and polyacrylic acid; acrylic resins such as PMMA, PAN, and polyacrylamide; polymers such as polystyrene, polyurethane, polyamide, polyimide, polyvinylidene chloride, polyester, polycarbonate, polyether, polyethylene, polysulfone, polypropylene, polybutadiene, PTFE, PVDF, and EVA; and copolymers thereof.

[0189] From the viewpoint of further improving the abrasion resistance and weather resistance, the hydrolyzable silicon compound (b) preferably contains one or more compounds selected from the group consisting of compounds containing an atomic group represented by the following formula (b-1), their hydrolysis products and condensation products, and compounds represented by the following formula (b-2), their hydrolysis products and condensation products. -R 2 n2 Six 3 3-n2 (b-1) In formula (b-1), R 2 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group, an alkynyl group, or an aryl group; R 2 may have a substituent containing a halogen, a hydroxy group, a mercapto group, an amino group, a (meth)acryloyl group, or an epoxy group, and X 3 represents a hydrolyzable group, and n2 represents an integer of 0 to 2. The hydrolyzable group is not particularly limited as long as it is a group that generates a hydroxyl group upon hydrolysis, and examples of such groups include a halogen atom, an alkoxy group, an acyloxy group, an amino group, a phenoxy group, and an oxime group. Six 4 4(b-2) In formula (b-2), X 4represents a hydrolyzable group. The hydrolyzable group is not particularly limited as long as it is a group that generates a hydroxyl group upon hydrolysis, and examples of such groups include halogen, an alkoxy group, an acyloxy group, an amino group, a phenoxy group, and an oxime group.

[0190] Specific examples of the compound containing the atomic group represented by general formula (b-1) include, but are not limited to, trimethoxysilane, triethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, isobutyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, decyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, octyltriethoxy ... Silane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethoxysilane, diethoxysilane, methyldimethoxysilane, methyldiethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethoxydiphenylsilane, diethoxydiphenylsilane, bis(trimethoxysilyl)methane, bis(triethoxysilyl)methane, bis(triphenoxysilyl)ethane, 1,1-bis(triethoxysilyl) Ethane, 1,2-bis(triethoxysilyl)ethane, 1,1-bis(triethoxysilyl)propane, 1,2-bis(triethoxysilyl)propane, 1,3-bis(triethoxysilyl)propane, 1,4-bis(triethoxysilyl)butane, 1,5-bis(triethoxysilyl)pentane, 1,1-bis(trimethoxysilyl)ethane, 1,2-bis(trimethoxysilyl)ethane, 1,1-bis(trimethoxysilyl)propane, 1,2-bis(trimethoxysilyl)propane, 1,3-bis(trimethoxysilyl)propane, 1,4-bis(trimethoxysilyl)propane, 1,4-bis(trimethoxysilyl)butane, 1,5-bis(trimethoxysilyl)pentane, 1,3-bis(triphenoxysilyl)propane, 1,4-bis(trimethoxysilyl)benzene, 1,4-bis(triethoxysilyl)benzene, 1,6-bis(trimethoxysilyl)hexane, 1,6-bis(triethoxysilyl)hexane, 1,7-bis(trimethoxysilyl)heptane, 1,7-bis(triethoxysilyl)heptane, 1,8-bis(trimethoxysilyl)octane, 1,8-Bis(triethoxysilyl)octane, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, trifluoropropyltrimethoxysilane, trifluoropropyltriethoxysilane, 3-hydroxypropyltrimethoxysilane, 3-hydroxypropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3 -Methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane Silane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane, 3-trimethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-triethoxysilyl-N-(1,3-Dimethyl-butylidene)propylamine, triacetoxysilane, tris(trichloroacetoxy)silane, tris(trifluoroacetoxy)silane, tris-(trimethoxysilylpropyl)isocyanurate, tris-(triethoxysilylpropyl)isocyanurate, methyltriacetoxysilane, methyltris(trichloroacetoxy)silane, trichlorosilane, tribromosilane, methyltrifluorosilane, tris(methylethylketoxime)silane, phenyltris(methylethylketoxime)silane, bis(methylethylketoxime)silane, methylbis(methylethylketoxime)silane, hexamethyldisilane, hexamethylcyclotrisilazane, bi Bis(dimethylamino)dimethylsilane, bis(diethylamino)dimethylsilane, bis(dimethylamino)methylsilane, bis(diethylamino)methylsilane, 2-[(triethoxysilyl)propyl]dibenzylresorcinol, 2-[(trimethoxysilyl)propyl]dibenzylresorcinol, 2,2,6,6-tetramethyl-4-[3-(triethoxysilyl)propoxy]piperidine, 2,2,6,6-tetramethyl-4-[3-(trimethoxysilyl)propoxy]piperidine, 2-hydroxy-4-[3-(triethoxysilyl)propoxy]benzophenone, 2-hydroxy-4-[3-(trimethoxysilyl)propoxy]benzophenone, and the like.

[0191] Specific examples of the compound represented by formula (b-2) include, but are not limited to, tetramethoxysilane, tetraethoxysilane, tetra(n-propoxy)silane, tetra(i-propoxy)silane, tetra(n-butoxy)silane, tetra(i-butoxy)silane, tetra-sec-butoxysilane, tetra-tert-butoxysilane, tetraacetoxysilane, tetra(trichloroacetoxy)silane, tetra(trifluoroacetoxy)silane, tetrachlorosilane, tetrabromosilane, tetrafluorosilane, tetra(methylethylketoxime)silane, tetramethoxysilane, or tetraethoxysilane. Examples of the hydrolyzed condensates of orchid include those sold under the trade names "M Silicate 51", "Silicate 35", "Silicate 45", "Silicate 40" and "FR-3" by Tama Chemical Co., Ltd.; those sold under the trade names "MS51", "MS56", "MS57" and "MS56S" by Mitsubishi Chemical; and those sold under the trade names "Methyl Silicate 51", "Methyl Silicate 53A", "Ethyl Silicate 40", "Ethyl Silicate 48", "EMS-485", "N-103X", "PX", "PS-169", "PS-162R", "PC-291", "PC-301", "PC-302R", "PC-309" and "EMSi48" by Colcoat Co., Ltd.

[0192] As described above, in this embodiment, it is preferable that the hydrolyzable silicon compound (b) contains at least one selected from the compound containing the atomic group represented by the above formula (b-1), its hydrolysis product and condensation product, and the compound represented by the above formula (b-2), its hydrolysis product and condensation product.

[0193] In this embodiment, the "hydrolyzable silicon compound (a) contained in the polymer nanoparticles (A)" may be the same as or different from the "hydrolyzable silicon compound (b) contained in the matrix component (B)". Even if the two are the same type, they are distinguished by calling the one contained in the polymer nanoparticles (A) the hydrolyzable silicon compound (a) and the one contained in the matrix component (B) the hydrolyzable silicon compound (b).

[0194] [Inorganic oxides (D)] The matrix component (B) in this embodiment contains an inorganic oxide (D). By containing the inorganic oxide (D), not only the hardness of the matrix component (B) is improved and the abrasion resistance is improved, but also the stain resistance of the coating film tends to be improved due to the hydrophilicity of the hydroxyl groups on the particle surface. Furthermore, the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Al, Zn, Ti, Zr, Sb, Mg, Sn, Bi, Co and Cu (hereinafter, also simply referred to as "inorganic component"). By containing the inorganic component in the inorganic oxide (D), weather resistance can be improved without impairing abrasion resistance and durability. In the case of using a commercially available product, examples include, but are not limited to, ultrafine particle material products of cerium oxide, zinc oxide, aluminum oxide, bismuth oxide, cobalt oxide, copper oxide, tin oxide, and titanium oxide manufactured by CIK Nanotech Co., Ltd.; titanium oxide "Tainoc" (trade name), cerium oxide "Needral" (trade name), tin oxide "Ceramece" (trade name), niobium oxide sol, and zirconium oxide sol manufactured by Taki Chemical Co., Ltd. From the viewpoint of improving weather resistance, it is preferable that the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Zn, Ti, and Zr, and it is more preferable that it contains Ce.

[0195] In the present embodiment, the inorganic component in the inorganic oxide (D) preferably contains at least one inorganic oxide (D') selected from the group consisting of Ce, Nb, Zn, Ti and Zr from the viewpoint of balance of abrasion resistance, durability and weather resistance, and the content of the inorganic oxide (D') in the hard coat coating film is not particularly limited, but from the viewpoint of balance of abrasion resistance, durability and weather resistance, it is preferably 1 mass% or more, more preferably 2 mass% or more. Also, from the viewpoint of transparency, it is preferably 50 mass% or less, more preferably 30 mass% or less. Here, the above content can be specified as the total amount of Ce, Nb, Zn, Ti and Zr when the hard coat coating film is 100 mass%.

[0196] Specific examples of the inorganic oxide (D) in this embodiment include, but are not limited to, oxides of aluminum, titanium, zirconium, zinc, cerium, tin, antimony, niobium, magnesium, bismuth, cobalt, copper, etc., as well as oxides of silicon, indium, gallium, germanium, molybdenum, etc., as described above as inorganic components. These may be used alone or as a mixture, regardless of their shape. The inorganic oxide (D) is not particularly limited as long as it contains an inorganic component, but from the viewpoint of interaction with the hydrolyzable silicon compound (b) described above, it is preferable to further contain silica particles, such as dry silica or colloidal silica, and from the viewpoint of dispersibility, it is preferable to further contain colloidal silica as the form of silica particles. When the inorganic oxide (D) contains colloidal silica, it is preferable that it is in the form of an aqueous dispersion, and either acidic or basic can be used.

[0197] [Average particle size of inorganic oxide (D)] In the present embodiment, the average particle diameter of the inorganic oxide (D) is preferably 2 nm or more from the viewpoint of improving the storage stability of the composition of the hard coat coating film, and is preferably 150 nm or less from the viewpoint of improving the transparency. That is, the average particle diameter of the inorganic oxide (D) is preferably 2 nm or more and 150 nm or less, more preferably 2 nm or more and 100 nm or less, and even more preferably 2 nm or more and 50 nm or less. The method for measuring the average particle diameter (D) of the inorganic oxide is not limited to the following, but for example, the water-dispersed colloidal silica is observed at a magnification of 50,000 to 100,000 times using a transmission microscope, and 100 to 200 inorganic oxide particles are photographed, and the average diameter of the inorganic oxide particles can be measured. When the inorganic oxide (D) contains a plurality of inorganic oxides, the average value of the average particle diameters of the individual inorganic oxides is regarded as the average particle diameter of the inorganic oxide (D) in the hard coat coating film or coating composition.

[0198] [Colloidal silica that may be contained in inorganic oxide (D)] The acidic colloidal silica with water as a dispersion medium that is preferably used in this embodiment is not particularly limited, but can be prepared by the sol-gel method or a commercially available product. When preparing by the sol-gel method, reference can be made to Werner Stober et al.; J. Colloid and Interface Sci., 26, 62-69 (1968), Rickey D. Badley et al.; Lang muir 6, 792-801 (1990), Journal of the Color Materials Association, 61 [9] 488-493 (1988), etc. When using commercially available products, examples include Snowtex-O, Snowtex-OS, Snowtex-OXS, Snowtex-O-40, Snowtex-OL, Snowtex-OYL, Snowtex-OUP, Snowtex-PS-SO, Snowtex-PS-MO, Snowtex-AK-XS, Snowtex-AK, Snowtex-AK-L, Snowtex-AK-YL, Snowtex-AK-PS-S (product names, manufactured by Nissan Chemical Industries, Ltd.), Adelite AT-20Q (product name, manufactured by Asahi Denka Kogyo Co., Ltd.), Crebosol 20H12, Crebosol 30CAL25 (product names, manufactured by Clariant Japan Co., Ltd.), and the like.

[0199] In addition, examples of basic colloidal silica include silica stabilized by the addition of alkali metal ions, ammonium ions, and amines, and are not particularly limited. Examples of such basic colloidal silica include, but are not limited to, Snowtex-20, Snowtex-30, Snowtex-XS, Snowtex-50, Snowtex-30L, Snowtex-XL, Snowtex-YL, Snowtex-ZL, Snowtex-UP, Snowtex-ST-PS-S, Snowtex-ST-PS-M, Snowtex-C, Snowtex-CXS, Snowtex-CM, Snowtex-N, Snowtex-NXS, Snowtex-NS, Snowtex-N-4, 0 (trade name, manufactured by Nissan Chemical Industries, Ltd.), Adelite AT-20, Adelite AT-30, Adelite AT-20N, Adelite AT-30N, Adelite AT-20A, Adelite AT-30A, Adelite AT-40, Adelite AT-50 (trade name, manufactured by Asahi Denka Kogyo Co., Ltd.), Crebosol 30R9, Crebosol 30R50, Crebosol 50R50 (trade name, manufactured by Clariant Japan Co., Ltd.), Ludox HS-40, Ludox HS-30, Ludox LS, Ludox AS-30, Ludox SM-AS, Ludox AM, Ludox HSA and Ludox SM (trade name, manufactured by DuPont) are examples of such.

[0200] Furthermore, the colloidal silica having a water-soluble solvent as a dispersion medium is not particularly limited, but examples thereof include MA-ST-M (methanol dispersion type having a particle size of 20 to 25 nm), IPA-ST (isopropyl alcohol dispersion type having a particle size of 10 to 15 nm), EG-ST (ethylene glycol dispersion type having a particle size of 10 to 15 nm), EGST-ZL (ethylene glycol dispersion type having a particle size of 70 to 100 nm), NPC-ST (ethylene glycol monopropyl ether dispersion type having a particle size of 10 to 15 nm), and TOL-ST (toluene dispersion type having a particle size of 10 to 15 nm), all manufactured by Nissan Chemical Industries, Ltd.

[0201] The dry silica particles are not particularly limited, but examples thereof include AEROSIL manufactured by Nippon Aerosil Co., Ltd. and Reolosil manufactured by Tokuyama Corporation.

[0202] Furthermore, these silica particles may contain an inorganic base (sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia, etc.) or an organic base (tetramethylammonium, triethylamine, etc.) as a stabilizer.

[0203] [Shape of inorganic oxide (D)] Furthermore, the shape of the inorganic oxide (D) in this embodiment is not limited to the following, but examples thereof include spherical, angular, polyhedral, elliptical, flat, linear, beaded, and pearl-like shapes, and from the viewpoints of hardness and transparency of the hard coat film, a spherical shape is particularly preferable.

[0204] [Functional group (e)] In this embodiment, the polymer nanoparticles (A) preferably have a functional group (e) that interacts with the matrix component (B) in order to improve the dispersibility of the polymer nanoparticles (A) in the matrix component (B) and improve the wear resistance. The fact that the polymer nanoparticles (A) have a functional group (e) can be confirmed by, for example, IR, GC-MS, pyrolysis GC-MS, LC-MS, GPC, MALDI-MS, TOF-SIMS, TG-DTA, composition analysis by NMR, and analysis by a combination of these.

[0205] Specific examples of the functional group (e) in this embodiment include, but are not limited to, a hydroxyl group, a carboxyl group, an amino group, an amide group, and a functional group consisting of an ether bond. From the viewpoint of interaction, a functional group having a hydrogen bond is preferable, and from the viewpoint of high hydrogen bonding property, an amide group is more preferable, and a secondary amide group and / or a tertiary amide group is even more preferable.

[0206] Examples of compounds containing the functional group (e) and their reaction products include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl vinyl ether or 4-hydroxybutyl vinyl ether, 2-hydroxyethyl allyl ether, (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, 2-dimethylaminoethyl (meth)acrylate, 2-diethylaminoethyl (meth)acrylate, 2-di-n-propylaminoethyl (meth)acrylate, 3-dimethylaminopropyl (meth)acrylate, 4-dimethylaminobutyl (meth)acrylate, N-[2-(meth)acryloyloxy]ethylmorpholine, vinylpyridine, N-vinylcarbazole, N-vinylquinoline, N-methylacrylamide, N-methylmeth ... N-ethylacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N-ethylmethacrylamide, N-methyl-N-ethylacrylamide, N-methyl-N-ethylmethacrylamide, N-isopropylacrylamide, Nn-propylacrylamide, N-isopropylmethacrylamide, Nn-propylmethacrylamide, N-methyl-Nn-propylacrylamide, N-methyl-N-isopropylacrylamide, N-acryloylpyrrolidine, N-methacryloylpyrrolidine, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylhexahydroazepine, N-acryloylmorpholine, N-methacryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, N,N'-methylenebisacrylamide, N,Examples of such an acrylic acid include N'-methylenebismethacrylamide, N-vinylacetamide, diacetone acrylamide, diacetone methacrylamide, N-methylolacrylamide, N-methylolmethacrylamide, Blenmer PE-90, PE-200, PE-350, PME-100, PME-200, PME-400, AE-350 (trade name, manufactured by Nippon Oil & Fats Co., Ltd.), MA-30, MA-50, MA-100, MA-150, RA-1120, RA-2614, RMA-564, RMA-568, RMA-1114, and MPG130-MA (trade name, manufactured by Nippon Nyukazai Co., Ltd.). In this specification, (meth)acrylate is a simple expression for acrylate or methacrylate, and (meth)acrylic acid is a simple expression for acrylic acid or methacrylic acid.

[0207] [Core / shell structure of polymer nanoparticles (A)] The polymer nanoparticle (A) in this embodiment preferably has a core / shell structure having a core layer and one or more shell layers covering the core layer. From the viewpoint of interaction with the matrix component (B) in the outermost layer of the core / shell structure, the polymer nanoparticle (A) preferably has a functional group (e).

[0208] [Other compounds that may be contained in the polymer nanoparticles (A)] The polymer nanoparticles (A) according to the present embodiment may contain the following polymers in order to improve the stability of the particles by providing electrostatic repulsion between the particles. For example, polyurethane-based, polyester-based, poly(meth)acrylate-based, poly(meth)acrylic acid, polyvinyl acetate-based, polybutadiene-based, polyvinyl chloride-based, chlorinated polypropylene-based, polyethylene-based, polystyrene-based polymers, or poly(meth)acrylate-silicone-based, polystyrene-(meth)acrylate-based, and styrene-maleic anhydride-based copolymers may be mentioned.

[0209] Among the polymers that may be contained in the above-mentioned polymer nanoparticles (A), a compound that is particularly excellent in electrostatic repulsion may be a polymer or copolymer of (meth)acrylic acid and (meth)acrylate. Specific examples include, but are not limited to, methyl acrylate, (meth)acrylic acid, methyl methacrylate, butyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl acrylate, n-butyl acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate polymers or copolymers. In this case, in order to further improve the electrostatic repulsion, the (meth)acrylic acid may be partially or completely neutralized with amines such as ammonia, triethylamine, and dimethylethanolamine, or bases such as NaOH and KOH.

[0210] The polymer nanoparticles (A) may also contain an emulsifier. The emulsifier is not particularly limited, and examples thereof include acidic emulsifiers such as alkylbenzenesulfonic acid, alkylsulfonic acid, alkylsulfosuccinic acid, polyoxyethylene alkylsulfuric acid, polyoxyethylene alkylarylsulfuric acid, and polyoxyethylene distyrylphenyl ether sulfonic acid; anionic surfactants such as alkali metal (Li, Na, K, etc.) salts of acidic emulsifiers, ammonium salts of acidic emulsifiers, and fatty acid soaps; cationic surfactants of quaternary ammonium salts, pyridinium salts, and imidazolinium salts, such as alkyltrimethylammonium bromide, alkylpyridinium bromide, and imidazolinium laurate; nonionic surfactants such as polyoxyethylene alkylaryl ether, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene oxypropylene block copolymers, and polyoxyethylene distyrylphenyl ether, and reactive emulsifiers having a radical polymerizable double bond.

[0211] Examples of the reactive emulsifier having a radically polymerizable double bond include, but are not limited to, Eleminol JS-2 (trade name, manufactured by Sanyo Chemical Industries, Ltd.), Latemul S-120, S-180A or S-180 (trade name, manufactured by Kao Corporation), Aqualon HS-10, KH-1025, RN-10, RN-20, RN30, RN50 (trade name, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), Adeka Reasoap SE1025, SR-1025, NE-20, NE-30, NE-40 (trade name, manufactured by Asahi Denka Kogyo Co., Ltd.), ammonium salt of p-styrenesulfonic acid, sodium salt of p-styrenesulfonic acid, potassium salt of p-styrenesulfonic acid, alkylsulfonic acid (meth)acrylate such as 2-sulfoethyl acrylate, methylpropanesulfonic acid (meth)acrylamide, ammonium salt of allylsulfonic acid, sodium salt of allylsulfonic acid, potassium salt of allylsulfonic acid, and the like.

[0212] [Other components that may be included in the coating film (C)] The coating film (C) of this embodiment may contain, as the matrix component (B), a solvent, an emulsifier, a plasticizer, a pigment, a dye, a filler, an antioxidant, a conductive material, an organic ultraviolet absorber, a light stabilizer, a release regulator, a softener, a surfactant, a flame retardant, an antioxidant, and a catalyst, depending on the application. Since high weather resistance is required particularly for outdoor applications, it is preferable to contain an organic ultraviolet absorber and a light stabilizer. Specific examples of organic ultraviolet absorbers and light stabilizers include, but are not limited to, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2,2'-dihydroxy-4-methoxybenzophenone, 2, benzophenone-based ultraviolet absorbers such as 2'-dihydroxy-4,4'-dimethoxybenzophenone (BASF's trade name "UVINUL3049"), 2,2',4,4'-tetrahydroxybenzophenone (BASF's trade name "UVINUL3050"), 4-dodecyloxy-2-hydroxybenzophenone, 5-benzoyl-2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-hydroxy-4-stearyloxybenzophenone, and 4,6-dibenzoylresortinol;2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-octylphenyl)benzotriazole, 2-[2'-hydroxy-3',5'-bis(α,α'-dimethylbenzyl)phenyl] Benzotriazole), methyl-3-[3-tert-butyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]propionate and polyethylene glycol (molecular weight 300) condensation product (BASF product name "TINUVIN 1130"), isooctyl-3-[3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionate (BASF product name "TINUVIN 384"), 2-(3-dodecyl-5-methyl-2-hydroxyphenyl)propionate (BASF product name "TINUVIN 384"), nyl)benzotriazole (trade name "TINUVIN571" manufactured by BASF), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-4'-octoxyphenyl)benzotriazole, 2-[2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole, benzotriazole-based ultraviolet absorbers such as 2,2-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (trade name "TINUVIN 900" manufactured by BASF), TINUVIN 384-2, TINUVIN 326, TINUVIN 327, TINUVIN 109, TINUVIN 970, TINUVIN 328, TINUVIN 171, TINUVIN 970, TINUVIN PS, TINUVIN P, TINUVIN 99-2, and TINVIN 928 (trade names, manufactured by BASF);2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bisbutyloxyphenyl) -1,3,5-triazine (trade name "TINUVIN 460" manufactured by BASF), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (trade name "TINUVIN 479" manufactured by BASF), TINUVIN 400, TINUVIN 405, TINUVIN 477, TINUVIN 1600 (trade names, manufactured by BASF), and other triazine-based ultraviolet absorbers; HOSTAVIN PR25, HOSTAVIN B-CAP, HOSTAVIN VSU (trade names, manufactured by Clariant), and other malonic acid ester-based ultraviolet absorbers; HOSTAVIN 3206 LIQ, HOSTAVIN VSU P, HOSTAVIN 3212 LIQ (trade name, manufactured by Clariant) and other anilide-based ultraviolet absorbers; amyl salicylate, menthyl salicylate, homomenthyl salicylate, octyl salicylate, phenyl salicylate, benzyl salicylate, p-isopropanol phenyl salicylate and other salicylate-based ultraviolet absorbers; ethyl-2-cyano-3,3-diphenylacrylate (trade name "UVINUL3035" manufactured by BASF) cyanoacrylate-based ultraviolet absorbers such as (2-ethylhexyl)-2-cyano-3,3-diphenylacrylate (BASF's trade name "UVINUL3039") and 1,3-bis((2'-cyano-3',3'-diphenylacryloyl)oxy)-2,2-bis-(((2'-cyano-3',3'-diphenylacryloyl)oxy)methyl)propane (BASF's trade name "UVINUL3030");2-hydroxy-4-acryloxybenzophenone, 2-hydroxy-4-methacryloxybenzophenone, 2-hydroxy-5-acryloxybenzophenone, 2-hydroxy-5-methacryloxybenzophenone, 2-hydroxy-4-(acryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-diethoxy)benzophenone, 2-hydroxy-4-(acryloxy-triethoxy)benzophenone, 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole (trade name "RUVA-93" manufactured by Otsuka Chemical Co., Ltd.), 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole (trade name "RUVA-93" manufactured by Otsuka Chemical Co., Ltd.), radical polymerizable ultraviolet absorbers having a radical polymerizable double bond in the molecule, such as 2-(2'-hydroxy-5'-methacrylyloxypropyl-3-tert-butylphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-methacrylyloxypropyl-3-tert-butylphenyl)-5-chloro-2H-benzotriazole, and 3-methacryloyl-2-hydroxypropyl-3-[3'-(2''-benzotriazolyl)-4-hydroxy-5-tert-butyl]phenylpropionate (trade name "CGL-104" manufactured by Ciba-Geigy Japan Ltd.); ultraviolet absorbing polymers, such as UV-G101, UV-G301, UV-G137, UV-G12, and UV-G13 (trade names manufactured by Nippon Shokubai Co., Ltd.);Bis(2,2,6,6-tetramethyl-4-piperidyl)succinate, bis(2,2,6,6-tetramethylpiperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2-butylmalonate, 1-[2-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propynyloxy]ethyl]-4-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propynyloxy]-2,2,6,6-tetramethylpiperidyl hindered amine light stabilizers such as peridine, a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl-1,2,2,6,6-pentamethyl-4-piperidyl-sebacate (BASF's trade name "TINUVIN 292"), bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, TINUVIN 123, TINUVIN 144, TINUVIN 152, TINUVIN 249, TINUVIN 292, and TINUVIN 5100 (BASF's trade names); ,2,6,6-Pentamethyl-4-piperidyl methacrylate, 1,2,2,6,6-Pentamethyl-4-piperidyl acrylate, 2,2,6,6-Tetramethyl-4-piperidyl methacrylate, 2,2,6,6-Tetramethyl-4-piperidyl acrylate, 1,2,2,6,6-Pentamethyl-4-iminopiperidyl methacrylate, 2,2,6,6,-Tetramethyl-4-iminopiperidyl methacrylate, 4-Cyano-2,2,6,6-Tetramethyl-4-piperidyl methacrylate, 4-Cyano-1,2,2,6,6- Examples of such light stabilizers include radically polymerizable hindered amine-based light stabilizers such as pentamethyl-4-piperidyl methacrylate; light-stable polymers such as U-DOUBLE E-133, U-DOUBLE E-135, U-DOUBLE S-2000, U-DOUBLE S-2834, U-DOUBLE S-2840, U-DOUBLE S-2818, and U-DOUBLE S-2860 (trade names, manufactured by Nippon Shokubai Co., Ltd.); and ultraviolet absorbers reactive with silanol groups, isocyanate groups, epoxy groups, semicarbazide groups, and hydrazide groups, which may be used alone or in combination of two or more kinds.

[0213] [Transparency of hard coat film] When the hard coat coating film of this embodiment is used as a transparent material, it is preferable that the hard coat coating film has a transparency that does not adversely affect the appearance of the material or the visibility through the material. The transparency of the hard coat coating film can be evaluated by the total light transmittance maintenance rate obtained by the following formula from the viewpoint of appearance change. In this embodiment, the total light transmittance maintenance rate of the hard coat coating film is preferably 90% or more, more preferably 95% or more from the viewpoint of ensuring natural lighting, and particularly preferably 98% or more from the viewpoint of ensuring visibility through the material. The total light transmittance maintenance rate of the hard coat coating film can be adjusted to the above-mentioned range, for example, by adopting the above-mentioned preferred embodiments as the polymer nanoparticles (A) and the matrix component (B). Total light transmittance maintenance rate of hard coat film (%) = (Total light transmittance of substrate with hard coat film (%) / Total light transmittance of substrate (%)) x 100

[0214] [Stain resistance of hard coat film] When the hard coat coating film of this embodiment is used as a transparent material, it is required that the visibility is not adversely affected when used for a long period of time. That is, in the above-mentioned applications, it is preferable that the hard coat coating film has good stain resistance. The stain resistance here indicates the degree of adhesion of soot and dust when used for a long period of time, and can be evaluated, for example, by attaching JIS test powder 1 (12 types of carbon black) to the coating film after the abrasion test, and by the total light transmittance maintenance rate after the test obtained by the following formula. Total light transmittance retention rate after black carbon test (%) = (total light transmittance after test / total light transmittance before test) x 100 The higher the total light transmittance maintenance rate after the black carbon test, the less black carbon adheres to the film when used for a long period of time, and the film tends to have better stain resistance.

[0215] [Hard coat film moisture resistance] In applications where the hard coat film of the present embodiment is used for a long period of time, it is required to maintain the performance of the hard coat film under the usage environment.For example, in applications as window materials for automobiles, it is assumed that the film will be used under high temperature and high humidity, so it is preferable that the appearance and adhesion do not change after exposure for two weeks at 50°C and 95% RH in accordance with JIS-R3211 and R3222.

[0216] <Substrate with hard coat film> The substrate with a hard coat according to the present embodiment includes a substrate and a hard coat according to the present embodiment formed on one and / or both sides of the substrate. The substrate with a hard coat has a hard coat on at least one and / or both sides of the substrate. The substrate with hard coat coating film of this embodiment is configured as described above, and therefore has high abrasion resistance, durability and weather resistance. The substrate with hard coat coating film of this embodiment exhibits high levels of abrasion resistance, durability and weather resistance, and is useful as a hard coat for, but not limited to, building materials, automobile parts, electronic devices, electrical products, etc., and is particularly preferably used for automobile parts.

[0217] [Base material] The substrate to which the hard coat film of the present embodiment is applied includes, but is not limited to, resin, metal, glass, etc. The shape of the substrate includes, but is not limited to, a plate-like shape, a shape including unevenness, a shape including a curved surface, a hollow shape, a porous shape, and combinations thereof. The substrate may be of any type, and may include, for example, a sheet, a film, a fiber, etc. Among them, a resin is preferable from the viewpoint of hard coat property and moldability. That is, a structure having a substrate containing a resin and the hard coat film of the present embodiment has excellent abrasion resistance, moldability, and contamination resistance. The resin used as the substrate includes, but is not limited to, thermoplastic resin and thermosetting resin. The thermoplastic resin used as the substrate includes, but is not limited to, polyethylene, polypropylene, polystyrene, ABS resin, vinyl chloride resin, methyl methacrylate resin, nylon, fluororesin, polycarbonate, polyester resin, etc. Thermosetting resins used as the substrate include, but are not limited to, phenolic resins, urea resins, melamine resins, unsaturated polyester resins, epoxy resins, silicon resins, silicone rubber, SB rubber, natural rubber, thermosetting elastomers, and the like.

[0218] [Adhesive layer] The substrate with the hard coat coating film according to the present embodiment may further have an adhesive layer between the substrate and the hard coat coating film. The adhesive layer may be a commonly used adhesive layer, and is not particularly limited. Examples of the adhesive layer include thermoplastic resins, thermosetting resins, rubber elastomers, and the like. Among them, acrylic resins, acrylic urethane resins, urethane resins, silicone resins, and the like are preferred. The adhesive layer may also contain any suitable additive as necessary. Examples of the additive include, but are not limited to, crosslinking agents, tackifiers, plasticizers, pigments, dyes, fillers, antioxidants, conductive materials, ultraviolet absorbers, inorganic oxides, light stabilizers, release regulators, softeners, surfactants, flame retardants, and antioxidants. Examples of the crosslinking agent include, but are not limited to, isocyanate-based crosslinking agents, epoxy-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, amine-based crosslinking agents, peroxide-based crosslinking agents, melamine-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, and metal salt-based crosslinking agents.

[0219] [Adhesive emulsion particles (F)] In this embodiment, the adhesive layer preferably contains adhesive emulsion particles (F). The adhesive emulsion particles (F) play a role in imparting flexibility and improving adhesion to the substrate. The adhesive emulsion particles (F) are not particularly limited, but are particles composed of one or more of polyurethane, polyester, poly(meth)acrylate, polyvinyl acetate, polybutadiene, polyvinyl chloride, chlorinated polypropylene, polyethylene, polystyrene, polystyrene-(meth)acrylate copolymers, rosin derivatives, alcohol adducts of styrene-maleic anhydride copolymers, polycarbonyl compounds such as cellulose resins, silicone compounds, etc. In this embodiment, the adhesive emulsion particles (F) are preferably poly(meth)acrylate.

[0220] The adhesive emulsion particle (F) in this embodiment is prepared by any method, but preferably has a structure obtained by polymerizing a vinyl monomer in the presence of water and an emulsifier. When the adhesive emulsion particle (F) thus obtained is included in the adhesive layer, it tends to maintain better adhesion to the substrate.

[0221] The vinyl monomer is not particularly limited, but examples thereof include (meth)acrylic acid esters, aromatic vinyl compounds, and vinyl cyanide compounds, as well as monomers containing functional groups such as carboxyl group-containing vinyl monomers, hydroxyl group-containing vinyl monomers, epoxy group-containing vinyl monomers, carbonyl group-containing vinyl monomers, and vinyl monomers having secondary and / or tertiary amide groups.

[0222] The (meth)acrylic acid ester is not particularly limited, but examples thereof include (meth)acrylic acid alkyl esters having an alkyl moiety with 1 to 50 carbon atoms, and (poly)oxyethylene di(meth)acrylates having 1 to 100 ethylene oxide groups.

[0223] The (meth)acrylic acid alkyl ester is not particularly limited, but examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, cyclohexyl (meth)acrylate, lauryl (meth)acrylate, and dodecyl (meth)acrylate.

[0224] The (poly)oxyethylene di(meth)acrylate is not particularly limited, but examples thereof include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, diethylene glycol methoxy(meth)acrylate, and tetraethylene glycol di(meth)acrylate.

[0225] The aromatic vinyl compound is not particularly limited, but examples thereof include styrene and 4-vinyltoluene.

[0226] The vinyl cyanide compound is not particularly limited, but examples thereof include acrylonitrile and methacrylonitrile.

[0227] The carboxyl group-containing vinyl monomer is not particularly limited, and examples thereof include (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, maleic anhydride, and half esters of dibasic acids such as itaconic acid, maleic acid, and fumaric acid. When using a carboxyl group-containing vinyl monomer, a carboxyl group can be introduced into the adhesive emulsion particles (F) in this embodiment, and the electrostatic repulsion between the particles improves the stability of the emulsion, and resistance to external dispersion destruction such as aggregation during stirring tends to improve. In this case, from the viewpoint of further improving the electrostatic repulsion, the introduced carboxyl group can be partially or completely neutralized with ammonia, amines such as triethylamine and dimethylethanolamine, or bases such as NaOH and KOH.

[0228] The hydroxyl group-containing vinyl monomer is not particularly limited, but examples thereof include hydroxyalkyl esters of (meth)acrylic acid such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; hydroxyalkyl esters of fumaric acid such as di-2-hydroxyethyl fumarate and mono-2-hydroxyethyl monobutyl fumarate; allyl alcohol and (poly)oxyethylene mono(meth)acrylate having 1 to 100 ethylene oxide groups; (poly)oxypropylene mono(meth)acrylate having 1 to 100 propylene oxide groups; and further, "Placcel FM, FA Monomer" (trade name of caprolactone addition monomer manufactured by Daicel Chemical Industries, Ltd.) and other hydroxyalkyl esters of α,β-ethylenically unsaturated carboxylic acids.

[0229] The (poly)oxyethylene (meth)acrylate is not particularly limited, but examples thereof include ethylene glycol (meth)acrylate, ethylene glycol methoxy(meth)acrylate, diethylene glycol (meth)acrylate, diethylene glycol methoxy(meth)acrylate, tetraethylene glycol (meth)acrylate, and tetraethylene glycol methoxy(meth)acrylate.

[0230] The (poly)oxypropylene (meth)acrylate is not particularly limited, but examples thereof include propylene glycol (meth)acrylate, propylene glycol methoxy(meth)acrylate, dipropylene glycol (meth)acrylate, dipropylene glycol methoxy(meth)acrylate, tetrapropylene glycol (meth)acrylate, and tetrapropylene glycol methoxy(meth)acrylate.

[0231] The epoxy group-containing vinyl monomer is not particularly limited, but examples thereof include glycidyl group-containing vinyl monomers, etc. The glycidyl group-containing vinyl monomer is not particularly limited, but examples thereof include glycidyl (meth)acrylate, allyl glycidyl ether, allyl dimethyl glycidyl ether, etc.

[0232] The carbonyl-containing vinyl monomer is not particularly limited, but examples thereof include diacetone acrylamide.

[0233] Specific examples of vinyl monomers other than those mentioned above include, but are not limited to, olefins such as ethylene, propylene, and isobutylene; dienes such as butadiene; haloolefins such as vinyl chloride, vinylidene chloride fluoride, tetrafluoroethylene, and chlorotrifluoroethylene; vinyl carboxylate esters such as vinyl acetate, vinyl propionate, vinyl n-butyrate, vinyl benzoate, vinyl pt-butylbenzoate, vinyl pivalate, vinyl 2-ethylhexanoate, vinyl versatate, and vinyl laurate; isopropenyl carboxylate esters such as isopropenyl acetate and isopropenyl propionate; ethyl vinyl ether; and isobutyl Examples of the vinyl ether include vinyl ethers such as vinyl ether and cyclohexyl vinyl ether, allyl esters such as allyl acetate and allyl benzoate, allyl ethers such as allyl ethyl ether and allyl phenyl ether, as well as 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-(meth)acryloyloxy-1,2,2,6,6-pentamethylpiperidine, perfluoromethyl (meth)acrylate, perfluoropropyl (meth)acrylate, perfluoropropylmethyl (meth)acrylate, vinylpyrrolidone, trimethylolpropane tri(meth)acrylate, allyl (meth)acrylate, and combinations thereof.

[0234] The vinyl monomer having the secondary and / or tertiary amide group is not particularly limited, and examples thereof include N-alkyl or N-alkylene substituted (meth)acrylamides, etc. Specific examples thereof include N-methylacrylamide, N-methylmethacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N-ethylmethacrylamide, N-methyl-N-ethylacrylamide, N-methyl-N-ethylmethacrylamide, N-isopropylacrylamide, Nn-propylacrylamide, N-isopropylmethacrylamide, Nn-propylmethacrylamide, N-methyl-Nn-propylacrylamide, N-methyl-N-iso ... Examples of the monomer units include N-vinyl amide, N-acryloylpyrrolidine, N-methacryloylpyrrolidine, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylhexahydroazepine, N-acryloylmorpholine, N-methacryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, N,N'-methylenebisacrylamide, N,N'-methylenebismethacrylamide, N-vinylacetamide, diacetone acrylamide, diacetone methacrylamide, N-methylolacrylamide, and N-methylol methacrylamide. The silicone compound is not particularly limited, but examples thereof include trimethoxysilane, triethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethoxysilane, diethoxysilane, methyldimethoxysilane, methyldiethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethoxydiphenylsilane, diethoxydiphenylsilane, 3 Examples of hydrolysis and condensation products include 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, tetramethoxysilane, and tetraethoxysilane.

[0235] The adhesive emulsion particles (F) may contain an emulsifier. The emulsifier is not particularly limited, and examples thereof include acidic emulsifiers such as alkylbenzenesulfonic acid, alkylsulfonic acid, alkylsulfosuccinic acid, polyoxyethylene alkylsulfuric acid, polyoxyethylene alkylarylsulfuric acid, and polyoxyethylene distyrylphenyl ether sulfonic acid; anionic surfactants such as alkali metal (Li, Na, K, etc.) salts of acidic emulsifiers, ammonium salts of acidic emulsifiers, and fatty acid soaps; cationic surfactants of quaternary ammonium salts, pyridinium salts, and imidazolinium salts, such as alkyltrimethylammonium bromides, alkylpyridinium bromides, and imidazolinium laurates; nonionic surfactants such as polyoxyethylene alkylaryl ethers, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene oxypropylene block copolymers, and polyoxyethylene distyrylphenyl ethers, and reactive emulsifiers having radical polymerizable double bonds.

[0236] Examples of the reactive emulsifier having a radically polymerizable double bond include, but are not limited to, Eleminol JS-2 (trade name, manufactured by Sanyo Chemical Industries, Ltd.), Latemul S-120, S-180A or S-180 (trade name, manufactured by Kao Corporation), Aqualon HS-10, KH-1025, RN-10, RN-20, RN30, RN50 (trade name, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), Adeka Reasoap SE1025, SR-1025, NE-20, NE-30, NE-40 (trade name, manufactured by Asahi Denka Kogyo Co., Ltd.), ammonium salt of p-styrenesulfonic acid, sodium salt of p-styrenesulfonic acid, potassium salt of p-styrenesulfonic acid, alkylsulfonic acid (meth)acrylate such as 2-sulfoethyl acrylate, methylpropanesulfonic acid (meth)acrylamide, ammonium salt of allylsulfonic acid, sodium salt of allylsulfonic acid, potassium salt of allylsulfonic acid, and the like.

[0237] [Average particle size of adhesive emulsion particles (F)] The average particle size of the adhesive emulsion particles (F) in this embodiment is determined from the size of the particles observed by cross-sectional SEM or dynamic light scattering. The average particle size of the adhesive emulsion particles (F) is preferably 300 nm or less. By adjusting the average particle size of the adhesive emulsion particles (F) to the above range, it is possible to form a coating film with even better adhesion due to an improved contact area with the substrate. In addition, from the viewpoint of improving the transparency of the resulting coating film, the average particle size is more preferably 200 nm or less. The method for measuring the average particle size of the adhesive emulsion particles (F) is not limited to the following, but for example, it is possible to measure the cumulant particle size using a dynamic light scattering particle size distribution analyzer (product number: ELSZ-1000) manufactured by Otsuka Electronics Co., Ltd. using an aqueous dispersion of the adhesive emulsion particles (F).

[0238] [Inorganic oxide (G)] From the viewpoint of improving adhesion through interaction with the hard coat film, the adhesive layer preferably further contains an inorganic oxide (G).

[0239] Specific examples of the inorganic oxide (G) in this embodiment include, but are not limited to, oxides of silicon, aluminum, titanium, zirconium, zinc, cerium, tin, indium, gallium, germanium, antimony, molybdenum, etc. These may be single or mixed. Among the above, the inorganic oxide (G) is preferably silica particles.

[0240] The average particle size of the inorganic oxide (G) in this embodiment is preferably 2 nm or more from the viewpoint of improving the storage stability of the raw material composition of the adhesive layer, and is preferably 150 nm or less from the viewpoint of improving the transparency of the substrate with the hard coat film as a whole. Therefore, the average particle size is preferably 2 nm or more and 100 nm or less, more preferably 2 nm or more and 50 nm or less.

[0241] From the viewpoint of strong interaction with the above-mentioned hydrolyzable silicon compound (b) and adhesion to the hard coat coating film, silica particles such as dry silica and colloidal silica are preferred, although not particularly limited. Colloidal silica is preferred because it can be used in the form of an aqueous dispersion.

[0242] [Colloidal silica preferably used as inorganic oxide (G)] The acidic colloidal silica with water as a dispersion medium that is preferably used in this embodiment is not particularly limited, but can be prepared by the sol-gel method or a commercially available product. When preparing by the sol-gel method, reference can be made to Werner Stober et al.; J. Colloid and Interface Sci., 26, 62-69 (1968), Rickey D. Badley et al.; Lang muir 6, 792-801 (1990), and Journal of the Color Materials Association, 61[9], 488-493 (1988), etc. When using commercially available products, examples include Snowtex-O, Snowtex-OS, Snowtex-OXS, Snowtex-O-40, Snowtex-OL, Snowtex-OYL, Snowtex-OUP, Snowtex-PS-SO, Snowtex-PS-MO, Snowtex-AK-XS, Snowtex-AK, Snowtex-AK-L, Snowtex-AK-YL, Snowtex-AK-PS-S (product names, manufactured by Nissan Chemical Industries, Ltd.), Adelite AT-20Q (product name, manufactured by Asahi Denka Kogyo Co., Ltd.), Crebosol 20H12, Crebosol 30CAL25 (product names, manufactured by Clariant Japan Co., Ltd.), and the like.

[0243] In addition, examples of basic colloidal silica include silica stabilized by the addition of alkali metal ions, ammonium ions, and amines, and are not particularly limited. Examples of such basic colloidal silica include, but are not limited to, Snowtex-20, Snowtex-30, Snowtex-XS, Snowtex-50, Snowtex-30L, Snowtex-XL, Snowtex-YL, Snowtex-ZL, Snowtex-UP, Snowtex-ST-PS-S, Snowtex-ST-PS-M, Snowtex-C, Snowtex-CXS, Snowtex-CM, Snowtex-N, Snowtex-NXS, Snowtex-NS, Snowtex-N-4, 0 (trade name, manufactured by Nissan Chemical Industries, Ltd.), Adelite AT-20, Adelite AT-30, Adelite AT-20N, Adelite AT-30N, Adelite AT-20A, Adelite AT-30A, Adelite AT-40, Adelite AT-50 (trade name, manufactured by Asahi Denka Kogyo Co., Ltd.), Crebosol 30R9, Crebosol 30R50, Crebosol 50R50 (trade name, manufactured by Clariant Japan Co., Ltd.), Ludox HS-40, Ludox HS-30, Ludox LS, Ludox AS-30, Ludox SM-AS, Ludox AM, Ludox HSA and Ludox SM (trade name, manufactured by DuPont) are examples of such.

[0244] Furthermore, the colloidal silica having a water-soluble solvent as a dispersion medium is not particularly limited, but examples thereof include MA-ST-M (methanol dispersion type having a particle size of 20 to 25 nm), IPA-ST (isopropyl alcohol dispersion type having a particle size of 10 to 15 nm), EG-ST (ethylene glycol dispersion type having a particle size of 10 to 15 nm), EGST-ZL (ethylene glycol dispersion type having a particle size of 70 to 100 nm), NPC-ST (ethylene glycol monopropyl ether dispersion type having a particle size of 10 to 15 nm), and TOL-ST (toluene dispersion type having a particle size of 10 to 15 nm), all manufactured by Nissan Chemical Industries, Ltd.

[0245] The dry silica particles are not particularly limited, but examples thereof include AEROSIL manufactured by Nippon Aerosil Co., Ltd. and Reolosil manufactured by Tokuyama Corporation.

[0246] The silica particles may contain an inorganic base (eg, sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia, etc.) or an organic base (eg, tetramethylammonium, triethylamine, etc.) as a stabilizer.

[0247] [Shape of inorganic oxide (G)] Furthermore, the shape of the inorganic oxide (G) in this embodiment is not limited to the following, but examples thereof include spherical, angular, polyhedral, elliptical, flat, linear, beaded, and pearl-like shapes, and from the viewpoints of hardness, transparency, and adhesion of the hard coat film, spherical, pearl-like, and beaded shapes are particularly preferred.

[0248] From the viewpoint of adhesion, the thickness of the adhesive layer is preferably 0.1 μm or more and 100.0 μm or less, and more preferably 0.3 μm or more and 50.0 μm or less.

[0249] The coating film (C) may further have a functional layer on at least one surface thereof, including, but not limited to, an anti-reflection layer, an anti-fouling layer, a polarizing layer, an impact absorbing layer, and the like.

[0250] From the viewpoint of weather resistance, the surface of the substrate having the hard coat film may be silica-treated to form a silica layer, which will be described later.

[0251] [Components that may be included in the adhesive layer] The adhesive layer of the present embodiment may contain a solvent, an emulsifier, a plasticizer, a pigment, a dye, a filler, an anti-aging agent, a conductive material, an ultraviolet absorber, a light stabilizer, a release regulator, a softener, a surfactant, a flame retardant, an antioxidant, and a catalyst depending on the application. Since high weather resistance is required especially for outdoor applications, it is preferable to contain an ultraviolet absorber and a light stabilizer. Specifically, but not limited to, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy - benzophenone-based ultraviolet absorbers such as 4,4'-dimethoxybenzophenone (BASF's trade name "UVINUL3049"), 2,2',4,4'-tetrahydroxybenzophenone (BASF's trade name "UVINUL3050"), 4-dodecyloxy-2-hydroxybenzophenone, 5-benzoyl-2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-hydroxy-4-stearyloxybenzophenone, and 4,6-dibenzoylresortinol;2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-octylphenyl)benzotriazole, 2-[2'-hydroxy-3',5'-bis(α,α'-dimethylbenzyl)phenyl] Benzotriazole), methyl-3-[3-tert-butyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]propionate and polyethylene glycol (molecular weight 300) condensation product (BASF product name "TINUVIN 1130"), isooctyl-3-[3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionate (BASF product name "TINUVIN 384"), 2-(3-dodecyl-5-methyl-2-hydroxyphenyl)propionate (BASF product name "TINUVIN 384"), nyl)benzotriazole (trade name "TINUVIN571" manufactured by BASF), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-4'-octoxyphenyl)benzotriazole, 2-[2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole, benzotriazole-based ultraviolet absorbers such as 2,2-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (trade name "TINUVIN 900" manufactured by BASF), TINUVIN 384-2, TINUVIN 326, TINUVIN 327, TINUVIN 109, TINUVIN 970, TINUVIN 328, TINUVIN 171, TINUVIN 970, TINUVIN PS, TINUVIN P, TINUVIN 99-2, and TINVIN 928 (trade names, manufactured by BASF);2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bisbutyloxyphenyl) -1,3,5-triazine (trade name "TINUVIN 460" manufactured by BASF), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (trade name "TINUVIN 479" manufactured by BASF), TINUVIN 400, TINUVIN 405, TINUVIN 477, TINUVIN 1600 (trade names, manufactured by BASF), and other triazine-based ultraviolet absorbers; HOSTAVIN PR25, HOSTAVIN B-CAP, HOSTAVIN VSU (trade names, manufactured by Clariant), and other malonic acid ester-based ultraviolet absorbers; HOSTAVIN 3206 LIQ, HOSTAVIN VSU P, HOSTAVIN 3212 LIQ (trade name, manufactured by Clariant) and other anilide-based ultraviolet absorbers; amyl salicylate, menthyl salicylate, homomenthyl salicylate, octyl salicylate, phenyl salicylate, benzyl salicylate, p-isopropanol phenyl salicylate and other salicylate-based ultraviolet absorbers; ethyl-2-cyano-3,3-diphenylacrylate (trade name "UVINUL3035" manufactured by BASF) cyanoacrylate-based ultraviolet absorbers such as (2-ethylhexyl)-2-cyano-3,3-diphenylacrylate (BASF's trade name "UVINUL3039") and 1,3-bis((2'-cyano-3',3'-diphenylacryloyl)oxy)-2,2-bis-(((2'-cyano-3',3'-diphenylacryloyl)oxy)methyl)propane (BASF's trade name "UVINUL3030");2-hydroxy-4-acryloxybenzophenone, 2-hydroxy-4-methacryloxybenzophenone, 2-hydroxy-5-acryloxybenzophenone, 2-hydroxy-5-methacryloxybenzophenone, 2-hydroxy-4-(acryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-diethoxy)benzophenone, 2-hydroxy-4-(acryloxy-triethoxy)benzophenone, 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole (trade name "RUVA-93" manufactured by Otsuka Chemical Co., Ltd.), 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole (trade name "RUVA-93" manufactured by Otsuka Chemical Co., Ltd.), radical polymerizable ultraviolet absorbers having a radical polymerizable double bond in the molecule, such as 2-(2'-hydroxy-5'-methacrylyloxypropyl-3-tert-butylphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-methacrylyloxypropyl-3-tert-butylphenyl)-5-chloro-2H-benzotriazole, and 3-methacryloyl-2-hydroxypropyl-3-[3'-(2''-benzotriazolyl)-4-hydroxy-5-tert-butyl]phenylpropionate (trade name "CGL-104" manufactured by Ciba-Geigy Japan Ltd.); ultraviolet absorbing polymers, such as UV-G101, UV-G301, UV-G137, UV-G12, and UV-G13 (trade names manufactured by Nippon Shokubai Co., Ltd.);Bis(2,2,6,6-tetramethyl-4-piperidyl) succinate, bis(2,2,6,6-tetramethylpiperidyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl) 2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2-butylmalonate, 1-[2-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propynyloxy]ethyl]-4-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propynyloxy]-2,2,6,6 - Tetramethylpiperidine, a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl-1,2,2,6,6-pentamethyl-4-piperidyl-sebacate (BASF's trade name "TINUVIN 292"), bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, TINUVIN 123, TINUVIN 144, TINUVIN 152, TINUVIN 249, TINUVIN 292, TINUVIN 5100 (BASF's trade names), etc. Daled amine light stabilizers; 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, 1,2,2,6,6-pentamethyl-4-piperidyl acrylate, 2,2,6,6-tetramethyl-4-piperidyl methacrylate, 2,2,6,6-tetramethyl-4-piperidyl acrylate, 1,2,2,6,6-pentamethyl-4-iminopiperidyl methacrylate, 2,2,6,6-tetramethyl-4-iminopiperidyl methacrylate, 4-cyano-2,2,6,6-tetramethyl-4-piperidyl radically polymerizable hindered amine-based light stabilizers such as methacrylate and 4-cyano-1,2,2,6,6-pentamethyl-4-piperidyl methacrylate; light-stable polymers such as U-DOUBLE E-133, U-DOUBLE E-135, U-DOUBLE S-2000, U-DOUBLE S-2834, U-DOUBLE S-2840, U-DOUBLE S-2818, and U-DOUBLE S-2860 (trade names, manufactured by Nippon Shokubai Co., Ltd.); ultraviolet absorbers reactive with silanol groups, isocyanate groups, epoxy groups, semicarbazide groups, and hydrazide groups;Examples of the inorganic ultraviolet absorbents include cerium oxide, niobium oxide, aluminum oxide, zinc oxide, titanium oxide, zirconium oxide, antimony oxide, magnesium oxide, tin oxide, bismuth oxide, cobalt oxide, and copper oxide, and these may be used alone or in combination of two or more kinds.

[0252] <Paint composition> The coating film (C) of this embodiment can be obtained, for example, by using the following coating composition (I). The coating composition (I) is a coating composition containing polymer nanoparticles (A) and a matrix raw material component (B'), and the elastic recovery rate η of the polymer nanoparticles (A) measured by an indentation test in accordance with ISO14577-1 is ITA is 0.30 or more and 0.90 or less, and the Martens hardness HM A and the Martens hardness HM of the matrix raw material component (B'). B' But, HM B' / HM A >1, the matrix raw material component (B') contains an inorganic oxide (D), and the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Al, Zn, Ti, Zr, Sb, Mg, Sn, Bi, Co and Cu. Because of this constitution, the coating composition (I) exhibits high abrasion resistance, durability and weather resistance.

[0253] [Hardness HM of polymer nanoparticles (A) A and the hardness HM of the matrix raw material component (B') B ] In the coating composition (I), the Martens hardness HM of the polymer nanoparticles (A) A and the Martens hardness HM of the matrix raw material component (B') B' satisfies the relationship of the following formula (3). HM B' / HM A >1 Formula (3) As described above, the above relationship is satisfied in the coating composition (I), and therefore, in the coating film (C) obtained by using the coating composition (I), the Martens hardness HMA and the Martens hardness HM of the matrix raw material component (B') B' The Martens hardness of each of the coating compositions (I) can be measured, for example, by separating the polymer nanoparticles (A) and the matrix raw material component (B') by an operation such as centrifugation or ultrafiltration, and measuring each of the separated components based on the method described in the examples below. The above HM A and H.M. B The values ​​of can be adjusted to satisfy the above-mentioned magnitude relationship depending on the structures and composition ratios of the constituent components of the polymer nanoparticles (A) and the matrix raw material component (B'), but are not limited to this method.

[0254] [Elastic recovery η of polymer nanoparticles (A) ITA ] Elastic recovery rate η of the polymer nanoparticles (A) in this embodiment ITA is W in ISO14577-1 elast / W total Ratio of η IT The parameter described as the total mechanical work of the indentation W was measured on the coating of the deposited polymeric nanoparticles (A). total and the elastic return deformation work of the dent W elast It is expressed as the ratio of elastic recovery η ITA The higher the elastic recovery rate η of the polymer nanoparticles (A), the more the coating film can return to its original state when it is subjected to an impact, and the higher the self-repairing ability against the impact. ITA is preferably 0.30 or more under the measurement conditions (Vickers square pyramid diamond indenter, load increase condition 2mN / 20sec, load decrease condition 2mN / 20sec), and η ITA The elastic recovery rate η of the polymer nanoparticles (A) is preferably 0.90 or less. ITAis more preferably 0.50 or more, and even more preferably 0.60 or more. The measurement of the elastic recovery rate of the polymer nanoparticles (A) is not limited to the following, but for example, the polymer nanoparticles (A) and the matrix raw material component (B') are separated by an operation such as centrifugation or ultrafiltration, and the separated polymer nanoparticles (A) are dispersed in a solvent to obtain a composition, which is then coated and dried to form a coating film. The coating film can be measured using a microhardness tester Fischerscope (HM2000S manufactured by Fisher Instruments), an ultra-microindentation hardness tester (ENT-NEXUS manufactured by Elionix Co., Ltd.), a nanoindenter (iNano, G200 manufactured by Toyo Corporation), a nanoindentation system (TI980 manufactured by Bruker), or the like. Elastic recovery rate η ITA The method for adjusting to within the above range is not limited to the following, but examples thereof include adjusting the structure and composition ratio of the components constituting the polymer nanoparticles (A). The coating film (C) can be obtained as a cured product obtained by curing the coating composition (I) by hydrolysis and condensation or the like. The composition of the polymer nanoparticles (A) usually does not change during the curing process. Therefore, the elastic recovery η of the polymer nanoparticles (A) in the coating composition (I) measured by the method described in the examples below. ITA The value of is the elastic recovery η of the polymer nanoparticles (A) in the coating film (C). ITA The elastic recovery rate η of the coating film (C) is in good agreement with ITA The value of can be determined.

[0255] [Solvent (H)] The coating composition (I) in this embodiment preferably contains a solvent (H). The solvent (H) that can be used is not particularly limited, and a general solvent can be used. Examples of the solvent include, but are not limited to, water; ethylene glycol, butyl cellosolve, isopropanol, n-butanol, 2-butanol, ethanol, methanol, denatured ethanol, 2-methoxy-1-propanol, 1-methoxy-2-propanol, diacetone alcohol, glycerin, monoalkyl monoglyceryl ether, propylene glycol monomethyl ether, diethylene glycol monobutyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monobutyl ether, diethylene glycol mono Examples of the solvent include alcohols such as phenyl ether and tetraethylene glycol monophenyl ether; aromatic hydrocarbons such as toluene and xylene; aliphatic hydrocarbons such as hexane, cyclohexane, and heptane; esters such as ethyl acetate and n-butyl acetate; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ethers such as tetrahydrofuran and dioxane; amides such as dimethylacetamide and dimethylformamide; halogen compounds such as chloroform, methylene chloride, and carbon tetrachloride; dimethylsulfoxide, and nitrobenzene; and the like. These may be used alone or in combination of two or more. Among these, from the viewpoint of reducing the environmental load when removing the solvent, it is particularly preferable to include water and alcohols.

[0256] The components, size, composition ratio, etc. of the polymer nanoparticles (A) contained in the coating composition (I) will be explained below. Details of points not mentioned below are as described above for the polymer nanoparticles (A) contained in the coating film (C). In addition, the matrix raw material component (B') contained in the coating composition (I) is cured by hydrolysis condensation or the like in the process of obtaining the coating film (C). That is, the matrix raw material component (B') contained in the coating composition (I) is in a relationship where it becomes the corresponding matrix component (B) in the resulting coating film (C). The components, size, composition ratio, etc. of the matrix raw material component (B') are also explained below, but details of points not mentioned below are as described above for the matrix component (B) contained in the coating film (C).

[0257] In the coating composition (I), the polymer nanoparticles (A) preferably contain the hydrolyzable silicon compound (a) described above, and the matrix raw material component (B') preferably contains the hydrolyzable silicon compound (b) described above. In addition, the hydrolyzable silicon compound (a) in the coating composition (I) preferably contains one or more selected from the compounds containing the atomic group represented by the above formula (a-1), their hydrolysis products and condensates, and the compounds represented by the above formula (a-2), their hydrolysis products and condensates. Similarly, the hydrolyzable silicon compound (b) in the coating composition (I) preferably contains one or more selected from the compounds containing the atomic group represented by the above formula (b-1), their hydrolysis products and condensates, and the compounds represented by the above formula (b-2), their hydrolysis products and condensates. Details of the hydrolyzable silicon compounds (a) and (b) in the coating composition (I) are as described above for the polymer nanoparticles (A) and matrix component (B) contained in the coating film (C).

[0258] [Content of hydrolyzable silicon compound (a) in polymer nanoparticles (A)] In the coating composition (I), the content of the hydrolyzable silicon compound (a) refers to the solid weight ratio of the hydrolyzable silicon compound (a) contained in the polymer nanoparticle (A), and the higher the content, the better the abrasion resistance, weather resistance, and heat resistance are improved. The content is preferably 50% by mass or more, more preferably 60% by mass or more. The content of the hydrolyzable silicon compound (a) in the polymer nanoparticle (A) can be measured, for example, by IR analysis, NMR analysis, elemental analysis, etc. of the polymer nanoparticle (A), but is not limited to the following.

[0259] [Functional group (e)] In the coating composition (I), the polymer nanoparticles (A) preferably have a functional group (e) that interacts with the matrix raw material component (B'). When the polymer nanoparticles (A) have a functional group (e), the matrix raw material component (B') tends to be easily adsorbed on the surface of the polymer nanoparticles (A) and tends to be stabilized as a protective colloid, and as a result, the storage stability of the coating composition (I) tends to be improved. Furthermore, when the polymer nanoparticles (A) have a functional group (e), the interaction between the polymer nanoparticles (A) and the matrix raw material component (B') becomes stronger, which increases the viscosity of the coating composition (I) relative to the solid content concentration, and tends to suppress sagging when coating a complex shape, and as a result, the coating film (C) tends to have a uniform thickness. The fact that the polymer nanoparticles (A) have a functional group (e) can be confirmed by, for example, composition analysis using IR, GC-MS, pyrolysis GC-MS, LC-MS, GPC, MALDI-MS, TOF-SIMS, TG-DTA, NMR, and combinations thereof.

[0260] Specific examples of the functional group (e) in this embodiment include, but are not limited to, a hydroxyl group, a carboxyl group, an amino group, an amide group, and a functional group consisting of an ether bond. From the viewpoint of interaction, a functional group having a hydrogen bond is preferable, and from the viewpoint of high hydrogen bonding property, an amide group is more preferable, and a secondary amide group and / or a tertiary amide group is even more preferable.

[0261] Examples of compounds containing the functional group (e) and their reaction products include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl vinyl ether or 4-hydroxybutyl vinyl ether, 2-hydroxyethyl allyl ether, (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, 2-dimethylaminoethyl (meth)acrylate, 2-diethylaminoethyl (meth)acrylate, 2-di-n-propylaminoethyl (meth)acrylate, 3-dimethylaminopropyl (meth)acrylate, 4-dimethylaminobutyl (meth)acrylate, N-[2-(meth)acryloyloxy]ethylmorpholine, vinylpyridine, N-vinylcarbazole, N-vinylquinoline, N-methylacrylamide, N-methylmeth ... N-ethylacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N-ethylmethacrylamide, N-methyl-N-ethylacrylamide, N-methyl-N-ethylmethacrylamide, N-isopropylacrylamide, Nn-propylacrylamide, N-isopropylmethacrylamide, Nn-propylmethacrylamide, N-methyl-Nn-propylacrylamide, N-methyl-N-isopropylacrylamide, N-acryloylpyrrolidine, N-methacryloylpyrrolidine, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylhexahydroazepine, N-acryloylmorpholine, N-methacryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, N,N'-methylenebisacrylamide, N,Examples of such an acrylic acid include N'-methylenebismethacrylamide, N-vinylacetamide, diacetone acrylamide, diacetone methacrylamide, N-methylolacrylamide, N-methylolmethacrylamide, Blenmer PE-90, PE-200, PE-350, PME-100, PME-200, PME-400, AE-350 (trade name, manufactured by Nippon Oil & Fats Co., Ltd.), MA-30, MA-50, MA-100, MA-150, RA-1120, RA-2614, RMA-564, RMA-568, RMA-1114, and MPG130-MA (trade name, manufactured by Nippon Nyukazai Co., Ltd.). In this specification, (meth)acrylate is a simple expression for acrylate or methacrylate, and (meth)acrylic acid is a simple expression for acrylic acid or methacrylic acid.

[0262] [Elastic recovery rate η of matrix raw material component (B') ITB' and elastic recovery rate η of matrix component (B) ITB ] In the coating composition (I), the elastic recovery rate η of the matrix raw material component (B') ITB' is defined as "W elast / W total Ratio of η IT The coating of the matrix raw material component (B') formed was measured using the parameters described as "total mechanical work W total and the elastic return deformation work of the dent W elast It is expressed as the ratio of elastic recovery η ITB' The higher the elastic recovery rate η of the matrix raw material component (B'), the more the coating film can return to its original state when it is subjected to an impact, and the higher the self-repairing ability against the impact. ITB' is preferably 0.60 or more, more preferably 0.65 or more, under the measurement conditions (Vickers square pyramid diamond indenter, load increase condition 2mN / 20sec, load decrease condition 2mN / 20sec). In addition, from the viewpoint of being able to follow the deformation of the substrate and component (A) when forming a coating film, η ITB'is preferably 0.95 or less. The elastic recovery rate of the matrix raw material component (B') can be measured, but is not limited to the following, by, for example, separating the polymer nanoparticles (A) and the matrix raw material component (B') by an operation such as centrifugation, dissolving the separated matrix raw material component (B') in a solvent, coating the composition, and drying the coating film to form a film. The film can be measured using a microhardness tester Fischerscope (HM2000S manufactured by Fisher Instruments), a super-microindentation hardness tester (ENT-NEXUS manufactured by Elionix Co., Ltd.), a nanoindenter (iNano, G200 manufactured by Toyo Corporation), a nanoindentation system (TI980 manufactured by Bruker), or the like. As described above, the matrix component (B) is a cured product obtained by curing the matrix raw material component (B') through hydrolysis and condensation. Therefore, the elastic recovery rate η of the matrix raw material component (B') measured by the method described in the examples described later is ITB' The value of the elastic recovery η of the corresponding matrix component (B) ITB The elastic recovery η ITB That is, the elastic recovery rate η of the matrix component (B) in this embodiment can be determined. ITB is preferably 0.60 or more, more preferably 0.65 or more. From the viewpoint of being able to follow the deformation of the substrate and component (A) when forming a coating film, η ITB is preferably 0.95 or less. Elastic recovery rate η ITB' and elastic recovery η ITB The method for adjusting to within the above range is not limited to the following, but examples thereof include adjusting the structure and composition ratio of the components constituting the matrix raw material component (B').

[0263] In the coating composition (I), the "hydrolyzable silicon compound (a) contained in the polymer nanoparticles (A)" may be the same as or different from the "hydrolyzable silicon compound (b) contained in the matrix raw material component (B')". Even if the two are the same type, they are distinguished by calling the one contained in the polymer nanoparticles (A) the hydrolyzable silicon compound (a) and the one contained in the matrix raw material component (B') the hydrolyzable silicon compound (b).

[0264] [Inorganic oxides (D)] In the coating composition (I), the matrix raw material component (B') contains an inorganic oxide (D). By containing the inorganic oxide (D), not only the hardness of the matrix raw material component (B') is improved and the abrasion resistance is improved, but also the contamination resistance of the coating film tends to be improved due to the hydrophilicity of the hydroxyl groups on the particle surface. Furthermore, the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Al, Zn, Ti, Zr, Sb, Mg, Sn, Bi, Co and Cu. By containing the inorganic component in the inorganic oxide (D), it is possible to improve the weather resistance without impairing the abrasion resistance and durability. From the viewpoint of improving the weather resistance, it is preferable that the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Zn, Ti and Zr, and it is more preferable that it contains Ce.

[0265] In the coating composition (I), the inorganic component in the inorganic oxide (D) preferably contains at least one inorganic oxide (D') selected from the group consisting of Ce, Nb, Zn, Ti and Zr from the viewpoint of balance of abrasion resistance, durability and weather resistance, and the content of the inorganic oxide (D') in the coating composition is not particularly limited, but is preferably 1% by mass or more, more preferably 2% by mass or more, from the viewpoint of balance of abrasion resistance, durability and weather resistance, and is preferably 50% by mass or less, more preferably 30% by mass or less, from the viewpoint of transparency. Here, the above content can be specified as the total amount of Ce, Nb, Zn, Ti and Zr when the solid content of the coating composition is 100% by mass.

[0266] The inorganic oxide (D) in the coating composition (I) is not particularly limited as long as it contains an inorganic component. That is, the inorganic oxide (D) in the coating composition (I) may be a single substance or a mixture, regardless of the shape. From the viewpoint of the interaction with the hydrolyzable silicon compound (b) described above, it is preferable to further contain silica particles, and from the viewpoint of dispersibility, it is preferable to further contain colloidal silica as the form of silica particles. When the inorganic oxide (D) contains colloidal silica, it is preferable that it is in the form of an aqueous dispersion, and either acidic or basic can be used.

[0267] The average particle size of the inorganic oxide (D) in the coating composition (I) is preferably 2 nm or more from the viewpoint of good storage stability of the coating composition (I), and is preferably 150 nm or less from the viewpoint of good transparency. That is, the average particle size is preferably 2 nm or more and 150 nm or less, more preferably 2 nm or more and 100 nm or less, and even more preferably 2 nm or more and 50 nm or less. The method for measuring the average particle size of the inorganic oxide (D) in the coating composition (I) is as described above for the inorganic oxide (D) contained in the coating film (C).

[0268] Other characteristics of the inorganic oxide (D) in the coating composition (I) are as described above for the inorganic oxide (D) contained in the coating film (C).

[0269] [Volume fraction of polymer nanoparticles (A) relative to the total volume of polymer nanoparticles (A) and matrix raw material component (B')] In the coating composition (I), the volume fraction of the polymer nanoparticles (A) relative to the total of the polymer nanoparticles (A) and the matrix raw material component (B') is preferably 2% or more from the viewpoint of film-forming properties, and is preferably 80% or less from the viewpoint of the transparency of the formed coating film. That is, the volume fraction of the polymer nanoparticles (A) in the coating composition (I) is preferably 2% or more and 80% or less, more preferably 3% or more and 70% or less, and even more preferably 5% or more and 45% or less. The volume fraction of the polymer nanoparticles (A) in the coating composition (I) can be calculated, for example, from the ratio of the polymer nanoparticles (A) in the entire coating film in the cross-sectional SEM image after forming the coating film (C) or the component ratio of the polymer nanoparticles (A) in the components constituting the coating composition (I).

[0270] [Core / shell structure of polymer nanoparticles (A)] In the coating composition (I), the polymer nanoparticles (A) preferably have a core / shell structure with a core layer and one or more shell layers covering the core layer. The polymer nanoparticles (A) preferably have the above-mentioned functional group (e) from the viewpoint of the interaction with the matrix raw material component (B') in the outermost layer of the core / shell structure. The fact that the polymer nanoparticles (A) have a core / shell structure can be confirmed, for example, by a transmission electron microscope image of the cross section of the coating film.

[0271] [Other components that may be included in the coating composition (I)] From the viewpoint of further improving the coating properties of the coating composition (I), the coating composition (I) may contain, in addition to the above-mentioned components as the matrix raw material component (B'), thickeners, leveling agents, thixotropic agents, defoamers, freeze stabilizers, dispersants, wetting agents, rheology control agents, film-forming aids, rust inhibitors, plasticizers, lubricants, preservatives, antifungal agents, antistatic agents, antistatic agents, etc., as necessary. From the viewpoint of improving the film-forming properties, it is preferable to use wetting agents and film-forming aids, and specific examples thereof include, but are not limited to, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, ethylene glycol mono-2-ethylhexyl ether, 2,2,4-trimethyl-1,3-butanediol isobutyrate, diisopropyl glutarate, propylene glycol-n-butyl ether, dipropylene glycol-n-butyl ether, tripropylene glycol-n-butyl ether, dipropylene glycol methyl ether, tripropylene glycol methyl ether, Megafac F-443, F-444, F-445, F-470, F-471, F-472SF, F-474, F-475, F-477, F-479, F-480SF, F-482, F-483, F-489, F-172D, F-178K (trade names, manufactured by DIC Corporation), SN Wet 366, SN Wet 980, SN Wet L, SN Wet S, SN Wet 125, SN Wet 126, SN Wet 970 (trade names, manufactured by San Nopco Co., Ltd.), etc. These compounds may be used alone or in combination of two or more kinds.

[0272] [catalyst] The coating composition (I) may contain a catalyst as the matrix raw material component (B'). When the coating composition (I) contains a catalyst that promotes the reaction between reactive groups, it is preferable in that unreactive groups are less likely to remain in the coating film, and the hardness is increased, and not only the abrasion resistance is improved, but also the weather resistance is improved. The catalyst is not particularly limited, but it is preferable that it is dissolved or dispersed when obtaining a hard coat coating film. Such catalysts are not particularly limited, but for example, organic acids, inorganic acids, organic bases, inorganic bases, metal alkoxides, metal chelates, etc. can be mentioned, and these catalysts may be used alone or in combination of two or more kinds.

[0273] [Properties of coating composition (I)] From the viewpoint of coatability, the coating composition (I) has a solids concentration of preferably 0.01 to 60 mass%, more preferably 1 to 40 mass%, and from the viewpoint of coatability, the viscosity of the coating composition (I) at 20°C is preferably 0.1 to 100,000 mPa s, more preferably 1 to 10,000 mPa s.

[0274] <Hard coat coating method> The method for producing the hard coat coating film and the substrate with the hard coat coating film of this embodiment is not particularly limited, but for example, a coating composition (I) obtained by dispersing and dissolving polymer nanoparticles (A), matrix raw material component (B'), inorganic oxide (D), and other components as appropriate in a solvent is applied to the substrate, and the coating film is formed by heat treatment, ultraviolet irradiation, infrared irradiation, etc. Furthermore, the coating method includes, but is not limited to, spray spraying, flow coating, brush coating, dip coating, spin coating, screen printing, casting, gravure printing, flexographic printing, etc. The applied coating composition (I) can be formed into a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, etc., preferably at room temperature to 250 ° C, more preferably at 40 ° C to 150 ° C.

[0275] [Surface treatment] The hard coat coating film or the substrate with the hard coat coating film of this embodiment may be silica-processed to form a silica layer from the viewpoint of weather resistance. The method of forming the silica layer is not particularly limited, but specific examples include silica processing by PECVD in which silicone or silazane is vapor-deposited / cured, and silica processing technology in which the surface is modified to silica by irradiating 155 nm ultraviolet light. In particular, surface processing by PECVD is preferred because it can create a layer that is difficult for oxygen and water vapor to pass through without deteriorating the surface. Silicones or silazanes that can be used for PECVD are not limited to the following, but specific examples include octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, decamethylcyclopentasiloxane, hexamethyldisiloxane, vinylmethysilane, vinylmethoxysilane, dimethyldimethoxysilane, TEOS, tetramethyldisiloxane, tetramethyltetravinylcyclotetrasiloxane, hexamethyldisilazane, and the like, and these may be used alone or in combination of two or more kinds.

[0276] <Applications of hard coat films and substrates with hard coat films> The hard coat film and the substrate with the hard coat film of the present embodiment have excellent abrasion resistance and durability. Therefore, the applications of the hard coat film and the substrate with the hard coat film are not particularly limited, but may be, for example, building materials, vehicle members, electronic devices, electrical products, etc. Examples of building material applications include, but are not limited to, window glass for construction machinery, window glass for buildings, houses, greenhouses, etc., roofs for garages and arcades, lighting fixtures such as lights and traffic lights, wallpaper covering materials, signs, sanitary products such as bathtubs and washbasins, building materials for kitchens, exterior wall materials, flooring materials, cork materials, tiles, cushion flooring, and interior flooring materials such as linoleum. Examples of vehicle members include, but are not limited to, parts used in automobiles, aircraft, and trains. Specific examples include glass for front, rear, front door, rear door, rear quarter, sunroof, etc., exterior members such as front bumpers, rear bumpers, spoilers, door mirrors, front grilles, emblem covers, and bodies, interior members such as center panels, door panels, instrument panels, and center consoles, lamp members such as headlamps and rear lamps, lens members for vehicle-mounted cameras, lighting covers, decorative films, and various glass substitute members. Preferred examples of electronic devices and electrical products include, but are not limited to, mobile phones, personal digital assistants, personal computers, portable game consoles, office automation equipment, solar cells, flat panel displays, touch panels, optical discs such as DVDs and Blu-ray discs, optical components such as polarizing plates, optical filters, lenses, prisms, and optical fibers, and optical films such as anti-reflection films, alignment films, polarizing films, and retardation films. The clear coating agent, substrate with a clear coating film, and laminate of the present embodiment can be applied to various fields such as machine parts, agricultural materials, fishing materials, transport containers, packaging containers, toys, and miscellaneous goods in addition to the above.

[0277] <Window materials> The window material of this embodiment (hereinafter also referred to as "window material (J)") is a window material having a polycarbonate resin and a coating film disposed on the polycarbonate resin, the coating film containing polymer nanoparticles (A) and a matrix component (B), the polymer nanoparticles (A) containing a hydrolyzable silicon compound (a), the matrix component (B) containing a hydrolyzable silicon compound (b), and the Martens hardness HM J But 100N / mm 2 More than 4000N / mm 2 The elastic recovery η of the window material is less than or equal to 1.0%, as measured by an indentation test in accordance with ISO 14577-1. ITJis 0.50 or more, the matrix component (B) contains an inorganic oxide (D), and the inorganic oxide (D) contains at least one inorganic component selected from the group consisting of Ce, Nb, Al, Zn, Ti, Zr, Sb, Mg, Sn, Bi, Co and Cu. Because of this configuration, the window material (J) has high abrasion resistance, durability and weather resistance. Since the window material (J) exhibits high levels of abrasion resistance, durability and weather resistance, it is preferable to use it as, for example, a window material for an automobile, although it is not limited to the following.

[0278] Hereinafter, the window material (J) may be described with reference to the constituent components of the polymer nanoparticles (A) and matrix component (B) contained in the window material (J); however, details of the constituent components are as described above for the polymer nanoparticles (A) and matrix component (B) contained in the coating film (C).

[0279] In the window material (J), the polymer nanoparticles (A) are preferably dispersed in the matrix component (B). Such a dispersed state can be confirmed by cross-sectional SEM observation of the coating film.

[0280] In the window material (J), the polymer nanoparticles (A) contain the hydrolyzable silicon compound (a) described above, and the matrix component (B) contains the hydrolyzable silicon compound (b) described above. The hydrolyzable silicon compound (a) in the window material (J) is preferably one or more selected from the compounds containing the atomic group represented by the above formula (a-1), their hydrolysis products and condensates, and the compounds represented by the above formula (a-2), their hydrolysis products and condensates. Similarly, the hydrolyzable silicon compound (b) in the window material (J) is preferably one or more selected from the compounds containing the atomic group represented by the above formula (b-1), their hydrolysis products and condensates, and the compounds represented by the above formula (b-2), their hydrolysis products and condensates. Details of the hydrolyzable silicon compounds (a) and (b) in the window material (J) are as described above for the polymer nanoparticles (A) and matrix component (B) contained in the coating film (C).

[0281] [Martens hardness HM of window material (J) J ] Martens hardness HM of window material (J) J From the viewpoint of wear resistance, it is preferably 150N / mm 2 More preferably, it is 200N / mm 2 From the viewpoint of bending resistance, it is preferably 4000N / mm 2 Less than or equal to 2000N / mm 2 or less, and even more preferably 1500N / mm 2 The Martens hardness HM of the window material (J) is as follows: J Methods for adjusting to within the above range include, but are not limited to, a coating composition prepared by dispersing and dissolving in a solvent a composition obtained by mixing polymer nanoparticles (A) and a matrix raw material component (B') that satisfies the predetermined relationship represented by the above formula (3) on a substrate, and forming a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, etc. In particular, when the content of the matrix component (B) relative to the total amount of the polymer nanoparticles (A) and the matrix component (B) is increased, the Martens hardness HM of the window material (J) decreases. J When the content of the matrix component (B) is reduced, the Martens hardness HM of the window material (J) tends to increase. J tends to decline.

[0282] Elastic recovery rate η of window material (J) ITJ is the total mechanical work of the cavity W total and the elastic return deformation work of the dent W elast This is the ratio of "W elast / W total Ratio of η IT " is a parameter described as "elastic recovery rate η ITJ The higher the elastic recovery rate η, the more the window material can return to its original state when deformed, and the higher its self-repairing ability against deformation. ITJis 0.50 or more under the measurement conditions (Vickers square pyramid diamond indenter, load increase condition 2 mN / 20 sec, load decrease condition 2 mN / 20 sec), and within this range, the larger the value, the more preferable. ITJ is preferably 0.55 or more, more preferably 0.60 or more, and even more preferably 0.65 or more. The measurement of the elastic recovery rate of the window material in this embodiment is not limited to the following, but can be measured, for example, by performing an indentation test on the surface of the window material using a microhardness tester Fischerscope (HM2000S manufactured by Fisher Instruments), an ultra-micro indentation hardness tester (ENT-NEXUS manufactured by Elionix Co., Ltd.), a nanoindenter (iNano, G200 manufactured by Toyo Corporation), a nanoindentation system (TI980 manufactured by Bruker), or the like. Elastic recovery rate η ITJ Methods for adjusting within the above range include, but are not limited to, a coating composition prepared by dispersing and dissolving a composition of polymer nanoparticles (A) and a matrix raw material component (B') described below, which satisfies the predetermined relationship represented by the above formula (3), in a solvent, and coating the resulting coating composition on a substrate and forming a coating film by heat treatment, ultraviolet irradiation, infrared irradiation, or the like.

[0283] In the window material (J), it is preferable to adjust the content of hydrolyzable silicon compound (a). Here, the content of hydrolyzable silicon compound (a) refers to the solid weight ratio of the hydrolyzable silicon compound (a) contained in the polymer nanoparticle (A) to the polymer nanoparticle (A), and the higher the content, the better from the viewpoint of improving abrasion resistance and weather resistance, and the content is preferably 50 mass% or more, more preferably 60 mass% or more. The content of hydrolyzable silicon compound (a) in the polymer nanoparticle (A) is not limited to the following, but can be measured by, for example, IR analysis, NMR analysis, elemental analysis, etc. of the polymer nanoparticle (A). EXAMPLES

[0284] Hereinafter, the present embodiment will be described with reference to specific examples and comparative examples, but the present embodiment is not limited to these.

[0285] <<Example corresponding to the first embodiment>> Various physical properties in the examples and comparative examples described below (hereinafter, unless otherwise specified, "examples" and "comparative examples" in the section <<Examples Corresponding to the First Embodiment>> mean "Examples Corresponding to the First Embodiment" and "Comparative Examples Corresponding to the First Embodiment", respectively) were measured by the following methods.

[0286] (1) Thickness measurement The thickness of each layer was measured using a reflection spectroscopic film thickness meter (product number: FE-3000) manufactured by Otsuka Electronics Co., Ltd.

[0287] (2) Measurement of the minimum film formation temperature of fine particles The E2050S aqueous dispersion or X-2 aqueous dispersion described below, which was used as the adhesive emulsion particles (F), was applied to an aluminum plate placed on a thermal gradient tester using an applicator to form a coating film of 0.1 mm, and then dried to obtain a coating film consisting of the adhesive emulsion particles (F). Separately, Snowtex C or Snowtex OS, which is used as the inorganic oxide (G) as described below, was applied to an aluminum plate placed on a thermal gradient tester using an applicator to form a coating film of 0.1 mm, and then dried to obtain a coating film consisting of the inorganic oxide (G). The minimum film-forming temperature of the obtained coating film was measured using the above-mentioned thermal gradient tester in accordance with JIS K6828-2. The measurement temperature range was 0 to 150°C, and when no film was formed, the minimum film-forming temperature was recorded as over 150°C.

[0288] (3) Average particle size of polymer nanoparticles (A) The cumulant particle size was measured using a dynamic light scattering particle size distribution analyzer (model number: ELSZ-1000) manufactured by Otsuka Electronics Co., Ltd. using an aqueous dispersion of polymer nanoparticles (A) obtained by the method described below, and this was taken as the average particle size of the polymer nanoparticles (A).

[0289] (4) Primary average particle size of inorganic oxides (D) and (G) and aspect ratio of inorganic oxide (G) A transmission microscope photograph was used to observe the particles at a magnification of 50,000 to 100,000 times, and 100 to 200 inorganic oxide particles were photographed. The average major and minor axes of the inorganic oxide particles were measured, and this value was taken as the primary average particle size of inorganic oxides (D) and (G). In addition, the average major axis / average minor axis ratio was calculated from the average major and minor axes measured above, and the obtained value was taken as the aspect ratio.

[0290] (5) Haze measurement The haze was measured by a method specified in JIS K7136 using a turbidity meter (product number: NDH5000SP) manufactured by Nippon Denshoku Industries Co., Ltd. The haze value H1 was measured by the above method for the substrate with the adhesive layer. The haze value H2 was measured by the above method for the laminate (substrate with the adhesive layer and hard coat layer).

[0291] (6) Measurement of surface roughness Ra The surface roughness Ra was measured using a color 3D laser microscope "VK-9700" (product name of Keyence Corporation) as the arithmetic average roughness Ra specified in JIS B0601. The surface roughness Ra1 was measured by the above method on the surface of the substrate with an adhesive layer on which the hard coat layer was formed. The surface roughness Ra2 was measured by the above method on the surface of the laminate (substrate with ...

Claims

[Claim 1] a substrate having an adhesive layer, the adhesive layer being disposed on the substrate and containing adhesive emulsion particles (F), an inorganic oxide (G) and a light-shielding agent (S1); a hard coat layer (C) disposed on the substrate with the adhesive layer and including a matrix component (B) containing an inorganic oxide (D); A laminate comprising: A laminate, wherein a haze value H1 of the substrate with an adhesive layer is greater than a haze value H2 of the laminate.

Citation Information

Patent Citations

  • Surface protective film

    JP2016186010A

  • Hard coat coated film

    JP2017114949A

  • Laminate polyester film

    JP2018104719A

  • Coating composition, coating film, laminate, and process for production of laminate

    WO2010104146A1

  • Polycarbonate molded body

    JP1993339400A